Prebiotic soda lowers postprandial glucose compared to traditional soda pop: A pilot randomized controlled trial - Colleen F. McKenna; Noah Voreades; Michael J. Weiser; Courtney McCormick; Ana M. Valdes; Traci Blonquist; Valerie Kaden; Eunice Mah; Chad M. Cook (Food and Humanity, 2026)

Dietary habits and barriers to healthier eating in Asian American adults, considering ethnic subgroups and immigrant generations - Rachel Cook; Xichen Wang; Rob M. van Dam (Appetite, 2026)

Effects of different LED light wavelengths on deep learning-based insect detection in arable crops - Rabiu Aminu; Samantha M. Cook; David Ljungberg; Oliver Hensel; Abozar Nasirahmadi (Computers and Electronics in Agriculture, 2026)

Survey of management practices related to parasite control from ranched North American bison (Bison bison) in the southern United States - Kaylee R. Kipp; Joe L. Luksovsky; Christine M. Budke; Walter E. Cook; John S. Gilleard; Guilherme G. Verocai (Veterinary Parasitology, 2026)

Urinary biomarkers of PAHs, VOCs, OPEs, and metal(loid)s in firefighters responding in the wildland urban interface (WUI) - Miriam M. Calkins; Alexander C. Mayer; Derek J. Urwin; Steve Bertke; Christine Toennis; Shawn C. Beitel; Jeff Hughes; Jamie Gabriel; Antonia M. Calafat; Christopher M. Reese; Julianne Cook Botelho; Maria Ospina; et al. (International Journal of Hygiene and Environmental Health, 2026)

Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.

Formal Mentorship and Leadership Training Contributes to the Development and Expertise of Graduate Students as Teachers, Scientists, and Engineers - Parker J. Esswein; Clare B. Cook; Lailah Ligons; Kiarra Richardson; Marc A. Sommer; Cameron M. Kim (Biomedical Engineering Education, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Per- and polyfluoroalkyl substances (PFAS) and fish consumption in the Great Lakes Fish Consumer Study (GLFCS) - Meghan Cerpa; Saria Awadalla; Robert M. Sargis; Henry Anderson; Julianne Cook Botelho; Antonia M. Calafat; Victoria Persky; Mary E. Turyk (Chemosphere, 2026)

Ten questions concerning the future of ventilation and indoor air quality in European schools - Robert S. McLeod; Ulla Haverinen-Shaughnessy; Pawel Wargocki; Marcel Loomans; Tunga Salthammer; Twan van Hooff; Malcolm J. Cook; Philomena M. Bluyssen; Atze Boerstra; Froukje van Dijken; Michael Swainson; Christina J. Hopfe (Building and Environment, 2026)

Genes Versus Environment: Body Size Variation Among Recruitment Cohorts of Dungeness Crab - James L. Dimond; Sarah K. Grossman; Emily V. Buckner; Claire E. Cook; Katelyn M. Bosley; Elizabeth D. Tobin; Julie S. Barber (Molecular Ecology, 2026)
Understanding the drivers of phenotypic variation is key to disentangling the evolutionary and environmental forces that shape patterns of trait variation within and among populations. In Dungeness crab, settlement‐stage megalopae exhibit striking seasonal variation in body size, with early season cohorts consistently larger than later ones. This pattern may result from genetically distinct larval sources or environmentally induced plasticity following the temperature–size rule, which predicts larger body size at cooler temperatures. Here, we evaluated the relative contributions of these potential drivers by analysing megalopae size, regional sea surface temperatures and whole‐genome resequencing data from megalopae collected across the ~5‐month settlement season throughout Washington, USA. Genomic analyses revealed a subtle coastal ancestry signal in early‐arriving megalopae, supporting the hypothesis that these megalopae are of coastal origin. Coastal ancestry was associated with larger megalopae, even after accounting for temperature; however, temperature was a stronger predictor, with a standardised effect size more than three times greater than that of ancestry. A genome‐wide association study found no significant associations with megalopae size, suggesting the absence of a strong genotype–phenotype relationship or a lack of statistical power to detect a highly polygenic trait. Together with prior laboratory rearing studies, our findings support a dominant role for environmentally driven plasticity in body size variation. Persistent cohort differences previously observed in juvenile and adult body size raise the possibility that thermal conditions during early life may promote a carryover effect with potentially significant demographic and fishery implications.

Influences of subtle NMDA receptor blockade and allosteric modulation of α5 GABAA receptors on reward-related impulsivity in rats - Jovana Aranđelović; Bojan Batinić; Dishary Sharmin; Danijela Milenković; Đorđe Đorović; V. V. N. Phani Babu Tiruveedhula; James M Cook; Miroslav M Savić (Psychopharmacology, 2026)

Ocean warming (OW) and freshening influence metabolism and cellular damage in Loxechinus albus at the extremes of their Patagonian distribution - Paola A. Villanueva; Jorge M. Navarro; Sebastián Cook; Danae Paredes; Joseline Büchner-Miranda; Eduardo Ramírez-Kuschel; Ignacio Echeverría; Víctor M. Cubillos; Carlos Lara; Marcela Astorga (Marine Pollution Bulletin, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Longitudinal patterns of urinary biomarkers of placental and renal function in pregnancy and associations with early pregnancy exposure to phthalates and replacements - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Reproductive Toxicology, 2026)

Australian stingless bees exhibit greater sensitivity to dimethoate than Apis mellifera: implications for pesticide risk assessment - Gaurav Singh; James C. Makinson; Mary Finlay Doney; Onyeka Peter Nzie; James M. Cook; Robert N. Spooner-Hart (Pesticide Biochemistry and Physiology, 2026)

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

Simultaneous detection of multiple viral pathogens in vacuumed dust from different building types - Austin Shamblin; Calissa Carlisle; Nicholas Nastasi; Genny M. Cook; Anthony C. Fries; Richard T. Agans; Seth Faith; Michael G. Sovic; Vanessa A. Varaljay; Karen C. Dannemiller (Building and Environment, 2026)

Correction: Mid-twenty-first century warm season climate change in the Central United States. Part I: regional and global model predictions - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2026)

Corrigendum to ‘A national-scale preliminary overview study of poly- and perfluoroalkyl substances (PFAS) occurrence in aquatic environments of England, UK’ [Chemosphere 394 (2026) 144804] - R.J. Patel; D.C. Gooddy; B. Marchant; D.J. Lapworth; A. James; M. Cook; K. Darby; T. Besien (Chemosphere, 2026)

Morphological and heat-tolerance traits are associated with progression and impact of, but not vulnerability to, tree decline - Sabina M. Aitken; Pieter A. Arnold; Matthew T. Brookhouse; Alicia M. Cook; Lisa M. Danzey; Rosalie J. Harris; Andy Leigh; Adrienne B. Nicotra (Forest Ecology and Management, 2026)

Associations between air pollution and markers of neuroinflammation, synaptic dysfunction and core Alzheimer’s disease pathology vary by APOE genotype - Kana Kimura; Ira Driscoll; Noah Cook; Sonia Shahzad; Tobey J. Betthauser; Sterling C. Johnson; Sanjay Asthana; Catherine L. Gallagher; Bruce P. Hermann; Mark A. Sager; Kaj Blennow; Henrik Zetterberg; et al. (Neurotoxicity Research, 2026)
To determine whether long-term residential air pollution [AP; ozone (O₃) and fine particulate matter (PM₂.₅)] is associated with (1) incident mild cognitive impairment (MCI) or Alzheimer’s disease (AD), (2) biomarkers of core and AD-relevant pathology, and (3) whether these relationships are moderated by APOE4+/- (carrier/non-carrier of one or both ε4 alleles) status or mediated by neuroinflammation. Sample included 795 participants (Mage 68.7 ± 7.9; 68% female) from the Wisconsin Alzheimer’s Disease Research Center and Wisconsin Registry for Alzheimer’s Prevention parent studies, both enriched for AD risk at enrollment based on parental AD history. Residential zip code and 2009–2021 EPA-based annual AP reports were used to estimate individual exposure. Cox proportional hazards models assessed MCI/AD risk. Linear regressions examined the relationships between AP exposure and biomarkers of core and AD-relevant pathology, with and without APOE4 + stratification. Causal mediation analysis examined whether markers of inflammation mediated the AP-AD pathology relationships. Neither O₃ nor PM₂.₅ exposure predicted MCI/AD incidence nor core AD pathology (Ps > 0.05). Higher PM₂.₅ was associated with higher CSF GFAP levels ( P = 0.003). APOE4 + with higher levels of PM₂.₅ exposure had higher CSF levels of tTau ( P = 0.01), pTau₁₈₁ ( P = 0.01) and neurogranin ( P = 0.02). These relationships were not mediated by neuroinflammation (Ps > 0.05). In this AD-risk enriched cohort, AP was not associated with MCI/AD incidence. However, higher PM₂.₅ exposure was associated with astrocytic activation, and in APOE4+, AD pathology, neurodegeneration, and synaptic dysfunction. Our findings suggest AP as an environmental risk factor contributing to AD-relevant pathology, particularly among genetically at-risk individuals.

Donkeys as livestock guardians against predators in an African savanna - Dhananjaysinh Y. Jhala; Dallas Ruble; Utarera Katjavivi; Stijn Verschueren; Robin M. Cook; Laurie L. Marker; Bogdan Cristescu (European Journal of Wildlife Research, 2026)

Correction: Mid-twenty-first century climate change in the Central United States. Part II: Climate change processes - Christina M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2026)

Correction: Northern African climate at the end of the twenty-first century: an integrated application of regional and global climate models - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2026)

Correction: Sub-Saharan Northern African climate at the end of the twenty-first century: forcing factors and climate change processes - Christina M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2026)

Cognition as a Conservation Tool: A Case Study of Florida Manatees and Boat Strikes - Gordon B. Bauer; Charles J. Deutsch; Roger L. Reep; Wendi Fellner; Tabitha Gunnars; Peter F. Cook; Heidi E. Harley; Athena M. Rycyk (Marine Mammal Science, 2026)
Boat strikes injure and kill large numbers of Florida manatees ( Trichechus manatus latirostris ) each year. Management actions taken to mitigate this threat can be potentially enhanced by consideration of manatee cognitive processes. The role of cognition in marine mammal conservation has received little consideration in the literature. Here, we integrate discoveries from laboratory research on auditory sensory processes and perception with findings from field studies of how manatees respond to motorized vessels and the effect of the ambient soundscape on response times to boat noise. We incorporate that information into recommendations for manatee management to further reduce the risk of collisions. We also suggest lines of research to investigate other relevant cognitive issues—including attention, learning, memory, and decision‐making—to improve conservation efforts and understanding of manatee behavior.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Rethinking nature-based solutions in informal settlements: community perceptions of urban risk in Durán, Ecuador - Margot Mattson; Isabella Pacenza; Shruti Jadala; Carlos Romero; Addison Martin; Marta Berbes-Blazquez; Elizabeth M. Cook; Mathieu Feagan; Mercy Borbor-Cordova; Pilar Cornejo-Rodriguez; Nancy B. Grimm (Climate and Development, 2026)

Investigating the effects of biogenic amines on the dominance hierarchy in the small carpenter bee, Ceratina calcarata - Riya N. Miller; Sandra M. Rehan; Chelsea N. Cook; Colin S. Brent; Sarah P. Lawson (Insectes Sociaux, 2026)
Biogenic amines are highly conserved across animal species and aid in the regulation of movement, behavior, motivation, temperature, blood pressure, and endocrine secretion. Within eusocial species, such as the honey bee Apis mellifera , biogenic amines are responsible for modulating traits associated with higher levels of sociality, such as division of labor. In Ceratina calcarata , a facultatively social bee species, mothers establish a dominance hierarchy over their eldest daughter by providing them with less pollen and less protein, resulting in smaller, more submissive adults referred to as dwarf eldest daughters (DEDs). We hypothesized that this dominance hierarchy is additionally modulated by biogenic amines. To examine this hypothesis, we first compared biogenic amine levels between mothers and daughters and found significantly higher levels of dopamine, octopamine and tyramine in the mothers. To quantify the effects of these biogenic amine differences, dopamine was topically administered to C. calcarata DEDs, while the mothers were topically treated with the dopamine blocker cis-(Z)-Flupentixol dihydrochloride. Aggression helps to establish social hierarchies, so mothers and DEDs from the same nest underwent behavioral assays to assess aggressive and tolerant behaviors. When dopamine was blocked in the naturally more aggressive mothers, there was no difference in the number of aggressive interactions. Instead, treated mothers became more tolerant of DEDs, indicating dopamine plays a key role in modulating these behaviors. More work is needed to understand the different roles each biogenic amine plays in the development of a dominance hierarchy, especially in these species on the brink of eusociality.

The enemy of my enemy is not always my friend: Susceptibility of honey bee to entomopathogenic nematodes - Alihan Katlav; Sitaram Aryal; Manoj Dhakal; Michael Duncan; Clarissa M. House; Uffe N. Nielsen; James M. Cook; Robert N. Spooner-Hart; Markus Riegler (Journal of Invertebrate Pathology, 2026)

Integrating the Microbiome Into Infection Ecology and Evolution in Wild Animals - Jingdi Li; Ian Will; Luís M. Silva; Tommy J. Travers‐Cook; Paradyse E. Blackwood; Kayla C. King (Molecular Ecology, 2026)
Parasites are a ubiquitous force in nature threatening wildlife populations and ecosystems. Interactions between hosts and their parasites are impacted by host‐associated microbiomes, which are essential for host development, physiology and immunity. We synthesise current understanding of the ecological interactions between host microbiomes and parasites, ranging from competitive to facilitative, and explore their potential evolutionary consequences for parasite virulence and transmission in the wild. We highlight recent mechanistic insights that support integrating a microbiome perspective into wildlife parasitology, with examples across diverse animal taxa including amphibians, bats, insects and corals, particularly within the context of climate change. Adopting such a holistic approach can open new avenues whereby host microbial shifts can be used to predict and mitigate infectious diseases in wild populations. Finally, we propose a conceptual framework to guide future research on microbiome‐parasite–host interactions, aiming to better reflect natural ecological complexities and advance both fundamental understanding and conservation applications.

A Dominant Founder Lineage Has Possible Fitness Costs for the Endangered Mexican Grey Wolf - Yeraldi Loera; Manisha Khakoo; Emily Krueckeberg; Ingrid G. Nilsson; Zehao Wu; Maggie Dwire; Jennifer Adams; Lisette Waits; John K. Oakleaf; Mariel L. Campbell; Jonathan L. Dunnum; Joseph A. Cook; et al. (Molecular Ecology, 2026)
The Mexican grey wolf ( Canis lupus baileyi ) is an endangered and genetically distinct subspecies of grey wolf adapted to the warm climates of the southwestern United States and Mexico. Following centuries of eradication efforts, Mexican grey wolves were protected under the Endangered Species Act in 1976, prompting an international ex situ breeding program to preserve their genetic legacy. Seven remnant wolves founded the three distinct lineages of this program: McBride, Ghost Ranch, and Aragón. However, concerns of rising inbreeding levels motivated the implementation of inter‐lineage pairings to decelerate genetic erosion. To evaluate the genetic health of the ex situ managed population, we analysed genome‐wide variation across several generations of breeding wolves and their descendants ( n = 179). Despite ongoing conservation interventions, we found a sharp decline in effective population size over the past 50 generations. However, estimates of inbreeding diminished over time following the inter‐lineage pairings, reflecting efficient pedigree management or potential fitness costs of inbreeding depression, as higher levels of inbreeding and autozygosity were associated with reduced lifespan and reproductive performance. Increasing contributions of Ghost Ranch and Aragón ancestry also aided in reducing levels of inbreeding observed in the more genetically distinct McBride lineage. These findings highlight the challenges of maintaining genetic diversity in bottlenecked populations, reveal fine‐scale patterns of inbreeding within the pedigree and underscore the urgent need to preserve genetic contributions from all founder lineages. Genomic insights from this study can guide breeding strategies to reduce kinship, balance ancestry and mitigate inbreeding depression, safeguarding the evolutionary legacy and the long‐term persistence of the Mexican grey wolf.

A national-scale preliminary overview study of poly- and perfluoroalkyl substances (PFAS) occurrence in aquatic environments of England, UK - R.J. Patel; D.C. Gooddy; B. Marchant; D.J. Lapworth; A. James; M. Cook; K. Darby; T. Besien (Chemosphere, 2026)

Detection of foodborne viruses in berries – State of science and future considerations - Lee-Ann Jaykus; Sabah Bidawid; Albert Bosch; Sophie Butot; Nigel Cook; Sanjay Gummalla; James Lowther; Neda Nasheri; Rosa M. Pintó; Donald W. Schaffner; Magnus Simonsson; Branko Velebit; et al. (Food Control, 2026)

Correction to: Bias correction of precipitation from convection-permitting models at the point scale: a case study in Switzerland - Trang Nguyen; Patricio Velasquez; Andreas Dietzel; Lauren M. Cook (Climatic Change, 2026)

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

Cooling potential of stormwater blue-green infrastructure depends on soil type and water availability - Giovan Battista Cavadini; Gabriele Manoli; Lauren M. Cook (Sustainable Cities and Society, 2026)

An Expansion of Weight Inclusivity to Include Body Autonomy and Harm Reduction: Striving for Health Equity - Rachel W. Goode; Tyisha Harper-Cooks; Ana Paola Campos; Katherine Matthes; Julian Robles; Claudia M. Calderon; Michelle Chen Lee; Millicent N. Robinson; Ramine C. Alexander (Journal of the Academy of Nutrition and Dietetics, 2026)

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

Air quality at mass gatherings: assessing ventilation and occupancy in marquees to evaluate airborne infection risk during the COVID-19 pandemic - Ben M. Roberts; Filipa Adzic; Ailsa Hamilton-Smith; Christopher Iddon; Oliver Wild; Malcolm Cook; Steve Gwynne; Aoife Hunt; Liora Malki-Epshtein (Building and Environment, 2026)

Adding value to imperfect long-term animal monitoring data for conservation insight - S.D. Sarre; E.J. Stringer; R. Brawata; E. Carlson; R. Colley; E. Cook; B. Croak; L.I. Doucette; M. Hoehn; B. Howland; W.S. Osborne; S. Pulsford; et al. (Biological Conservation, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Metabolic and survival responses of the carnivorous snail Acanthina monodon to extreme marine heatwaves - Paola A. Villanueva; Joseline A. Büchner-Miranda; Jorge M. Navarro; Sebastián Cook; Octavio Mercado-Peña; Paula Amador-Véliz; Gonzalo Donoso; Elisabeth Teca Oliva; Oscar R. Chaparro (Regional Studies in Marine Science, 2025)

Corrigendum to Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission Remote Sensing of Environment Volume 329, 1 November 2025, 114929 - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Concentrations of per- and polyfluoroalkyl substances (PFAS) in private well drinking water and serum of individuals exposed to PFAS through biosolids: The Maine Biosolids Study - Rachel Criswell; Katherine Senechal; Anne M. Mullin; Antonia M. Calafat; Julianne Cook Botelho; Lisa B. Rokoff; Abby F. Fleisch (Environmental Pollution, 2025)

Examining Explicit Stereotype Perceptions of Colorectal Cancer Screening and Diagnosis in the Hispanic Community - Aidan Foley; Bianca Luna-Lupercio; Jessica M. Capaldi; Galen Wiens-Cook; Vinicius Calsavara; Zulfikarali Surani; Sarah-Jeanne Salvy; Jane C. Figueiredo; Robert Haile; Nenette A. Cáceres; Celina H. Shirazipour (Journal of Cancer Education, 2025)
Cancer is a leading cause of death among Hispanic people in the USA. One potential reason is low adherence to cancer screening guidelines, particularly for colorectal cancer (CRC). Previous research suggests that low CRC screening may be linked to negative stereotypes associated with cancer and CRC screening methods. The purpose of this study was to examine explicit stereotype perceptions of CRC screening and diagnosis in the Hispanic community. Hispanic adults ( n = 279) were asked to read three vignettes presenting a gender-neutral individual who was either diagnosed with CRC, completed colonoscopies for CRC screening, or was a control (no cancer information provided). Using the Stereotype Content Model approach, after reading each vignette, participants completed measures assessing explicit perceptions (warmth and competence) of the individual. Linear mixed-effects models were fitted to evaluate differences in perceptions between vignettes. The main effect indicated no significant difference in warmth or competence perceptions based on vignette condition ( p = .78). However, there was a significant difference in explicit perceptions based on the study participant’s Hispanic heritage, gender, and age ( p s < .05). Findings emphasize differences in explicit perceptions of cancer and cancer screening based on important demographic characteristics. Thus, important implications include the need for cancer educational materials and interventions to consider the important heterogeneity within the Hispanic community. Future CRC screening interventions should be tailored based on Hispanic heritage, gender, and age.

The miRNomics of antiretroviral therapy-induced obesity - Niska Majumdar; Bishwa R. Pokharel; Abigail Dickerson; Andreea Cruceanu; Smit Rajput; Lok R. Pokhrel; Paul P. Cook; Shaw M. Akula (Functional & Integrative Genomics, 2025)
Human immunodeficiency virus (HIV) is a retrovirus that incorporates its genetic material into the host’s chromosome. The resulting diseases and related conditions constitute a global health problem as there are no treatments to eliminate HIV from an infected individual. However, the potent, complex, and active antiretroviral therapy (ART) strategies have been able to successfully inhibit HIV replication in patients. Unfortunately, obesity following ART is frequent among HIV-infected patients. The mechanism underlying ART-induced obesity is characterized based on expression of traditional markers such as genes and proteins. However, little is known about, yet another key component of molecular biology known as microRNAs (miRNAs). Micro-RNAs are ~ 22 base-long non-coding nucleotides capable of regulating more than 60% of all human protein-coding genes. The interest in miRNA molecules is increasing and their roles in HIV and obesity are beginning to be apparent. In this review, we provide an overview of HIV and its associated diseases, ART-induced obesity, and discuss the roles and plausible benefits of miRNAs in regulating obesity genes in HIV-infected patients. Understanding the roles of miRNAs in ART-induced obesity will aid in tracking the disease progression and designing beneficial therapeutic approaches.

Bias correction of precipitation from convection-permitting models at the point scale: a case study in Switzerland - Trang Nguyen; Patricio Velasquez; Andreas Dietzel; Lauren M. Cook (Climatic Change, 2025)
In comparison to regional climate models, convection-permitting models (CPMs) improve predictions of short-duration extreme rainfall by resolving convective processes. Their sub-daily rainfall output is thus valuable for impact models like those used for urban drainage systems. However, limitations remain, including short simulation periods and biases requiring correction to match station-scale resolution. To overcome these limitations, this study evaluates five quantile mapping (QM) approaches to bias correct and downscale sub-hourly COSMO-CLM simulations at 2.2 km resolution to the station scale using data from over 70 weather stations in Switzerland. To more effectively analyze the impact of QM on different rainfall features, stations were grouped based on location, altitude, and rainfall characteristics through an unsupervised clustering algorithm. Conventional QM was tested against several advanced methods, including using a moving window, spatial pooling, and extending the observational record. These techniques were validated using cross-validation and by evaluating several historical rainfall indices and the climate change signal. Results reveal that wet biases in raw CPM output remain and can exceed 90%. QM reduces biases in annual precipitation indices, but conventional QM often overcorrects, introducing dry biases in extreme quantiles. Additionally, all QM approaches can modify climate change signals, inflating or reversing trends in key indices. Combining spatial pooling with a moving window shows the most promise for reducing overall bias; however, challenges persist, such as data scarcity for extreme events, observation-simulation precision disparities, and short calibration periods. Future work should explore seasonality and utilize diverse CPM ensembles for more reliable precipitation projections.

The impacts of marine heatwaves on ecosystems and fisheries in Aotearoa New Zealand - Katie M. Cook; Matthew R. Dunn; Erik Behrens; Matt H. Pinkerton; Cliff S. Law; Vonda J. Cummings (New Zealand Journal of Marine and Freshwater Research, 2025)
Marine heatwaves (MHWs) are increasing in frequency and intensity globally, yet the impacts of such extreme events are not well understood. We review the effects of MHWs on the fisheries and ecosystems of Aotearoa‐New Zealand (NZ), an island nation with over 15,000 km of coastline, and 4 million km 2 of exclusive economic zone, that supports diverse marine communities and valuable commercial and recreational fisheries. Using Aotearoa‐NZ and global literature, we discuss the potential effects of MHWs on the physical environment and on species, populations and ecosystems. We review recorded national impacts with a fisheries focus, and systematically assess MHW effects on 32 commercially or culturally important Aotearoa‐NZ wild‐caught fishery or aquaculture species, classifying their vulnerabilities. We found records of MHW‐induced ecosystem shifts, with macroalgae community change, and out‐of‐range occurrences of warm‐water species. Of the 32 species examined, national MHW impacts were documented for three species (green‐lipped mussel, snapper, and Chinook salmon). We highlight the paucity of information for life‐stage specific impacts, and indirect impacts such as changes in predator‐prey interactions and biogenic habitat distributions. Assessing MHW impacts through a fisheries lens highlights the need for enhanced interdisciplinary research and monitoring, to develop sustainable management strategies under environmental change.

Insights from U.S. beekeeper triage surveys following unusually high honey bee colony losses 2024–2025 - Anthony Nearman; Christopher L. Crawford; M. Marta Guarna; Priyadarshini Chakrabarti; Katie Lee; Steven Cook; Elizabeth Hill; Arathi Seshadri; Garett Slater; Zachary S. Lamas; Yan Ping Chen; Danielle Downey; et al. (Science of The Total Environment, 2025)

Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

Stakeholder values on the management of African elephants for large tree conservation in protected areas - Robin M. Cook; Ed T. F. Witkowski; Michelle D. Henley (European Journal of Wildlife Research, 2025)
Stakeholder perspectives play a crucial role in conservation decisions, particularly for species with complex ecological and social impacts, such as African savanna elephants ( Loxodonta africana ). In a South African protected area experiencing high elephant densities and significant tree loss, we surveyed 170 stakeholders, including conservation managers, property owners, tourists, and tourism personnel. Using a Likert scale and thematic analysis, we evaluated their attitudes towards tree protection, waterhole closures, contraception, and culling to mitigate elephant impacts on large trees. Results showed strong support for waterhole closures and tree protection, particularly among younger conservation managers and property owners, who viewed these methods as effective in dispersing elephant populations and safeguarding valuable trees. Conversely, tourists and younger stakeholders preferred non-lethal strategies like contraception, while conservation managers expressed practical concerns about its feasibility. Culling emerged as the most divisive strategy, supported primarily by older and male stakeholders in conservation but largely opposed by tourists due to ethical concerns. The chord diagram illustrated distinct patterns, with conservation managers aligning more with waterhole closures and culling, while property owners and tourists favoured tree protection and contraception. These findings highlight the diversity in stakeholder values, shaped by demographic factors, and underscore the need for adaptive, context-specific management strategies. Our study provides a framework for conservation policies that balance ecological objectives with social acceptability, promoting sustainable coexistence between elephants, large trees, and diverse stakeholder interests.

Time since HIV diagnosis is linked to amnestic mild cognitive impairment (MCI) in older adults with HIV - Jason S. DeFelice; Mark K. Britton; Yancheng Li; Eric C. Porges; Gladys E. Ibañez; Charurut Somboonwit; Robert L. Cook; Ronald A. Cohen; Joseph M. Gullett (Journal of NeuroVirology, 2025)

We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Green roofs harbor different and non-substituting invertebrate communities than surrounding ground-level habitats - Kilian Perrelet; Marco Moretti; Océane Inglard; Florian Altermatt; Lauren M. Cook (Journal of Environmental Management, 2025)

Corrigendum to “Exposure to endocrine disrupting chemicals including phthalates, phenols, and parabens in infancy: Associations with neurodevelopmental outcomes in the MARBLES study” [IJHEH 261 (2024) 114425] - Jennie Sotelo-Orozco; Antonia M. Calafat; Julianne Cook Botelho; Rebecca J. Schmidt; Irva Hertz-Picciotto; Deborah H. Bennett (International Journal of Hygiene and Environmental Health, 2025)

A higher-order finite-element implementation of the nonlinear Fokker–Planck collision operator for charged particle collisions in a low density plasma - M.R. Hardman; M. Abazorius; J. Omotani; M. Barnes; S.L. Newton; J.W.S. Cook; P.E. Farrell; F.I. Parra (Computer Physics Communications, 2025)

Four unusual mortality events of seabirds in the Patagonian Sea, 2000–2006: species affected and possible causes - Marcela M. Uhart; Ralph E. T. Vanstreels; Flavio Quintana; Belén Mattera; Nora Montoya; Leonardo Guzman; Hernan Pacheco Valles; Gemita Pizarro; Carolina A. Marull; Luciana Pozzi; Torsten Mörner; Pablo García-Borboroglu; et al. (Polar Biology, 2025)
The Patagonian Sea is a highly productive marine ecosystem and a hotspot for seabird diversity and density in the Southwest Atlantic Ocean. Reports of unusual mortality events are relatively scarce in this region, likely due to under detection and investigation. In this study, we report on four unusual mortality events affecting seabirds in the Patagonian Sea from 2000 to 2006. Events 1 and 2 occurred at Golfo Nuevo and Chubut coast, Argentina in September–December 2000, affecting at least 4550 seabirds, mainly Magellanic penguins ( Spheniscus magellanicus ). Event 3 occurred at the Falkland/Malvinas Islands during December 2002–January 2003, affecting at least 3500 seabirds, mainly gentoo penguins ( Pygoscelis papua ). Event 4 occurred at Punta Loma and Punta León, Argentina, in November 2006, affecting at least 57 seabirds, mainly kelp gulls ( Larus dominicanus ). The aetiology of Events 1 and 2 could not be determined, but malnutrition/starvation and paralytic shellfish poisoning, respectively, were identified as potential causes. Pathological findings and toxicological testing supported paralytic shellfish poisoning as the cause of Events 3 and 4. Our results illustrate how identifying the occurrence, cause and extent of unusual mortality events affecting seabirds can present significant challenges. Moreover, our investigations of the events display variations in timeliness and completeness, and our lack of certainty on aetiology reflects the shortcomings often faced in remote locations and low resource settings. Technological advances, such as smartphones, increased public awareness and connectivity, coupled with more and better equipped protected areas and diagnostic laboratories will likely aid in overcoming difficulties from past decades.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Forty-five years of removal campaigns for feral ungulates reveal strategies for success and future directions - Nathan P. Snow; Keely J. Kohen; Ingrid A. Messer; Abigail Pagels; Seth M. Cook; Scott Beckerman; Travis Guerrant; Kurt C. VerCauteren; Kim M. Pepin (Biological Invasions, 2025)
Feral or invasive ungulates (hereafter: feral ungulates) exist worldwide, and their ability to thrive threatens biodiversity, degrades ecosystems, and causes damage to agriculture and properties. Strategies for removing feral ungulates from their introduced insular and mainland ranges have varied greatly, successes have been difficult, and the need is increasing. We reviewed published scientific literature on feral ungulate eradication and maximum control campaigns during 1978–2023 to identify practices that led to greater success. Of 54 campaigns, 32 (59%) reported success. Most campaigns focused on feral swine (61%; Sus scrofa ) or feral goats (24%; Capra hircus ). The average duration of a campaign was 61 months and cost an average of $1.9 m ($USD 2024) or $636/km 2 /month. The most important components for success included ensuring adequate funding was secured for the campaign ($0.5–1 million/km 2 is recommended) and population recovery or reinvasion were minimized. The frequency of campaigns has increased during the last 45 years; however, the areas worked (km 2 ), monthly durations, removal techniques used, funding, and ultimately the rates of success have not changed. A lack of increasing success for larger and more complex campaigns indicated that modernization of technologies for population control has been minimal, and larger breakthroughs are needed. Safe and effective toxicants and sterilants may provide those advances if developed. Lessons learned from campaigns indicate that pilot testing control methods prior to initiating full campaigns may help to alleviate uncertainties, produce more reliable plans, and help inform the biology of the animals being targeted for removal.

Expanding Monitoring Capacity for Potential Invasive Species in Arctic Canada With Environmental DNA Metabarcoding - Elizabeth Boyse; Melody S. Clark; Ian M. Carr; Alison J. Cook; Philippe Archambault; Jean E. Holloway; Zhewen Luo; Michael Milton; Mathieu Roy; Jackie Dawson; Victoria L. Peck (Global Change Biology, 2025)
To date, environmental conditions have been enough to act as an effective barrier to prevent non‐indigenous species from arriving and establishing in Arctic Canada. However, rapidly changing climatic conditions are creating more suitable habitats for non‐indigenous species to potentially establish and become invasive. Concurrently, shipping traffic in parts of Arctic Canada has increased by over 250% since 1990, providing an effective vector for transporting non‐indigenous species to the region. Arctic Canada has been historically undersampled, so Arctic biota inventories are incomplete, hampering efforts to establish if a species is new to the region (and potentially invasive) or newly discovered. In this study, we utilize environmental DNA (eDNA) metabarcoding and ships of opportunity to assess eukaryotic community composition and potential invasives along one of the busiest shipping routes, the Northwest Passage. One liter seawater samples were collected in triplicate at 27 locations, targeting touristic hotspots frequently visited by passenger vessels. Eukaryotic DNA was amplified from the 18S rRNA V9 and COI regions, resulting in 126 unique Amplicon Sequence Variants (ASVs) detected with COI and 391 ASVs with 18S, providing an important snapshot of current community composition. Copepods, dinoflagellates, and diatoms were the most abundant taxonomic groups, correlating well with previous net sampler surveys, validating the efficacy of eDNA for biodiversity surveillance. We also report the first detections of a prolific invasive species, the bay barnacle ( Amphibalanus improvisus ), in Arctic Canada. Further work is currently in progress to establish whether these detections represent transient barnacle larvae or sessile adults capable of recruiting and reproducing. Our study demonstrates the utility of eDNA for the detection of non‐indigenous species in a data‐poor area, which, if combined with citizen science initiatives and local communities, could provide a vital monitoring tool for the detection of new invasives in this rapidly changing area.

Urbanisation Drives the Decoupling, Simplification, and Homogenization of Aquatic and Terrestrial Food Webs - Kilian Perrelet; Lauren M. Cook; Merin Reji Chacko; Florian Altermatt; Marco Moretti (Ecology Letters, 2025)
Aquatic and terrestrial communities often co‐occur at close distances, enabling biotic interactions across ecosystem boundaries. While such interactions in natural habitats contribute to complex, coupled food webs, their dynamics in engineered and fragmented urban habitats are hardly known. Using environmental DNA metabarcoding and a metaweb approach, we examined food web structure at 54 paired aquatic‐terrestrial sites along an urbanisation gradient in Zurich, Switzerland. We found that urbanisation led to simpler, less connected, and more homogeneous food webs by replacing high‐trophic‐level predators with low‐trophic‐level basal consumers. This shift towards basal consumers, dependent on distinct aquatic or terrestrial basal resources, subsequently weakened the links between aquatic and terrestrial food webs. Conversely, enhancing habitat quantity and landscape connectivity bolstered predator diversity, promoting vertically diverse, connected, complex, and stable food webs. Our findings reveal that while urbanisation can disrupt aquatic‐terrestrial food webs, careful urban habitat planning can enhance biodiversity and food web stability.

Aquatic and terrestrial environmental DNA signals reveal decoupling of blue-green communities along an urbanization gradient - Kilian Perrelet; Lauren M. Cook; Andreas Dietzel; Florian Altermatt; Marco Moretti (Landscape and Urban Planning, 2025)

Exposure to phthalates and replacements during pregnancy in association with gestational blood pressure and hypertensive disorders of pregnancy - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Emma M. Rosen; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Environmental Research, 2025)

Harmonizing nature’s timescales in ecosystem models - Vivienne P. Groner; Jacob Cook; C. David L. Orme; Priyanga Amarasekare; Edward Comyn-Platt; Taran Rallings; Jaideep Joshi; Robert M. Ewers (Trends in Ecology & Evolution, 2025)

Prenatal per- and polyfluoroalkyl substance mixtures and weight for length from birth to 12 months: The New Hampshire Birth Cohort Study - Gyeyoon Yim; Caitlin G. Howe; Lisa G. Gallagher; Diane Gilbert-Diamond; Antonia M. Calafat; Julianne Cook Botelho; Margaret R. Karagas; Megan E. Romano (Science of The Total Environment, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Dynamic cooling: Thermal and temporal effects on cognitive load and performance in office environments - Amelie Reitmayer; Sebastian Clark Koth; Kelly R Johnstone; Cassandra Madigan; Margaret M Cook (Building and Environment, 2025)

Native Australian seedlings exhibit novel strategies to acclimate to repeated heatwave events - Philippa R. Alvarez; Rosalie J. Harris; Alicia M. Cook; Verónica F. Briceño; Adrienne B. Nicotra; Andrea Leigh (Oecologia, 2025)
Heatwaves are becoming more intense and frequent. Plant photosystem thermal thresholds can vary with species, but also shift in response to environmental triggers. Both upper and lower thresholds can acclimate to repeated heatwaves through ecological stress memory, where prior exposure primes them for subsequent events. The extent to which acclimation to repeated heat stress events varies among environmental origin and/or species is unknown. Different acclimation strategies might reflect biome of origin, or may be species-specific. For 12 species from two contrasting biomes—extreme desert and benign coastal temperate—we investigated responses to two simulated heatwaves, via shifts in upper and lower critical temperatures of photosystem II, and the difference between these thresholds, thermal tolerance breadth (TTB). Biome of origin had no effect on thermal tolerance. Observed differences among species following heat events suggested two possible acclimatory strategies. In some cases, species increased thermal thresholds during the first heatwave, but at the cost of reduced thermal tolerance during the second heatwave, a sprinter strategy. Other species acclimated to the first heatwave and further increased thermal tolerance to a second heatwave, indicative of ecological stress memory, a marathoner strategy. Synthesis: these among-species responses to heatwaves could suggest distinct vulnerabilities and resilience to repeat heat stress events, with some species having limited capacity to tolerate consecutive heatwaves, possibly as the cost of acclimation is too great, with other species having the advantage of increased tolerance via stress memory, helping them survive future stress, at least in the short-term.

Correction to: Structural controls on cobalt mineralisation during regional metamorphism: an example from the Rajapalot area, Finland - Mohammad Sayab; Andrew Menzies; Richard M. Palin; Alan R. Butcher; Nick Cook; Jukka Kuva; Quentin Dehaine (Mineralium Deposita, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Prenatal per- and polyfluoroalkyl substances and blood pressure trajectories in the New Hampshire Birth Cohort Study - Yuting Wang; Elizabeth C. Anderson; Caitlin G. Howe; Jiang Gui; Lisa G. Gallagher; Brianna Heggeseth; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas; Megan E. Romano (International Journal of Hygiene and Environmental Health, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

STICr: An open-source package and workflow for stream temperature, intermittency, and conductivity (STIC) data - Sam Zipper; Christopher T. Wheeler; Delaney M. Peterson; Stephen C. Cook; Sarah E. Godsey; Ken Aho (Environmental Modelling & Software, 2025)

Per- and polyfluoroalkyl substances (PFAS) exposure in the U.S. population: NHANES 1999–March 2020 - Julianne Cook Botelho; Kayoko Kato; Lee-Yang Wong; Antonia M. Calafat (Environmental Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Microplastic pollution in salt marsh and urban tributary sediment cores of the River Thames estuary, UK: Spatial and temporal accumulation trends - Megan M. Trusler; Sarah Cook; Barry H. Lomax; Christopher H. Vane (Marine Pollution Bulletin, 2025)

New York City 2100: Environmental justice implications of future scenarios for addressing extreme heat - Maya Dutta; Pablo Herreros-Cantis; Timon McPhearson; Ahmed Mustafa; Matthew I. Palmer; Mika Tosca; Jennifer Ventrella; Elizabeth M. Cook (Landscape and Urban Planning, 2025)

Associations between per- and polyfluoroalkyl substances (PFAS) and female sexual function in a preconception cohort - Samantha Schildroth; Julia C. Bond; Amelia K. Wesselink; Jasmine Abrams; Antonia M. Calafat; Julianne Cook Botelho; Katharine O. White; Ganesa Wegienka; Elizabeth E. Hatch; Lauren A. Wise (Environmental Research, 2025)

A critical review of ventilation effectiveness in naturally ventilated spaces from the perspective of sustainability and health - M. Mustafa; M.J. Cook; R.S. McLeod (Building and Environment, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Operational lessons learned from simulating an elimination response to a transboundary animal disease in wild animals - K. Chalkowski; K.M. Pepin; M.J. Lavelle; R.S. Miller; J. Fischer; V.R. Brown; M. Glow; B. Smith; S. Cook; K. Kohen; S. Sherburne; H. Smith; et al. (Preventive Veterinary Medicine, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Structural controls on cobalt mineralisation during regional metamorphism: an example from the Rajapalot area, Finland - Mohammad Sayab; Andrew Menzies; Richard M. Palin; Alan R. Butcher; Nick Cook; Jukka Kuva; Quentin Dehaine (Mineralium Deposita, 2025)
The Rajapalot area of Finnish Lapland hosts an unusually high-grade association of cobalt-only and gold–cobalt deposits (10.91 Mt @ 2.5 g/t Au + 0.044% Co total inferred resources) within multiply folded metasedimentary rocks of the Paleoproterozoic Svecofennian collisional orogeny. Through the integration of X-ray computed micro-tomography and micro-X-ray fluorescence raster imaging of drill-core samples, we produce a model of cobalt-bearing ore mineralisation, which reveals primary fluid transportation mechanisms and precipitation pathways. When combined with the deposit-scale, high-resolution ground-based magnetic geophysical data, we show that cobalt-bearing ores in the Rajapalot region occur mostly as saddle reefs located in dilated fold hinges, which formed by simultaneous synthetic and antithetic shearing along developing crenulation-cleavage planes and incompetent bedding layers, respectively. We suggest that multi-layered rock complexes with alternations of competent and incompetent layers deformed and metamorphosed to upper greenschist-lower amphibolite facies should represent focus regions for cobalt exploration targeting campaigns in orogenic belts. The non-destructive workflow presented in this study could be an integral part of an early stage of cobalt mineral processing and traceability before metallurgical treatment.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Species Sensitivity Distribution (SSD) profiles towards λ-cyhalothrin for key ecosystem service provider (ESP) species across five European countries representing different pedoclimatic zones - José M. Blanco-Moreno; Berta Caballero-López; Samantha M. Cook; Stephen P. Foster; Danuta Frydryszak; Ryszard Laskowski; Patricia Ortega-Ramos; Mykola Rasko; Pauline Reichardt; José Paulo Sousa; Grzegorz Sowa; Renata Śliwińska-Grochot; et al. (Science of The Total Environment, 2024)

Exploring resource recovery from diverted organics: Life cycle assessment comparison of options for managing the organic fraction of municipal solid waste - Brooke M. Marten; Sherri M. Cook (Science of The Total Environment, 2024)

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

New insights to be gained from a Virtual Ecosystem - Robert M. Ewers; Jacob Cook; Olivia Z. Daniel; C.David L. Orme; Vivienne Groner; Jaideep Joshi; Anna Rallings; Taran Rallings; Priyanga Amarasekare (Ecological Modelling, 2024)

Mechanistic in silico explorations of the immunogenic and synergistic effects of radiotherapy and immunotherapy: a critical review - Allison M. Ng; Kelly M. MacKinnon; Alistair A. Cook; Rebecca A. D’Alonzo; Pejman Rowshanfarzad; Anna K. Nowak; Suki Gill; Martin A. Ebert (Physical and Engineering Sciences in Medicine, 2024)
Immunotherapy is a rapidly evolving field, with many models attempting to describe its impact on the immune system, especially when paired with radiotherapy. Tumor response to this combination involves a complex spatiotemporal dynamic which makes either clinical or pre-clinical in vivo investigation across the resulting extensive solution space extremely difficult. In this review, several in silico models of the interaction between radiotherapy, immunotherapy, and the patient’s immune system are examined. The study included only mathematical models published in English that investigated the effects of radiotherapy on the immune system, or the effect of immuno-radiotherapy with immune checkpoint inhibitors. The findings indicate that treatment efficacy was predicted to improve when both radiotherapy and immunotherapy were administered, compared to radiotherapy or immunotherapy alone. However, the models do not agree on the optimal schedule and fractionation of radiotherapy and immunotherapy. This corresponds to relevant clinical trials, which report an improved treatment efficacy with combination therapy, however, the optimal scheduling varies between clinical trials. This discrepancy between the models can be attributed to the variation in model approach and the specific cancer types modeled, making the determination of the optimum general treatment schedule and model challenging. Further research needs to be conducted with similar data sets to evaluate the best model and treatment schedule for a specific cancer type and stage.

Microplastics pollution in sediments of the Thames and Medway estuaries, UK: Organic matter associations and predominance of polyethylene - Megan M. Trusler; Vicky L. Moss-Hayes; Sarah Cook; Barry H. Lomax; Christopher H. Vane (Marine Pollution Bulletin, 2024)

Avoidance and attraction responses of kittiwakes to three offshore wind farms in the North Sea - Christopher J. Pollock; Daniel T. Johnston; Philipp H. Boersch-Supan; Chris B. Thaxter; Elizabeth M. Humphreys; Nina J. O’Hanlon; Gary D. Clewley; Ewan D. Weston; Judy Shamoun-Baranes; Aonghais S. C. P. Cook (Marine Biology, 2024)
Seabird collision risk is a key concern in relation to the environmental impacts associated with offshore wind farms (OWFs). Understanding how species respond both to the wind farm itself, and individual turbines within the wind farm, is key to enabling better quantification and management of collision risk. Collision risk is of particular concern for the black-legged kittiwake, Rissa tridactyla , where modelling predicts unsustainable population level impacts. In this study 20 adult breeding kittiwakes, were tracked with GPS from Whinnyfold, Scotland (57°23′07″N, 001°52′11″W) during the breeding season in 2021. An Avoidance-Attraction Index (AAI) was estimated at several bands within macro- and meso-scales (0–4 km from outer boundary and 0–400 m from turbines, respectively), and the Avoidance Rate (AR; used in environmental impact assessments) at macro-scale to estimate avoidance behaviour to three operational OWFs within their foraging range. One offshore wind farm and its buffer zone (0–4 km from outer boundary) was visited more frequently by the majority of tracked individuals (19/20 birds), despite being twice as far as the closest OWF (17.3 and 31.9 km respectively), whilst 10 or less individuals used the remaining two OWFs. At the most frequented OWF we found macro-scale attraction to the closest band (0–1 km) trending towards avoidance in the furthest band (3–4 km). At the meso-scale we found avoidance of areas below the rotor height range (RHR, a.k.a. rotor swept area/zone) up to 120 m from individual turbines, which decreased to 60 m when within the RHR. Our results indicate that kittiwakes may be slightly attracted to the area around OWFs or aggregate here due to displacement but avoid individual turbines. Increased productivity in the OWF area may potentially be drawing birds into the general area, with aversion to individual turbines being responsible for meso-scale observations.

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Intracerebral Administration of a Novel Self-Assembling Peptide Hydrogel Is Safe and Supports Cell Proliferation in Experimental Intracerebral Haemorrhage - Faye Bolan; Ben R. Dickie; James R. Cook; Josephine M. Thomas; Emmanuel Pinteaux; Stuart M. Allan; Alberto Saiani; Catherine B. Lawrence (Translational Stroke Research, 2024)
Intracerebral haemorrhage (ICH) is the deadliest form of stroke, but current treatment options are limited, meaning ICH survivors are often left with life-changing disabilities. The significant unmet clinical need and socioeconomic burden of ICH mean novel regenerative medicine approaches are gaining interest. To facilitate the regeneration of the ICH lesion, injectable biomimetic hydrogels are proposed as both scaffolds for endogenous repair and delivery platforms for pro-regenerative therapies. In this paper, the objective was to explore whether injection of a novel self-assembling peptide hydrogel (SAPH) Alpha2 was feasible, safe and could stimulate brain tissue regeneration, in a collagenase-induced ICH model in rats. Alpha2 was administered intracerebrally at 7 days post ICH and functional outcome measures, histological markers of damage and repair and RNA-sequencing were investigated for up to 8 weeks. The hydrogel Alpha2 was safe, well-tolerated and was retained in the lesion for several weeks, where it allowed infiltration of host cells. The hydrogel had a largely neutral effect on functional outcomes and expression of angiogenic and neurogenic markers but led to increased numbers of proliferating cells. RNAseq and pathway analysis showed that ICH altered genes related to inflammatory and phagocytic pathways, and these changes were also observed after administration of hydrogel. Overall, the results show that the novel hydrogel was safe when injected intracerebrally and had no negative effects on functional outcomes but increased cell proliferation. To elicit a regenerative effect, future studies could use a functionalised hydrogel or combine it with an adjunct therapy.

Influence of wind on kittiwake Rissa tridactyla flight and offshore wind turbine collision risk - Jacob G. Davies; Philipp H. Boersch-Supan; Gary D. Clewley; Elizabeth M. Humphreys; Nina J. O’Hanlon; Judy Shamoun-Baranes; Chris B. Thaxter; Ewan Weston; Aonghais S. C. P. Cook (Marine Biology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Wild native insects are efficient pollinators of mangoes in the Northern Territory of Australia - Gaurav Singh; James C. Makinson; Amy M. Gilpin; Robert N. Spooner-Hart; James M. Cook (Agriculture, Ecosystems & Environment, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Oral Bioavailability Enhancement of Poorly Soluble Drug by Amorphous Solid Dispersion Using Sucrose Acetate Isobutyrate - Eman M. Mohamed; Sathish Dharani; Tahir Khuroo; Mohammad T. H. Nutan; Phillip Cook; Rajendran Arunagiri; Mansoor A. Khan; Ziyaur Rahman (AAPS PharmSciTech, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Remission cytochrome spectroscopy reveals the mode of action of bedaquiline in living mycobacteria - Suzanna H. Harrison; Rowan C. Walters; Morwan M. Osman; Roger J. Springett; Gregory M. Cook; James N. Blaza (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

The value of seabird foraging ranges as a tool to investigate potential interactions with offshore wind farms - Ian D. Woodward; Chris B. Thaxter; Ellie Owen; Mark Bolton; Robin M. Ward; Aonghais S.C.P. Cook (Ocean & Coastal Management, 2024)

Connecting blue-green infrastructure elements to reduce combined sewer overflows - Giovan Battista Cavadini; Mayra Rodriguez; Lauren M. Cook (Journal of Environmental Management, 2024)

Exposure to endocrine disrupting chemicals including phthalates, phenols, and parabens in infancy: Associations with neurodevelopmental outcomes in the MARBLES study - Jennie Sotelo-Orozco; Antonia M. Calafat; Julianne Cook Botelho; Rebecca J. Schmidt; Irva Hertz-Picciotto; Deborah H. Bennett (International Journal of Hygiene and Environmental Health, 2024)

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Reframing wildlife disease management problems with decision analysis - Margaret C. McEachran; Johanna A. Harvey; Riley O. Mummah; Molly C. Bletz; Claire S. Teitelbaum; Elias Rosenblatt; F. Javiera Rudolph; Fernando Arce; Shenglai Yin; Diann J. Prosser; Brittany A. Mosher; Jennifer M. Mullinax; et al. (Conservation Biology, 2024)
Contemporary wildlife disease management is complex because managers need to respond to a wide range of stakeholders, multiple uncertainties, and difficult trade‐offs that characterize the interconnected challenges of today. Despite general acknowledgment of these complexities, managing wildlife disease tends to be framed as a scientific problem, in which the major challenge is lack of knowledge. The complex and multifactorial process of decision‐making is collapsed into a scientific endeavor to reduce uncertainty. As a result, contemporary decision‐making may be oversimplified, rely on simple heuristics, and fail to account for the broader legal, social, and economic context in which the decisions are made. Concurrently, scientific research on wildlife disease may be distant from this decision context, resulting in information that may not be directly relevant to the pertinent management questions. We propose reframing wildlife disease management challenges as decision problems and addressing them with decision analytical tools to divide the complex problems into more cognitively manageable elements. In particular, structured decision‐making has the potential to improve the quality, rigor, and transparency of decisions about wildlife disease in a variety of systems. Examples of management of severe acute respiratory syndrome coronavirus 2, white‐nose syndrome, avian influenza, and chytridiomycosis illustrate the most common impediments to decision‐making, including competing objectives, risks, prediction uncertainty, and limited resources.

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Per- and polyfluoroalkyl substances (PFAS), perceived stress, and depressive symptoms in a prospective cohort study of black women - Samantha Schildroth; Birgit Claus Henn; Anissa I. Vines; Ruth J. Geller; Sharonda M. Lovett; Chad M. Coleman; Traci N. Bethea; Julianne Cook Botelho; Antonia M. Calafat; Chad Milando; Donna D. Baird; Ganesa Wegienka; et al. (Science of The Total Environment, 2024)

An analysis of culture-based methods used for the detection and isolation of Salmonella spp., Escherichia coli, and Enterococcus spp. from surface water: A systematic review - Betty R. McConn; Autumn L. Kraft; Lisa M. Durso; Abasiofiok M. Ibekwe; Jonathan G. Frye; James E. Wells; Elizabeth M. Tobey; Stephanie Ritchie; Clinton F. Williams; Kimberly L. Cook; Manan Sharma (Science of The Total Environment, 2024)

Exploiting the Greenland volcanic ash repository to date caldera-forming eruptions and widespread isochrons during the Holocene - Siwan M. Davies; Paul G. Albert; Anna J. Bourne; Sara Owen; Anders Svensson; Matthew S.M. Bolton; Eliza Cook; Britta J.L. Jensen; Gwydion Jones; Vera V. Ponomareva; Takehiko Suzuki (Quaternary Science Reviews, 2024)

Influence of bubble size on perfluorooctanesulfonic acid degradation in a pilot scale non-thermal plasma treatment reactor - David Alam; Samiuela Lee; Jungmi Hong; David F. Fletcher; Xinying Liu; Dale McClure; David Cook; Johan le Nepvou de Carfort; Ulrich Krühne; P.J. Cullen; John M. Kavanagh (Chemical Engineering Journal, 2024)

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Search for source of invasive-range populations of a haplodiploid pest species reveals Wolbachia-driven mitochondrial selective sweep in native range - Alihan Katlav; Duong T. Nguyen; Asha Chhagan; Lisa Jamieson; Alexander R. Robertson; Jodie Cheesman; Stewart Learmonth; Piotr Trębicki; James M. Cook; Markus Riegler (Journal of Pest Science, 2024)

Enhancing spatiotemporal paleoclimate reconstructions of hydroclimate across the Mediterranean over the last millennium - Kevin J. Anchukaitis; Ramzi Touchan; David M. Meko; Dalila Kherchouche; Said Slimani; Fatih Sivrikaya; Rachid Ilmen; Ioannis Mitsopoulos; Jean Stephan; Jihad Attieh; Foued Hasnaoui; J. Julio Camarero; et al. (Climate Dynamics, 2024)

Plasma per- and polyfluoroalkyl substance mixtures during pregnancy and duration of breastfeeding in the New Hampshire birth cohort study - Megan E. Romano; Lisa G. Gallagher; George Price; Kathryn A. Crawford; Rachel Criswell; Emily Baker; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas (International Journal of Hygiene and Environmental Health, 2024)

What is known, unknown, and needed to be known about damage caused by wild pigs - Kurt C. VerCauteren; Kim M. Pepin; Seth M. Cook; Sophie McKee; Abigail Pagels; Keely J. Kohen; Ingrid A. Messer; Michael P. Glow; Nathan P. Snow (Biological Invasions, 2024)
Damage assessments provide evidence for initiating and evaluating management programs that protect natural resources and human livelihoods against invasive species. Wild pigs ( Sus scrofa ) cause extensive damage in their native and non-native ranges, but the extent of current damage and efficacy of management of the damage (i.e., population control of wild pigs, exclusion fencing, etc.) remains poorly described. We conducted a systematic review of physical damage caused by wild pigs to summarize what is known and identify knowledge gaps for damage assessment. Wild pig damage assessments have been overwhelmingly qualitative (84% of studies) and measured differently across studies, which prevents the determination of typical damage amounts to a particular resource and comparison across studies. Key priorities going forward are to standardize damage assessments quantitatively and measure population density (or index of such) of wild pigs concurrently with damage assessments to determine the relationship between damage and population levels. We provide a framework for inferring damage in new areas and assessing the benefits of management—to evaluate and optimize landscape-scale management programs. Overall, we recommend future studies strive for: (1) report the amount of damages in a standardized fashion (e.g., area damaged/area surveyed), (2) evaluate and report the amount of damage relative to the density of wild pigs, and (3) when reporting economic costs of damages incurred and management actions, describe the economic valuation method used along with the year of reference for the valuation. Capturing these elements are necessary steps to predict the benefits of management for an area with particular profile of resources and wild pig density, even in areas where damage assessments are not available. Meeting these criteria with allow for more generalizable results that can inform managers across the nearly global distribution of wild pigs.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Do baseline assumptions alter the efficacy of green stormwater infrastructure to reduce combined sewer overflows? - Mayra Rodriguez; Giovan Battista Cavadini; Lauren M. Cook (Water Research, 2024)

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

Identifying the influence of episodic events on groundwater recharge in semi-arid environments using environmental tracers - M. Chmielarski; S. Dogramaci; P.G. Cook; G. Skrzypek; A. Jackson; M. Nelson Tredwell; J.L. McCallum (Journal of Hydrology, 2024)

Moderate D/H ratios in methane ice on Eris and Makemake as evidence of hydrothermal or metamorphic processes in their interiors: Geochemical analysis - Christopher R. Glein; William M. Grundy; Jonathan I. Lunine; Ian Wong; Silvia Protopapa; Noemi Pinilla-Alonso; John A. Stansberry; Bryan J. Holler; Jason C. Cook; Ana Carolina Souza-Feliciano (Icarus, 2024)

Altered vacuole membrane protein 1 (VMP1) expression is associated with increased NLRP3 inflammasome activation and mitochondrial dysfunction - Stephanie R. Zack; Meghana Venkatesan; Roman Nikolaienko; Ben Cook; Ronald Melki; Aleksey V. Zima; Edward M. Campbell (Inflammation Research, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Spatial variation in spawning timing for multi-species Acropora assemblages in the Red Sea - Eslam O. Osman; David J. Suggett; Tamer M. Attalla; Marco Casartelli; Nathan Cook; Islam El-Sadek; Ahmed Gallab; Elizabeth A. Goergen; Neus Garcias-Bonet; Jessica S. Glanz; Pedro Henrique Pereira; Megan Ramirez-Sanchez; et al. (Frontiers in Marine Science, 2024)
Sexual reproduction is a crucial process for reef building coral populations to maximize genetic diversity and recover from large scale disturbances. Mass spawning events by Acropora species represent critical opportunities for populations to persist, and a process that is increasingly exploited to actively restore degraded reefs. However, the timing and predictive capacity of coral spawning throughout the broad thermal and environmental regime of the Red Sea – a region also undergoing significant development and active reef restoration – remains patchy. We, therefore, conducted three parallel reef surveys in the central Red Sea (Al-Fahal Reef, Thuwal - Saudi Arabia) and the eastern (Shushah Island - Saudi Arabia) and western (Hurghada – Egypt) coast of the northern Red Sea. Surveys assessed the gravidity of gonads, spawning timing, alignment with the lunar cycle of 21 Acropora spp. (total n= 572 colonies) around the full moons of April and May 2023. Consistent with past observations, synchronous spawning was observed for Acropora spp. in both the central and northern Red Sea during April and May, respectively. Interestingly, corals spawned on the full moon in both Shushah and Thuwal sites. In contrast, corals in Hurghada were independent of the lunar cycle and spawned 7-9 nights before the full moon in May. By integrating our 2023 observations with the historical spawning events in Hurghada and Thuwal (2002-2022), we found that the deviation of spawning timing from the full moon day was correlated with absolute Sea Surface Temperature (SST) (earlier spawning before the full moon day, lower SST) and warming rate (earlier spawning, more rapid warming) in 6-weeks prior to spawning. As such, temperature pattern is likely one of the primary factors governing gamete release, among other factors, that likely influence spawning day within the lunar month. These correlations between SST metrics and spawning timing suggest a potential framework to predict future Acropora spp. spawning dates. Our observations demonstrate the importance of parallel efforts across borders to collect critical data needed to inform management strategies aimed at conserving and restoring coral reefs in this ecologically diverse region.

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Variation in functional composition of reef fishes along a tropical‐to‐temperate gradient - Charlotte G. Clay; James D. Reimer; Brigitte Sommer; Katie M. Cook; Masaru Mizuyama; Masami Obuchi; Iori Kawamura; Hiroki Kise; Maria Beger (Journal of Biogeography, 2024)
Aims Transformation of species and functional composition on subtropical reefs are ongoing due to poleward range shifts of some tropical species, with largely unknown consequences to ecosystem functioning. Trait‐based approaches are powerful tools to quantify such changes. Here, we evaluated changes in the trait composition of coral‐associated fish assemblages along a tropical‐to‐temperate environmental gradient of ca. 1400 km in southern Japan with abundance‐weighted trait expression to assess how trait composition changes with increasing latitude. Location Ryukyu Islands and southern Pacific coast of Japan. Taxon Reef fish. Methods We tested for shifts in trait space and functional redundancy, based on five morphological, life history and behavioural traits: maximum length, pelagic larval duration, trophic level, substrate preference and reproductive mode. Our trait database was coded with two approaches, first, by attributing a single value to each trait per species, and second, by fuzzy coding that allows more than one value per trait and hence considers some intraspecific trait variation. Results We found a reduction in specialist habitat traits (coral substrate preference, nesters and herbivores) and an increase in generalist traits (predators) with increasing latitude, along with a contraction in trait space from tropical‐to‐temperate reefs. Functional redundancy declined with increasing latitude. These trends were closely linked with latitudinal gradients in temperature, along with changes in other environmental factors such as turbidity and photosynthetically active radiation. Main Conclusion Functional turnover and contractions are thus likely due to the marginal conditions for coral‐associated fishes at higher latitudes, favouring generalist species, whereas increased resources at lower latitudes favour high redundancy and niche partitioning. Accounting for intraspecific trait variation indicated the same trends but highlighted increased functional vulnerability across all sites. We show that trait complexity in coral‐associated fish communities decreases from tropical‐to‐temperate reefs, highlighting the reduced functional scope that comes with marginal environmental conditions.

Beyond a single temperature threshold: Applying a cumulative thermal stress framework to plant heat tolerance - Alicia M. Cook; Enrico L. Rezende; Katherina Petrou; Andy Leigh (Ecology Letters, 2024)
Most plant thermal tolerance studies focus on single critical thresholds, which limit the capacity to generalise across studies and predict heat stress under natural conditions. In animals and microbes, thermal tolerance landscapes describe the more realistic, cumulative effects of temperature. We tested this in plants by measuring the decline in leaf photosynthetic efficiency ( F V / F M ) following a combination of temperatures and exposure times and then modelled these physiological indices alongside recorded environmental temperatures. We demonstrate that a general relationship between stressful temperatures and exposure durations can be effectively employed to quantify and compare heat tolerance within and across plant species and over time. Importantly, we show how F V / F M curves translate to plants under natural conditions, suggesting that environmental temperatures often impair photosynthetic function. Our findings provide more robust descriptors of heat tolerance in plants and suggest that heat tolerance in disparate groups of organisms can be studied with a single predictive framework.

Behavioural responses of Sandwich terns following the construction of offshore wind farms - Chris B. Thaxter; Ros M. W. Green; Mark P. Collier; Rachel C. Taylor; Robert P. Middelveld; Emily S. Scragg; Lucy J. Wright; Aonghais S. C. P. Cook; Ruben C. Fijn (Marine Biology, 2024)

Transmission mode predicts coinfection patterns of insect‐specific viruses in field populations of the Queensland fruit fly - Stephen R. Sharpe; Jennifer L. Morrow; James M. Cook; Alexie Papanicolaou; Markus Riegler (Molecular Ecology, 2024)
Insect‐specific viruses (ISVs) can affect insect health and fitness, but can also interact with other insect‐associated microorganisms. Despite this, ISVs are often studied in isolation from each other, in laboratory populations. Consequently, their diversity, prevalence and associations with other viruses in field populations are less known, yet these parameters are important to understanding virus epidemiology. To help address this knowledge gap, we assessed the diversity, prevalence and coinfections of three ISVs (horizontally transmitted cripavirus, biparentally transmitted sigmavirus and maternally transmitted iflavirus) in 29 field populations of Queensland fruit fly, Australia's most significant horticultural pest, in the context of their different transmission modes. We detected new virus variant diversity. In contrast to the very high virus prevalence in laboratory populations, 46.8% of 293 field flies carried one virus and 4.8% had two viruses. Cripavirus and sigmavirus occurred in all regions, while iflavirus was restricted to subtropical and tropical regions. Cripavirus was most prevalent (37.5%), followed by sigmavirus (13.7%) and iflavirus (4.4%). Cripavirus coinfected some flies with either one of the two vertically transmitted viruses. However, sigmavirus did not coinfect individuals with iflavirus. Three different modelling approaches detected negative association patterns between sigmavirus and iflavirus, consistent with the absence of such coinfections in laboratory populations. This may be linked with their maternal transmission and the ineffective paternal transmission of sigmavirus. Furthermore, we found that, unlike sigmavirus and iflavirus, cripavirus load was higher in laboratory than field flies. Laboratory and mass‐rearing conditions may increase ISV prevalence and load due to increased transmission opportunities. We conclude that a combination of field and laboratory studies is needed to uncover ISV interactions and further our understanding of ISV epidemiology.

Substrate microorganisms can be an ideal tool for improving green roof sustainability - Hongqing Liu; Fanhua Kong; Haiwei Yin; Lauren M. Cook; Jing Huang; Itamar M. Lensky; Taotao Tan (Urban Forestry & Urban Greening, 2024)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Prospective cohort of pre- and post-diagnosis alcohol consumption and cigarette smoking on survival outcomes: an Alberta Endometrial Cancer Cohort Study - Renée L. Kokts-Porietis; Andria R. Morielli; Jessica McNeil; Jamie L. Benham; Kerry S. Courneya; Linda S. Cook; Christine M. Friedenreich (Cancer Causes & Control, 2024)

Relating social, ecological, and technological vulnerability to future flood exposure at two spatial scales in four U.S. cities - Jason Sauer; Arun Pallathadka; Idowu Ajibade; Marta Berbés-Blázquez; Heejun Chang; Elizabeth M. Cook; Nancy B. Grimm; David M. Iwaniec; Robert Lloyd; Gregory C. Post (Sustainable Cities and Society, 2023)

A comparison of methods to detect low levels of Salmonella enterica in surface waters to support antimicrobial resistance surveillance efforts performed in multiple laboratories - Autumn L. Kraft; Jim E. Wells; Jonathan G. Frye; Abasiofiok M. Ibekwe; Lisa M. Durso; Lari Hiott; Cheryl East; Betty R. McConn; Alison M. Franklin; Laura A. Boczek; Jay L. Garland; Claudine Kabera; et al. (Science of The Total Environment, 2023)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (II) optimizing acquisition configurations - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Omar Regaieg; Zhijun Zhen; Rongjun Qin; et al. (Remote Sensing of Environment, 2023)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (I) methods and comparisons with actual data - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Douglas C. Morton; Omar Regaieg; Zhijun Zhen; et al. (Remote Sensing of Environment, 2023)

Experimental investigations of Per- and Poly-fluoroalkyl substances (PFAS) degradation by non-thermal plasma in aqueous solutions - David Alam; Samiuela Lee; Jungmi Hong; David F. Fletcher; Dale McClure; David Cook; PJ Cullen; John M. Kavanagh (Journal of Environmental Chemical Engineering, 2023)

Psychometric Properties of Computerized Cognitive Tools and Standard Neuropsychological Tests Used to Assess Sport Concussion: A Systematic Review - Kristin Wilmoth; Benjamin L. Brett; Natalie A. Emmert; Carolyn M. Cook; Jeffrey Schaffert; Todd Caze; Thomas Kotsonis; Margaret Cusick; Gary Solomon; Jacob E. Resch; C. Munro Cullum; Lindsay D. Nelson; et al. (Neuropsychology Review, 2023)

Dietary reconstruction based on stable isotopes and stature at Torre de Palma, a Late Roman/Late Antiquity site in southern Portugal - Mark R. Schurr; Mary Lucas Powell; Della Collins Cook; Michael MacKinnon; Maia M. Langley (Archaeological and Anthropological Sciences, 2023)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Comparing PV-green and PV-cool roofs to diverse rooftop options using decision analysis - Bettina Maurer; Judit Lienert; Lauren M. Cook (Building and Environment, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Assessing resilience, equity, and sustainability of future visions across two urban scales - Marta Berbés-Blázquez; Elizabeth M. Cook; Nancy B. Grimm; David M. Iwaniec; Lelani M. Mannetti; Tischa A. Muñoz-Erickson; Darin Wahl (Sustainability Science, 2023)
Cities need to take swift action to deal with the impacts of extreme climate events. The co-production of positive visions offers the potential to not only imagine but also intervene in guiding change toward more desirable urban futures. While participatory visioning continues to be used as a tool for urban planning, there needs to be a way of comparing and evaluating future visions so that they can inform decision-making. Traditional tools for comparison tend to favor quantitative modeling, which is limited in its ability to capture nuances or normative elements of visions. In this paper, we offer a qualitative method to assess the resilience, equity, and sustainability of future urban visions and demonstrate its use by applying it to 11 visions from Phoenix, AZ. The visions were co-produced at two different governance scales: five visions were created at the village (or borough) scale, and six visions were created at the regional (or metropolitan) scale. Our analysis reveals different emphases in the mechanisms present in the visions to advance resilience, sustainability, and equity. In particular, we note that regional future visions align with a green sustainability agenda, whereas village visions focus on social issues and emphasize equity-driven approaches. The visions have implications for future trajectories, and the priorities that manifest at the two scales speak of the political nature of visioning and the need to explore how these processes may interact in complementary, synergistic, or antagonistic ways.

Heat stress survival and thermal tolerance of Australian stingless bees - Scott Nacko; Mark A. Hall; Rosalyn Gloag; Kate E. Lynch; Robert N. Spooner-Hart; James M. Cook; Markus Riegler (Journal of Thermal Biology, 2023)

Other Vegetables, Whole Fruit, Total Grains, and Sodium Intake Correlated to Vascular Responses from Butyrate - L. San Diego; H. Colleran; M. Cook; R. Claro Da Silva; T. Purdom; L. Toneygay (Journal of the Academy of Nutrition and Dietetics, 2023)

Commercially Available High-protein Nutrient Dense Ready-to-eat Meals Have Beneficial Effects on Postprandial Appetite Responses for up to 5 Hours in Adults with Overweight and Obesity - C. Cook; T. Blonquist; C. McCormick; M. Knowles (Journal of the Academy of Nutrition and Dietetics, 2023)

Development and Validation of an Abbreviated Child and Adult Food Security Scale for Use in Clinical and Research Settings in the United States - Ana Poblacion; Stephanie Ettinger de Cuba; Deborah A. Frank; Georgiana Esteves; Lindsey J. Rateau; Timothy C. Heeren; Sharon Coleman; Maureen M. Black; Diana B. Cutts; Félice Lê-Scherban; Eduardo R. Ochoa; Megan Sandel; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Survival trends (2008–2020) of three tree species in response to elephant impact, environmental variation, and stem wire-netting protection in an African savanna - Robin M. Cook; Ed T.F. Witkowski; Michelle D. Henley (Forest Ecology and Management, 2023)

How do dynamic and time-dependent indoor temperature patterns impact on the health of office based workers? – A scoping review - Amelie Reitmayer; Kelly R. Johnstone; Cassandra Madigan; Margaret M. Cook; Sava Arsenijevic (Building and Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Big advocacy, little recognition: the hidden work of Black patients in precision medicine - Lynette Hammond Gerido; Kenneth Resnicow; Elena M. Stoffel; Tiah Tomlin; Robert Cook-Deegan; Melissa Cline; Amy Coffin; Jill Holdren; Mary Anderlik Majumder; Zhe He (Journal of Community Genetics, 2023)
As cost-effective next-generation genome sequencing rapidly develops, calls for greater inclusion of Black people in genomic research, policy, and practice are necessary for effective translation of genomic science into precision population health and medicine. Employing a community-based participatory mixed methods research design, we developed a semi-structured survey that was disseminated to three cancer advocacy organizations. Of the 81 survey respondents 49 (60%) self-identified as Black, and 26 (32%) indicated a prior breast cancer diagnosis. Black participants’ expressed concerns about genetic testing were evenly distributed between concerns that could be addressed through genetic counseling (24%) and concerns about subsequent use of their genetic data (27%). Patient advocates contributed to contextualization of respondent concerns in terms of community experiences. Although genetic counseling services and policies governing genomic data use are not always accessible to many Black communities, advocates on our research team provided a bridge to discussion of the intersection between respondent concerns and the roles advocates play in filling gaps in access to genetic counseling and data governance. Concerns expressed by Black patients underscore a shared need among all patients for access to education, inclusion in research, and assurances regarding the use and handling of genetic data. Black cancer patients have joined in patient-led efforts to overcome systemic inequities in cancer care to improve their health outcomes through representation. Often their efforts are overshadowed by a relentless burden of continued health disparities. Future research should support their hidden work as a means to reduce barriers and improve representation in genomic databases.

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

X-ray computed tomography: A novel non-invasive approach for the detection of microplastics in sediments? - Megan M. Trusler; Craig J. Sturrock; Christopher H. Vane; Sarah Cook; Barry H. Lomax (Marine Pollution Bulletin, 2023)

Pulses of labile carbon cause transient decoupling of fermentation and respiration in permeable sediments - Philipp A. Nauer; Adam J. Kessler; Puspitaningsih Hall; Maria Elena Popa; Sophie ten Hietbrink; Tess Hutchinson; Wei Wen Wong; Karl Attard; Ronnie N. Glud; Chris Greening; Perran L. M. Cook (Limnology and Oceanography, 2023)
Dihydrogen (H 2 ) is an important intermediate in anaerobic microbial processes, and concentrations are tightly controlled by thermodynamic limits of consumption and production. However, recent studies reported unusual H 2 accumulation in permeable marine sediments under anoxic conditions, suggesting decoupling of fermentation and sulfate reduction, the dominant respiratory process in anoxic permeable marine sediments. Yet, the extent, prevalence and potential triggers for such H 2 accumulation and decoupling remain unknown. We surveyed H 2 concentrations in situ at different settings of permeable sand and found that H 2 accumulation was only observed during a coral spawning event on the Great Barrier Reef. A flume experiment with organic matter addition to the water column showed a rapid accumulation of hydrogen within the sediment. Laboratory experiments were used to explore the effect of oxygen exposure, physical disturbance and organic matter inputs on H 2 accumulation. Oxygen exposure had little effect on H 2 accumulation in permeable sediments suggesting both fermenters and sulfate reducers survive and rapidly resume activity after exposure to oxygen. Mild physical disturbance mimicking sediment resuspension had little effect on H 2 accumulation; however, vigorous shaking led to a transient accumulation of H 2 and release of dissolved organic carbon suggesting mechanical disturbance and cell destruction led to organic matter release and transient decoupling of fermenters and sulfate reducers. In summary, the highly dynamic nature of permeable sediments and its microbial community allows for rapid but transient decoupling of fermentation and respiration after a C pulse, leading to high H 2 levels in the sediment.

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

PCB126 exposure during pregnancy alters maternal and fetal gene expression - Cetewayo S. Rashid; Joshua D. Preston; Sara Y. Ngo Tenlep; Marissa K. Cook; Eric M. Blalock; Changcheng Zhou; Hollie I. Swanson; Kevin J. Pearson (Reproductive Toxicology, 2023)

Melissopalynological investigations of seasonal honey samples from the Greater Kruger National Park, Savanna biome of South Africa - Nikiwe Ndlovu; Frank H. Neumann; Michelle D. Henley; Robin M. Cook; Chevonne Reynolds (Palynology, 2023)

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Comparing relationships between urban heat exposure, ecological structure, and socio-economic patterns in Beijing and New York City - Jing Wang; Timon McPhearson; Weiqi Zhou; Elizabeth M. Cook; Pablo Herreros-Cantis; Jing Liu (Landscape and Urban Planning, 2023)

A prospective nested case-control study of serum concentrations of per- and polyfluoroalkyl substances and aggressive prostate cancer risk - Jongeun Rhee; Kathryn H. Barry; Wen-Yi Huang; Joshua N. Sampson; Jonathan N. Hofmann; Debra T. Silverman; Antonia M. Calafat; Julianne Cook Botelho; Kayoko Kato; Mark P. Purdue; Sonja I. Berndt (Environmental Research, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

Host insect specificity and interspecific competition drive parasitoid diversification in a plant–insect community - Ai‐Ying Wang; Yan‐Qiong Peng; James M. Cook; Da‐Rong Yang; Da‐Yong Zhang; Wan‐Jin Liao (Ecology, 2023)
Ecological interactions among plants, insect herbivores, and parasitoids are pervasive in nature and play important roles in community assembling, but the codiversification of tri‐trophic interactions has received less attention. Here we compare pairwise codiversification patterns between a set of 22 fig species, their herbivorous pollinating and galling wasps, and their parasitoids. The parasitoid phylogeny showed significant congruence and more cospeciation events with host insects phylogeny than with host plants. These results suggest that parasitoid phylogeny and speciation is more closely related to their host insects than to their host plants. The pollinating wasps hosted more parasitoid species than gallers and indicated a more intense interspecific competition among parasitoids associated with pollinators. Closer matching and fewer evolutionary host shifts were found between parasitoids and galler hosts than between parasitoids and pollinator hosts. These results suggest that interspecific competition among parasitoids, rather than resource availability of host wasps, is the main driver of the codiversification pattern in this community. Therefore, our study highlights the important role of interspecific competition among high trophic level insects in plant–insect tri‐trophic community assembling.

Effect of oviposition delay on early reproductive effort and offspring fitness in a thrips species - Alihan Katlav; James M. Cook; Markus Riegler (Animal Behaviour, 2023)

Late Cenozoic history and the role of Beringia in assembling a Holarctic cestode species complex - Kurt E. Galbreath; Arseny A. Makarikov; Kayce C. Bell; Stephen E. Greiman; Julie M. Allen; Genevieve M.S. Haas; Chenhong Li; Joseph A. Cook; Eric P. Hoberg (Molecular Phylogenetics and Evolution, 2023)

Microbial diversity in stingless bee gut is linked to host wing size and influenced by the environment - Hongwei Liu; Mark A. Hall; Laura E. Brettell; Juntao Wang; Megan Halcroft; Scott Nacko; Robert Spooner-Hart; James M. Cook; Markus Riegler; Brajesh K. Singh (Journal of Invertebrate Pathology, 2023)

Associations of urinary metabolite concentrations of phthalates and phthalate replacements with body composition from mid-childhood to early adolescence - Lisa B. Rokoff; Shravanthi M. Seshasayee; Jenny L. Carwile; Sheryl L. Rifas-Shiman; Julianne Cook Botelho; Catherine M. Gordon; Russ Hauser; Tamarra James-Todd; Jessica G. Young; Clifford J. Rosen; Antonia M. Calafat; Emily Oken; et al. (Environmental Research, 2023)

Adult-onset epilepsy and hippocampal pathology in a California sea lion (Zalophus californianus): A case study of suspected in utero exposure to domoic acid - David D.R. Krucik; Peter Cook; Michael Cathey; Jennifer M. Meegan; Forrest M. Gomez; William Van Bonn; Carolina Le-Bert (NeuroToxicology, 2023)

Antimicrobial susceptibility of Salmonella and Escherichia coli from equids sampled in the NAHMS 2015–16 equine study and association of management factors with resistance - Allison B. Kohnen; Alyson M. Wiedenheft; Josie L. Traub-Dargatz; Diana M. Short; Kim L. Cook; Kristina Lantz; Brenda Morningstar-Shaw; Jodie Plumblee Lawrence; Sandra House; Katherine L. Marshall; Sangeeta Rao (Preventive Veterinary Medicine, 2023)

Total thermal neutron cross section measurements of hydrogen dense polymers from 0.0005–20 eV - D. Fritz; Y. Danon; K. Ramic; C.W. Chapman; J.M. Brown; G. Arbanas; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; P. Brain; A. Ney; et al. (Annals of Nuclear Energy, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Assessing the Effects of Physical Barriers and Hypoxia on Red Drum Movement Patterns to Develop More Effective Management Strategies - Steven M. Baker; Eric A. Reyier; Bonnie J. Ahr; Geoffrey S. Cook (Fishes, 2023)
Human modification of coastal ecosystems often creates barriers to fish movement. Passive acoustic telemetry was used to quantify movement patterns and habitat use of red drums (Sciaenops ocellatus) within and around a complex of coastal impoundments, and explored how the presence of artificial structures (i.e., bollards and culverts) and a hypoxia-related mortality event impacted fish movement. Results indicated bollards impede the movement of individuals with head widths greater than the mean distance between bollards (~16.0 cm). Red drum home range area and daily distance traveled were related to water dissolved oxygen concentrations; as oxygen levels decreased, fish habitat use area decreased initially. However, continued exposure to hypoxic conditions increased fish cumulative daily distance traveled. When exposed to anoxic waters, fish daily distance traveled and rate of movement were greatly reduced. These findings suggest prolonged exposure to low dissolved oxygen in combination with artificial structures can reduce movement of red drum, increase risk of mortality, and decrease habitat connectivity. Constructing and maintaining (sediment and biofouling removal) larger culvert openings and/or using wider bollard spacing would improve water circulation in impoundments, increase habitat connectivity, and facilitate movement of large sportfish inhabiting Florida’s coastal waters.

Are we there yet? Management baselines and biodiversity indicators for the protection and restoration of subtidal bivalve shellfish habitats - Jose M. Fariñas-Franco; Robert L. Cook; Fiona R. Gell; Dan B. Harries; Natalie Hirst; Flora Kent; Rebecca MacPherson; Colin Moore; James M. Mair; Joanne S. Porter; William G. Sanderson (Science of The Total Environment, 2023)

An international wheat diversity panel reveals novel sources of genetic resistance to tan spot in Australia - Julian Taylor; Dorthe Jorgensen; Caroline S. Moffat; Ken J. Chalmers; Rebecca Fox; Grant J. Hollaway; Melissa J. Cook; Stephen M. Neate; Pao Theen See; Manisha Shankar (Theoretical and Applied Genetics, 2023)
Key message Novel sources of genetic resistance to tan spot in Australia have been discovered using one-step GWAS and genomic prediction models that accounts for additive and non-additive genetic variation. Abstract Tan spot is a foliar disease in wheat caused by the fungal pathogen Pyrenophora tritici-repentis (Ptr) and has been reported to generate up to 50% yield losses under favourable disease conditions. Although farming management practices are available to reduce disease, the most economically sustainable approach is establishing genetic resistance through plant breeding. To further understand the genetic basis for disease resistance, we conducted a phenotypic and genetic analysis study using an international diversity panel of 192 wheat lines from the Maize and Wheat Improvement Centre (CIMMYT), the International Centre for Agriculture in the Dry Areas (ICARDA) and Australian (AUS) wheat research programmes. The panel was evaluated using Australian Ptr isolates in 12 experiments conducted in three Australian locations over two years, with assessment for tan spot symptoms at various plant development stages. Phenotypic modelling indicated high heritability for nearly all tan spot traits with ICARDA lines displaying the greatest average resistance. We then conducted a one-step whole-genome analysis of each trait using a high-density SNP array, revealing a large number of highly significant QTL exhibiting a distinct lack of repeatability across the traits. To better summarise the genetic resistance of the lines, a one-step genomic prediction of each tan spot trait was conducted by combining the additive and non-additive predicted genetic effects of the lines. This revealed multiple CIMMYT lines with broad genetic resistance across the developmental stages of the plant which can be utilised in Australian wheat breeding programmes to improve tan spot disease resistance.

Total thermal neutron cross section measurements of yttrium hydride from 0.0005 - 3 eV - D. Fritz; Y. Danon; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; C.W. Chapman; G. Arbanas; J.M. Brown; K. Ramic; X. Hu; S. Singh; et al. (Annals of Nuclear Energy, 2023)

The Diversity of Eucheumatoid Seaweed Cultivars in the Philippines - Richard V. Dumilag; Bea A. Crisostomo; Zae-Zae A. Aguinaldo; Lourie Ann R. Hinaloc; Lawrence M. Liao; Hilly Ann Roa-Quiaoit; Floredel Dangan-Galon; Giuseppe C. Zuccarello; Marie-Laure Guillemin; Juliet Brodie; Elizabeth J. Cottier-Cook; Michael Y. Roleda (Reviews in Fisheries Science & Aquaculture, 2023)

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

Analysis of Charon’s spectrum at 2.21- μ m from New Horizons/LEISA and Earth-based observations - Jason C. Cook; Silvia Protopapa; Cristina M. Dalle Ore; Dale P. Cruikshank; William M. Grundy; Carey M. Lisse; Bernard Schmitt; Anne Verbiscer; Kelsi N. Singer; John Spencer; S. Alan Stern; Harold A. Weaver (Icarus, 2023)

Induced Pluripotent Stem Cell-Derived Corneal Cells: Current Status and Application - Nasif Mahmood; Taylor Cook Suh; Kiran M. Ali; Eelya Sefat; Ummay Mowshome Jahan; Yihan Huang; Brian C. Gilger; Jessica M. Gluck (Stem Cell Reviews and Reports, 2022)

Preclinical efficacy and safety of novel SNAT against SARS-CoV-2 using a hamster model - Lok R. Pokhrel; Frank Williams; Paul P. Cook; Dorcas O’Rourke; Gina Murray; Shaw M. Akula (Drug Delivery and Translational Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The contribution of respiratory and hearing protection use to psychological distress in the workplace: a scoping review - Richard Leung; Margaret M. Cook; Mike F. Capra; Kelly R. Johnstone (International Archives of Occupational and Environmental Health, 2022)
Objective Workers from various industries use personal protective equipment (PPE) including masks, respirators, and hearing protection to reduce their exposures to workplace hazards. Many studies have evaluated the physiological impacts of PPE use, but few have assessed the psychological impacts. The aim of the present study was to carry out a scoping review to compile existing evidence and determine the extent of knowledge on workplace mask, respirator or hearing protection use as a psychosocial hazard (stressor) that could result in a stress response and potentially lead to psychological injury. Methods The scoping review followed recognized methods and was conducted using Ovid Emcare, PubMed, Sage Journals, ScienceDirect, Scopus, SpringerLink, Google Scholar and preprint databases (OSF Preprints and medRxiv). Articles on the stressors associated with the use of masks, respirators, and hearing protection were included. The extracted data included author(s) name, year of publication, title of article, study design, population data, stressors assessed, and key findings. Results We retrieved 650 articles after removal of duplicates, of which 26 were deemed eligible for inclusion for review. Identified factors associated with PPE use that could potentially create a stress response were identified: communication impacts, physical impacts, psychological illness symptoms, cognitive impacts, and perceived PPE-related impacts. Evidence for respirators suggest that there may be psychological injury associated with their use. However, hearing protection appears to have a protective effect in reducing psychological symptoms such as anxiety, depression, and aggression. Conclusions Mask or respirator use may lead to an increase in work-related stress. Whereas hearing protection may have protective effects against psychological symptoms and improves speech intelligibility. More research is needed to better understand potential psychosocial impacts of mask, respirator and/or hearing protection use.

Inconsistent results from trait-based analyses of moth trends point to complex drivers of change - George M. Tordoff; Emily B. Dennis; Richard Fox; Patrick M. Cook; Tony M. Davis; Dan Blumgart; Nigel A. D. Bourn (Biodiversity and Conservation, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Prostate cancer addiction to oxidative stress defines sensitivity to anti-tumor neutrophils - Diane L. Costanzo-Garvey; Adam J. Case; Gabrielle F. Watson; Massar Alsamraae; Arpita Chatterjee; Rebecca E. Oberley-Deegan; Samikshan Dutta; Maher Y. Abdalla; Tammy Kielian; Merry L. Lindsey; Leah M. Cook (Clinical & Experimental Metastasis, 2022)
Bone metastatic prostate cancer (BM-PCa) remains one of the most difficult cancers to treat due to the complex interactions of cancer and stromal cells. We previously showed that bone marrow neutrophils elicit an anti-tumor immune response against BM-PCa. Further, we demonstrated that BM-PCa induces neutrophil oxidative burst, which has previously been identified to promote primary tumor growth of other cancers, and a goal of this study was to define the importance of neutrophil oxidative burst in BM-PCa. To do this, we first examined the impact of depletion of reactive oxygen species (ROS), via systemic deletion of the main source of ROS in phagocytes, NADPH oxidase (Nox)2, which we found to suppress prostate tumor growth in bone. Further, using pharmacologic ROS inhibitors and Nox2-null neutrophils, we found that ROS depletion specifically suppresses growth of androgen-insensitive prostate cancer cells. Upon closer examination using bulk RNA sequencing analysis, we identified that metastatic prostate cancer induces neutrophil transcriptomic changes that activates pathways associated with response to oxidative stress. In tandem, prostate cancer cells resist neutrophil anti-tumor response via extracellular (i.e., regulation of neutrophils) and intracellular alterations of glutathione synthesis, the most potent cellular antioxidant. These findings demonstrate that BM-PCa thrive under oxidative stress conditions and such that regulation of ROS and glutathione programming could be leveraged for targeting of BM-PCa progression.

Recovery of denitrification and dissimilatory nitrate reduction to ammonium following reoxygenation of sediments from a periodically hypoxic temperate lagoon - Keryn L. Roberts; Wei Wen Wong; Jeff Shimeta; Adam J. Kessler; Perran L. M. Cook (Limnology and Oceanography, 2022)
Eutrophication and stratification events have increased the incidences of hypoxia and anoxia in coastal environments. The depletion of oxygen in these environments can lead to a shift in biogeochemical processes such as denitrification and dissimilatory nitrate reduction to ammonium (DNRA). The balance between denitrification and DNRA is critical because denitrification leads to a loss of bioavailable nitrogen and DNRA maintains it within the system. This study examined the effects of reoxygenation on denitrification and DNRA in sediments collected from a periodically hypoxic system (Gippsland Lakes, Australia) and subjected to experimental hypoxia using a modified 15 N‐isotope pairing technique. For freshly collected sediments, the ratio of denitrification : DNRA was generally 1. Profiles of 15 N‐N 2 and accumulation in these experiments showed denitrification and DNRA generally only took place in the surface ~ 2 cm of sediment. Prolonged experiments with reoxygenated sediments showed a decrease in the denitrification : DNRA to

Review of adaptations of U.S. Commercial Fisheries in response to the COVID ‐19 pandemic using the Resist ‐ Accept ‐ Direct (RAD) framework - Sarah Lindley Smith; Samantha Cook; Abigail Golden; Mia Aiko Iwane; Danika Kleiber; Kirsten M. Leong; Anthony Mastitski; Laurie Richmond; Marysia Szymkowiak; Sarah Wise (Fisheries Management and Ecology, 2022)
The COVID‐19 pandemic transformed social and economic systems globally, including fisheries systems. Decreases in seafood demand, supply chain disruptions, and public safety regulations required numerous adaptations to maintain the livelihoods and social resilience of fishing communities. Surveys, interviews, and focus groups were undertaken to assess impacts from and adaptive responses to the pandemic in commercial fisheries in five U.S. regions: the Northeast, California, Alaska, the U.S. Caribbean, and the Pacific Islands. Fishery adaptation strategies were categorized using the Resist–Accept–Direct (RAD) framework, a novel application to understand social transformation in a social‐ecological system in response to a disturbance. A number of innovations emerged, or were facilitated, that could improve the fisheries' resilience to future disruptions. Fishers with diversified options and strategic flexibility generally fared better, i.e., had fewer disruptions to their livelihoods. Using the RAD framework to identify adaptation strategies from fishery system actors highlights opportunities for improving resilience of fisheries social‐ecological systems to future stressors.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Traits data for the butterflies and macro‐moths of Great Britain and Ireland - Patrick M. Cook; George M. Tordoff; Tony M. Davis; Mark S. Parsons; Emily B. Dennis; Richard Fox; Marc S. Botham; Nigel A. D. Bourn (Ecology, 2022)
Butterflies and moths, collectively Lepidoptera, are integral components of ecosystems, providing key services such as pollination and a prey resource for vertebrate and invertebrate predators. Lepidoptera are a relatively well studied group of invertebrates. In Great Britain and Ireland numerous citizen science projects provide data on changes in distribution and abundance. The availability of high‐quality monitoring and recording data, combined with the rapid response of Lepidoptera to environmental change, makes them ideal candidates for traits‐based ecological studies. Recently, there has been an increase in the number of studies documenting traits‐based responses of Lepidoptera, highlighting the demand for a standardized and referenced traits database. There is a wide range of primary and secondary literature sources available regarding the ecology of British and Irish Lepidoptera to support such studies. Currently these sources have not been collated into one central repository that would facilitate and enhance future research. Here, we present a comprehensive traits database for the butterflies and macro‐moths of Great Britain and Ireland. The database covers 968 species in 21 families. Ecological traits fall into four main categories: life cycle ecology and phenology, host plant specificity and characteristics, breeding habitat, and morphological characteristics. The database also contains data regarding species distribution, conservation status, and temporal trends for abundance and occupancy. This database can be used for a wide array of purposes including further fundamental research on species and community responses to environmental change, conservation and management studies, and evolutionary biology. There are no copyright restrictions, and this paper must be cited if data are used in publications.

Local adaptation and spatiotemporal patterns of genetic diversity revealed by repeated sampling of Caenorhabditis elegans across the Hawaiian Islands - Timothy A. Crombie; Paul Battlay; Robyn E. Tanny; Kathryn S. Evans; Claire M. Buchanan; Daniel E. Cook; Clayton M. Dilks; Loraina A. Stinson; Stefan Zdraljevic; Gaotian Zhang; Nicole M. Roberto; Daehan Lee; et al. (Molecular Ecology, 2022)
The nematode Caenorhabditis elegans is among the most widely studied organisms, but relatively little is known about its natural ecology. Genetic diversity is low across much of the globe but high in the Hawaiian Islands and across the Pacific Rim. To characterize the niche and genetic diversity of C. elegans on the Hawaiian Islands and to explore how genetic diversity might be influenced by local adaptation, we repeatedly sampled nematodes over a three‐year period, measured various environmental parameters at each sampling site, and whole‐genome sequenced the C. elegans isolates that we identified. We found that the typical Hawaiian C. elegans niche comprises moderately moist native forests at high elevations (500–1,500 m) where ambient air temperatures are cool (15–20°C). Compared to other Caenorhabditis species found on the Hawaiian Islands ( e.g ., Caenorhabditis briggsae and Caenorhabditis tropicalis ), we found that C. elegans were enriched in native habitats. We measured levels of genetic diversity and differentiation among Hawaiian C. elegans and found evidence of seven genetically distinct groups distributed across the islands. Then, we scanned these genomes for signatures of local adaptation and identified 18 distinct regions that overlap with hyper‐divergent regions, which may be maintained by balancing selection and are enriched for genes related to environmental sensing, xenobiotic detoxification, and pathogen resistance. These results provide strong evidence of local adaptation among Hawaiian C. elegans and contribute to our understanding of the forces that shape genetic diversity on the most remote volcanic archipelago in the world.

The Alberta moving beyond breast cancer (AMBER) cohort study: baseline description of the full cohort - Christine M. Friedenreich; Jeff K. Vallance; Margaret L. McNeely; S. Nicole Culos-Reed; Charles E. Matthews; Gordon J. Bell; John R. Mackey; Karen A. Kopciuk; Leanne Dickau; Qinggang Wang; Diane Cook; Stephanie Wharton; et al. (Cancer Causes & Control, 2022)
Purpose The Alberta Moving Beyond B r east Cancer (AMBER) Study is an ongoing prospective cohort study investigating how direct measures of physical activity (PA), sedentary behavior (SB), and health-related fitness (HRF) are associated with survival after breast cancer. Methods Women in Alberta with newly diagnosed stage I (≥ T1c) to IIIc breast cancer were recruited between 2012 and 2019. Baseline assessments were completed within 90 days of surgery. Measurements included accelerometers to measure PA and SB; a graded treadmill test with gas exchange analysis to measure cardiorespiratory fitness (VO 2peak ); upper and lower body muscular strength and endurance; dual-X-ray absorptiometry to measure body composition; and questionnaires to measure self-reported PA and SB. Results At baseline, the 1528 participants’ mean age was 56 ± 11 years, 59% were post-menopausal, 62% had overweight/obesity, and 55% were diagnosed with stage II or III disease. Based on device measurements, study participants spent 8.9 ± 1.7 h/day sedentary, 4.4 ± 1.2 h/day in light-intensity activity, 0.9 ± 0.5 h/day in moderate-intensity activity, and 0.2 ± 0.2 h/day in vigorous-intensity activity. For those participants who reached VO 2peak , the average aerobic fitness level was 26.6 ± 6 ml/kg/min. Average body fat was 43 ± 7.1%. Conclusion We have established a unique cohort of breast cancer survivors with a wealth of data on PA, SB, and HRF obtained through both direct and self-reported measurements. Study participants are being followed for at least ten years to assess all outcomes after breast cancer. These data will inform clinical and public health guidelines on PA, SB, and HRF for improving breast cancer outcomes.

Prioritization and thresholds for managing biological invasions in urban ecosystems - L. J. Potgieter; M. F. J. Aronson; A. J. Brandt; C. N. Cook; M. Gaertner; N. E. Mandrak; D. M. Richardson; N. Shrestha; M. W. Cadotte (Urban Ecosystems, 2022)

Development and Implementation of a Biometrics Device Design Project in an Introductory BME Course to Support Student Wellness - Isabel Miller; Sara Lamer; Aidan Brougham-Cook; Karin J. Jensen; Holly M. Golecki (Biomedical Engineering Education, 2022)

Effects of methylphenidate on reinforcement learning depend on working memory capacity - Mojtaba Rostami Kandroodi; Jennifer L. Cook; Jennifer C. Swart; Monja I. Froböse; Dirk E. M. Geurts; Abdol-Hossein Vahabie; Majid Nili Ahmadabadi; Roshan Cools; Hanneke E. M. den Ouden (Psychopharmacology, 2021)
Rationale Brain catecholamines have long been implicated in reinforcement learning, exemplified by catecholamine drug and genetic effects on probabilistic reversal learning. However, the mechanisms underlying such effects are unclear. Objectives and methods Here we investigated effects of an acute catecholamine challenge with methylphenidate (20 mg, oral) on a novel probabilistic reversal learning paradigm in a within-subject, double-blind randomised design. The paradigm was designed to disentangle effects on punishment avoidance from effects on reward perseveration. Given the known large individual variability in methylphenidate’s effects, we stratified our effects by working memory capacity and trait impulsivity, putatively modulating the effects of methylphenidate, in a large sample ( n = 102) of healthy volunteers. Results Contrary to our prediction, methylphenidate did not alter performance in the reversal phase of the task. Our key finding is that methylphenidate altered learning of choice-outcome contingencies in a manner that depended on individual variability in working memory span. Specifically, methylphenidate improved performance by adaptively reducing the effective learning rate in participants with higher working memory capacity. Conclusions This finding emphasises the important role of working memory in reinforcement learning, as reported in influential recent computational modelling and behavioural work, and highlights the dependence of this interplay on catecholaminergic function.

Viral-Like Particles Are Associated With Endosymbiont Pathology in Florida Corals Affected by Stony Coral Tissue Loss Disease - Thierry M. Work; Tina M. Weatherby; Jan H. Landsberg; Yasunari Kiryu; Samantha M. Cook; Esther C. Peters (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) was first documented in 2014 near the Port of Miami, Florida, and has since spread north and south along Florida’s Coral Reef, killing large numbers of more than 20 species of coral and leading to the functional extinction of at least one species, Dendrogyra cylindrus . SCTLD is assumed to be caused by bacteria based on presence of different molecular assemblages of bacteria in lesioned compared to apparently healthy tissues, its apparent spread among colonies, and cessation of spread of lesions in individual colonies treated with antibiotics. However, light microscopic examination of tissues of corals affected with SCTLD has not shown bacteria associated with tissue death. Rather, microscopy shows dead and dying coral cells and symbiotic dinoflagellates (endosymbionts) indicating a breakdown of host cell and endosymbiont symbiosis. It is unclear whether host cells die first leading to death of endosymbionts or vice versa. Based on microscopy, hypotheses as to possible causes of SCTLD include infectious agents not visible at the light microscopy level or toxicosis, perhaps originating from endosymbionts. To clarify this, we examined corals affected with SCTLD and apparently healthy corals using transmission electron microscopy. Endosymbionts in SCTLD-affected and apparently healthy corals consistently had varying degrees of pathology associated with elongated particles compatible in morphology with filamentous positive single-stranded RNA viruses of plants termed anisometric viral-like particles (AVLP). There was apparent progression from early to late replication of AVLP in the cytoplasm of endosymbionts adjacent to or at times within chloroplasts, with morphologic changes in chloroplasts consistent with those seen in plant cells infected by viruses. Coral host cell pathology appeared limited to massive proliferation and lysis of mucus cells. Based on these findings, we hypothesize that SCTLD is a viral disease of endosymbionts leading to coral host death. Efforts to confirm the presence of a virus associated with SCTLD through other means would be appropriate. These include showing the presence of a virus through molecular assays such as deep sequencing, attempts to grow this virus in the laboratory through culture of endosymbionts, localization of virus in tissue sections using immunohistochemistry or in situ hybridization, and experimental infection of known-virus-negative corals to replicate disease at the gross and microscopic level.

Nesting biology and social organisation of the allodapine bee Exoneura angophorae (Hymenoptera: Apidae): montane environmental constraints yield biased sex allocation yet phenology is unhindered - O. M. Bernauer; J. M. Cook; S. M. Tierney (Insectes Sociaux, 2021)

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

Trace Element Patterns in Otoliths: The Role of Biomineralization - Karin Hüssy; Karin E. Limburg; Hélène de Pontual; Oliver R. B. Thomas; Philip K. Cook; Yvette Heimbrand; Martina Blass; Anna M. Sturrock (Reviews in Fisheries Science & Aquaculture, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide - M. Peacock; J. Audet; D. Bastviken; S. Cook; C. D. Evans; A. Grinham; M. A. Holgerson; L. Högbom; A. E. Pickard; P. Zieliński; M. N. Futter (Global Change Biology, 2021)
Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH 4 ) and carbon dioxide (CO 2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH 4 m −2 year −1 and −36–4421 g CO 2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH 4 emissions were converted to CO 2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Detection of Hepatitis A Virus in Strawberries Implicated in an Outbreak in the USA in 1997 - N. Cook; L. Vickers-Smith; M. D’Agostino (Food and Environmental Virology, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Quantifying the Effects of Aging on Morphological and Cellular Properties of Human Female Pelvic Floor Muscles - Mary Rieger; Pamela Duran; Mark Cook; Simon Schenk; Manali Shah; Marni Jacobs; Karen Christman; Deborah M. Kado; Marianna Alperin (Annals of Biomedical Engineering, 2021)

Synergistic antihyperalgesic and antinociceptive effects of morphine and methyl 8-ethynyl-6-(pyridin-2-yl)-4H-benzo[f]imidazo[1,5-a][1,4]diazepine-3-carboxylate (MP-III-024): a positive allosteric modulator at α2GABAA and α3GABAA receptors - Mohammad A. Rahman; Thomas M. Keck; Michael M. Poe; Dishary Sharmin; James M. Cook; Bradford D. Fischer (Psychopharmacology, 2021)

Emerging roles for myeloid immune cells in bone metastasis - Massar Alsamraae; Leah M. Cook (Cancer and Metastasis Reviews, 2021)

The Influence of the Toxin-Producing Dinoflagellate, Alexandrium catenella (1119/27), on the Survival and Reproduction of the Marine Copepod, Acartia tonsa, During Prolonged Exposure - Ali H. Abdulhussain; Kathryn B. Cook; Andrew D. Turner; Adam M. Lewis; Thomas S. Bibby; Daniel J. Mayor (Frontiers in Marine Science, 2021)
Copepods can feed on, and may regulate, the blooms of harmful algae (HA), and may also facilitate dinoflagellate blooms by inducing toxin production and through selective grazing. However, exposure to HA may also cause mortality and reproductive impairment in copepods, with detrimental effects at the population-scale. Here we present the toxin profile of the dinoflagellate, Alexandrium catenella (formerly Alexandrium tamarense ), and examine how it affects the survival and reproduction of the cosmopolitan marine copepod, Acartia tonsa . Healthy adult copepods were exposed to mono-specific diets of toxic and non-toxic strains of A. catenella (1119/27 and 1119/19, respectively) and non-toxic Rhodomonas sp. for 10 days alongside unfed controls to examine how their survival was influenced by likely HA bloom conditions. Additional 2-day experiments examined how their egg production rate and hatching success were affected by food deprivation, toxic A. catenella , a non-toxic alternative and a mixture of toxic and non-toxic prey, at high and low concentrations. Survival of A. tonsa declined over the 10-day experiment in all treatments but was not significantly lower in the toxic A. catenella treatment; mortality was only significantly enhanced in the unfed animals, which showed 100% mortality after 9 days. Egg production rates and hatching success from females in the unfed and toxic A. catenella treatments were all significantly lower than values observed in females fed Rhodomonas sp. or non-toxic A. catenella . Animals offered 1,000 μg C L –1 of Rhodomonas sp. and a 50:50 mixture of toxic A. catenella and Rhodomonas sp. produced significantly more eggs than animals fed toxic A. catenella alone. These results were not apparent at prey concentrations of 100 μg C L –1 . The percentages of eggs to successfully hatch from females offered mono-specific diets of toxic A. catenella were always close to zero. Collectively, our results indicate that adult female A. tonsa can acquire sufficient energy from toxic A. catenella to survive, but suffer reproductive impairment when feeding on this prey alone.

Coating characterization by hyperspectroscopy and predictive dissolution models of tablets coated with blends of cellulose acetate and cellulose acetate phthalate - Tahir Khuroo; Eman M. Mohamed; Sathish Dharani; Hamideh Afrooz; Sogra F. Barakh Ali; Phillip Cook; Mansoor A. Khan; Ziyaur Rahman (AAPS PharmSciTech, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

Associations between daily aspirin use and cancer risk across strata of major cancer risk factors in two large U.S. cohorts - Lauren M. Hurwitz; Kara A. Michels; Michael B. Cook; Ruth M. Pfeiffer; Britton Trabert (Cancer Causes & Control, 2021)

Early olfactory, but not gustatory processing, is affected by the selection of heritable cognitive phenotypes in honey bee - Meghan M. Bennett; Chelsea N. Cook; Brian H. Smith; Hong Lei (Journal of Comparative Physiology A, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Biogeochemical attenuation of nitrate in a sandy subterranean estuary: Insights from two stable isotope approaches - Wei Wen Wong; Andrew Applegate; Seng Chee Poh; Perran L. M. Cook (Limnology and Oceanography, 2020)
The role of permeable sediments and subterranean estuaries as coastal nutrient filters is a question of key interest, particularly in areas with high nitrogen loadings. Here, we evaluated the effectiveness of a sandy subterranean estuary in cycling and removing nitrate using stable isotopes of N and O at natural (δ 15 N‐NO 3 − and δ 18 O‐NO 3 − ) and enriched levels ( 15 N). Isotopes were used in conjunction with flow through reactors under anoxic conditions to quantify (1) the overall enrichment factor ( 15 ε) of nitrate removal processes which was then applied to estimate the in situ percentage of nitrate removal within the subterranean estuary and (2) the potential rates of denitrification, dissimilatory nitrate reduction to ammonium, and anammox. We found that 15 ε varied between −24 and −34‰ and were positively correlated with nitrate concentrations and the percentage of organic carbon added to the sediments. Using these 15 ε values in a Rayleigh distillation model resulted in an estimated average of 34% ± 14% nitrate removal within the subterranean estuary, less than half of the percentage estimated using the nitrate‐salinity mixing model (66% ± 28%). Denitrification was the most dominant nitrate removal pathway within the subterranean estuary with potential rates among the highest denitrification rates reported for both permeable and cohesive sediments. The contribution of dissimilatory nitrate reduction to ammonium showed significant seasonal variation while the rates of anammox were consistent throughout the study. We suggest that the spatial shift of the subterranean estuary is the most likely explanation for the seasonal differences in the rates of denitrification and dissimilatory nitrate reduction to ammonium.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

Genomic analysis of Caldalkalibacillus thermarum TA2.A1 reveals aerobic alkaliphilic metabolism and evolutionary hallmarks linking alkaliphilic bacteria and plant life - Samuel I. de Jong; Marcel A. van den Broek; Alexander Y. Merkel; Pilar de la Torre Cortes; Falk Kalamorz; Gregory M. Cook; Mark C. M. van Loosdrecht; Duncan G. G. McMillan (Extremophiles, 2020)
The aerobic thermoalkaliphile Caldalkalibacillus thermarum strain TA2.A1 is a member of a separate order of alkaliphilic bacteria closely related to the Bacillales order. Efforts to relate the genomic information of this evolutionary ancient organism to environmental adaptation have been thwarted by the inability to construct a complete genome. The existing draft genome is highly fragmented due to repetitive regions, and gaps between and over repetitive regions were unbridgeable. To address this, Oxford Nanopore Technology’s MinION allowed us to span these repeats through long reads, with over 6000-fold coverage. This resulted in a single 3.34 Mb circular chromosome. The profile of transporters and central metabolism gives insight into why the organism prefers glutamate over sucrose as carbon source. We propose that the deamination of glutamate allows alkalization of the immediate environment, an excellent example of how an extremophile modulates environmental conditions to suit its own requirements. Curiously, plant-like hallmark electron transfer enzymes and transporters are found throughout the genome, such as a cytochrome b 6 c 1 complex and a CO 2 -concentrating transporter. In addition, multiple self-splicing group II intron-encoded proteins closely aligning to those of a telomerase reverse transcriptase in Arabidopsis thaliana were revealed. Collectively, these features suggest an evolutionary relationship to plant life.

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

S-EQUOL: a neuroprotective therapeutic for chronic neurocognitive impairments in pediatric HIV - Kristen A. McLaurin; Hailong Li; Anna K. Cook; Rosemarie M. Booze; Charles F. Mactutus (Journal of NeuroVirology, 2020)

Low‐coverage genomic data resolve the population divergence and gene flow history of an Australian rain forest fig wasp - Lisa Cooper; Lynsey Bunnefeld; Jack Hearn; James M. Cook; Konrad Lohse; Graham N. Stone (Molecular Ecology, 2020)
Population divergence and gene flow are key processes in evolution and ecology. Model‐based analysis of genome‐wide data sets allows discrimination between alternative scenarios for these processes even in nonmodel taxa. We used two complementary approaches (one based on the blockwise site frequency spectrum [bSFS], the second on the pairwise sequentially Markovian coalescent [PSMC]) to infer the divergence history of a fig wasp, Pleistodontes nigriventris . Pleistodontes nigriventris and its fig tree mutualist Ficus watkinsiana are restricted to rain forest patches along the eastern coast of Australia and are separated into The Northern population is to the north of the Southern populations by two dry forest corridors (the Burdekin and St. Lawrence Gaps). We generated whole genome sequence data for two haploid males per population and used the bSFS approach to infer the timing of divergence between northern and southern populations of P. nigriventris , and to discriminate between alternative isolation with migration (IM) and instantaneous admixture (ADM) models of postdivergence gene flow. Pleistodontes nigriventris has low genetic diversity (π = 0.0008), to our knowledge one of the lowest estimates reported for a sexually reproducing arthropod. We find strongest support for an ADM model in which the two populations diverged ca . 196 kya in the late Pleistocene, with almost 25% of northern lineages introduced from the south during an admixture event ca. 57 kya. This divergence history is highly concordant with individual population demographies inferred from each pair of haploid males using PSMC. Our analysis illustrates the inferences possible with genome‐level data for small population samples of tiny, nonmodel organisms and adds to a growing body of knowledge on the population structure of Australian rain forest taxa.

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry - Cicilia S. B. Kambey; Iona Campbell; Calvyn F. A. Sondak; Adibi R. M. Nor; Phaik E. Lim; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma ; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks including legislation, regulatory tools, and national standards was conducted. Biosecurity themes and risks were used to evaluate current national biosecurity content. The results identified major challenges faced by the industry in order to implement biosecurity policies in practice. Barriers to implementation included unspecific reference to the seaweed aquaculture sector, limited variety of approaches to biosecurity, limited use of up-to-date scientific evidence, insufficient guidance for the use of precaution and insufficient inclusion of specific biosecurity hazards. In general, although national regulations are currently under revision, current policies indicate a lack of clarity where biosecurity is included. Six recommendations are suggested to incorporate proactive biosecurity actions into current frameworks, with the aim of improving the health and sustainability of the seaweed aquaculture sector in Indonesia.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Tackling the tide: A rapid assessment protocol to detect terrestrial vertebrates in mangrove forests - Stefanie M. Rog; Rohan H. Clarke; Ernest Minnema; Carly N. Cook (Biodiversity and Conservation, 2020)

Simulating alternative sustainable water futures - D. A. Sampson; E. M. Cook; M. J. Davidson; N. B. Grimm; D. M. Iwaniec (Sustainability Science, 2020)

Development of Abuse-Deterrent Formulations Using Sucrose Acetate Isobutyrate - Sogra F. Barakh Ali; Sathish Dharani; Hamideh Afrooz; Eman M. Mohamed; Phillip Cook; Mansoor A. Khan; Ziyaur Rahman (AAPS PharmSciTech, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Development of an instrumented thoracoscopic surgical trainer for objective evaluation of esophageal atresia/tracheoesophageal fistula repair - Ashton A. Moorhead; David Nair; Chris Morison; Nicholas J. Cook; Spencer W. Beasley; Jonathan M. Wells (Medical & Biological Engineering & Computing, 2020)

“Always do your best!”—The relationship between food addiction, exercise dependence, and perfectionism in amateur athletes - C. Hauck; M. Schipfer; T. Ellrott; B. Cook (German Journal of Exercise and Sport Research, 2020)

The effect of modeling choices on updating intensity-duration-frequency curves and stormwater infrastructure designs for climate change - Lauren M. Cook; Seth McGinnis; Constantine Samaras (Climatic Change, 2020)
Intensity-duration-frequency (IDF) curves, commonly used in stormwater infrastructure design to represent characteristics of extreme rainfall, are gradually being updated to reflect expected changes in rainfall under climate change. The modeling choices used for updating lead to large uncertainties; however, it is unclear how much these uncertainties affect the design and cost of stormwater systems. This study investigates how the choice of spatial resolution of the regional climate model (RCM) ensemble and the spatial adjustment technique affect climate-corrected IDF curves and resulting stormwater infrastructure designs in 34 US cities for the period 2020 to 2099. In most cities, IDF values are significantly different between three spatial adjustment techniques and two RCM spatial resolutions. These differences have the potential to alter the size of stormwater systems designed using these choices and affect the results of climate impact modeling more broadly. The largest change in the engineering decision results when the design storm is selected from the upper bounds of the uncertainty distribution of the IDF curve, which changes the stormwater pipe design size by five increments in some cases, nearly doubling the cost. State and local agencies can help reduce some of this variability by setting guidelines, such as avoiding the use of the upper bound of the future uncertainty range as a design storm and instead accounting for uncertainty by tracking infrastructure performance over time and preparing for adaptation using a resilience plan.

The Vertical and Horizontal Distribution of Deep-Sea Crustaceans in the Order Euphausiacea in the Vicinity of the DeepWater Horizon Oil Spill - Tamara M. Frank; Charles D. Fine; Eric A. Burdett; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Ultra-endurance triathlon performance and markers of whole-body and gut-specific inflammation - Kyle A. Smith; Jacob N. Kisiolek; Brandon D. Willingham; Margaret C. Morrissey; Samantha M. Leyh; Patrick G. Saracino; Daniel A. Baur; Marc D. Cook; Michael J. Ormsbee (European Journal of Applied Physiology, 2020)

Case–control study of endogenous sex steroid hormones and risk of endometrial cancer - Christine M. Friedenreich; Jeroen W. G. Derksen; Thomas Speidel; Darren R. Brenner; Emily Heer; Kerry S. Courneya; Linda S. Cook (Cancer Causes & Control, 2020)

Right place. Right time. Right tool: guidance for using target analysis to increase the likelihood of invasive species detection - Jeffrey T. Morisette; Jamie K. Reaser; Gericke L. Cook; Kathryn M. Irvine; Helen E. Roy (Biological Invasions, 2020)
In response to the National Invasive Species Council’s 2016–2018 Management Plan , this paper provides guidance on applying target analysis as part of a comprehensive framework for the early detection of and rapid response to invasive species (EDRR). Target analysis is a strategic approach for detecting one or more invasive species at a specific locality and time, using a particular method and/or technology(ies). Target analyses, which are employed across a wide range of disciplines, are intended to increase the likelihood of detection of a known target in order to maximize survey effectiveness and cost-efficiency. Although target analyses are not yet a standard approach to invasive species management, some federal agencies are employing target analyses in principle and/or in part to improve EDRR capacities. These initiatives can provide a foundation for a more standardized and comprehensive approach to target analyses. Guidance is provided for improving computational information. Federal agencies and their partners would benefit from a concerted effort to collect the information necessary to perform rigorous target analyses and make it available through open access platforms.

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Inclusion of discards in stock assessment models - Robin M. Cook (Fish and Fisheries, 2019)
A large portion of the catch in many stocks may comprise discards which need to be accounted for in assessments in order to avoid bias in estimates of fishing mortality, stock biomass and reference points. In age‐structured assessment models, discards are sometimes treated as a separate fleet or are added to the landings before fitting so that information about discard behaviour and sampling error is lost. In this paper, an assessment model is developed to describe the discard process with size as a covariate while retaining age‐structured population dynamics. Discard size selection, high grading and bulk dumping of fish at sea are modelled so that the temporal dynamics of the process can be quantified within the assessment. The model is used to show that discarding practices have changed over time in a range of Northeast Atlantic demersal fish. In some stocks, there is a substantial increase in high grading and evidence for bulk discarding which can be related to regulatory measures. The model offers a means of identifying transient effects in the discard process that should be removed from both short‐term forecasts and equilibrium reference point calculations.

Correction to: Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johanssen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Conservation practitioners’ understanding of how to manage evolutionary processes - Carly N. Cook; Carla M. Sgrò (Conservation Biology, 2019)
Both academics and practitioners consider a lack of knowledge about evolutionary theory to be a general barrier to effectively managing genetic diversity. However, it is challenging to judge practitioners’ level of understanding and how this influences their management decisions. Knowledge built through experience may be difficult for practitioners to articulate, but could nonetheless result in appropriate management strategies. To date, researchers have assessed only the explicit (formal) knowledge practitioners have of evolutionary concepts. To explore practitioners’ understanding of evolutionary concepts, it is necessary to consider how they might apply explicit and implicit knowledge to their management decisions. Using an online survey, we asked Australian practitioners to respond to 2 common management scenarios in which there is strong evidence that managing genetic diversity can improve outcomes: managing small, isolated populations and sourcing seeds for restoration projects. In describing their approach to these scenarios, practitioners demonstrated a stronger understanding of the effective management of genetic diversity than the definitions of the relevant concepts. However, their management of genetic diversity within small populations was closer to best practice than for restoration projects. Moreover, the risks practitioners described in implementing best practice management were more likely to affect their approach to restoration than translocation projects. These findings provide evidence that strategies to build the capacity of practitioners to manage genetic diversity should focus on realistic management scenarios. Given that practitioners recognize the importance of adapting their practices and the strong evidence for the benefits of actively managing genetic diversity, there is hope that better engagement by evolutionary biologists with practitioners could facilitate significant shifts toward evolutionarily enlightened management.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johannsen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Population Pharmacokinetic Modeling in the Presence of Missing Time-Dependent Covariates: Impact of Body Weight on Pharmacokinetics of Paracetamol in Neonates - Wojciech Krzyzanski; Sarah F. Cook; Melanie Wilbaux; Catherine M. T. Sherwin; Karel Allegaert; An Vermeulen; John N. van den Anker (The AAPS Journal, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

Rethinking false spring risk - Catherine J. Chamberlain; Benjamin I. Cook; Iñaki García de Cortázar-Atauri; Elizabeth M. Wolkovich (Global Change Biology, 2019)
Temperate plants are at risk of being exposed to late spring freezes. These freeze events—often called false springs—are one of the strongest factors determining temperate plants species range limits and can impose high ecological and economic damage. As climate change may alter the prevalence and severity of false springs, our ability to forecast such events has become more critical, and it has led to a growing body of research. Many false spring studies largely simplify the myriad complexities involved in assessing false spring risks and damage. While these studies have helped advance the field and may provide useful estimates at large scales, studies at the individual to community levels must integrate more complexity for accurate predictions of plant damage from late spring freezes. Here, we review current metrics of false spring, and how, when, and where plants are most at risk of freeze damage. We highlight how life stage, functional group, species differences in morphology and phenology, and regional climatic differences contribute to the damage potential of false springs. More studies aimed at understanding relationships among species tolerance and avoidance strategies, climatic regimes, and the environmental cues that underlie spring phenology would improve predictions at all biological levels. An integrated approach to assessing past and future spring freeze damage would provide novel insights into fundamental plant biology and offer more robust predictions as climate change progresses, which are essential for mitigating the adverse ecological and economic effects of false springs.

α5GABAA subunit-containing receptors and sweetened alcohol cue-induced reinstatement and active sweetened alcohol self-administration in male rats - Cassie M. Chandler; Jaren Reeves-Darby; Sherman A. Jones; J. Abigail McDonald; Guanguan Li; Md T. Rahman; James M. Cook; Donna M. Platt (Psychopharmacology, 2019)

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Characterization of mule deerpox virus in Florida white-tailed deer fawns expands the known host and geographic range of this emerging pathogen - Katherine A. Sayler; Kuttichantran Subramaniam; Jessica M. Jacob; Julia C. Loeb; William F. Craft; Lisa L. Farina; Nicole I. Stacy; Nissin Moussatche; Laurie Cook; John A. Lednicky; Samantha M. Wisely; Thomas B. Waltzek (Archives of Virology, 2019)

A synthesis to understand responses to capture stressors among fish discarded from commercial fisheries and options for mitigating their severity - Katrina V. Cook; Andrea J. Reid; David A. Patterson; Kendra A. Robinson; Jacqueline M. Chapman; Scott G. Hinch; Steven J. Cooke (Fish and Fisheries, 2019)
Discarding non‐target fish from commercial fisheries is controversial and has been a persistent concern for fisheries managers globally. Discard management strategies typically begin by understanding mortality rates among discarded fish, a challenging task given the dynamic, highly context‐specific nature of fisheries. An alternative is to develop our knowledge of how stressors operate by first understanding the causes of mortality that drive this context dependence. Particularly relevant to mitigation efforts is an understanding of how fish respond to the physical factors of fishing, such as the gear itself and methods of fishing and handling the gear. We provide a synthesis of how commercial fishing methods may influence discard mortality and outline means by which capture‐induced stress and injury can be mitigated for common commercial gear types, emphasizing method variants or alternatives during capture, handling, and release that could improve survival. This synthesis identifies exhaustion and injury as the most detrimental and ubiquitous stressors experienced by discarded fish, with few options for mitigating their effects. Trawls and hanging net fisheries are identified as the most harmful gears for by‐catch, characterized by high stress regardless of method variants and limited options for mitigation. Irrespective of gear type and type of stressor, minimizing durations of capture and handling and encouragement of good handling behaviour (e.g., during landing and sorting) will reduce the magnitude of stress and injury in fish, and ultimately increase survival.

Modelling glacial lake outburst flood impacts in the Bolivian Andes - Ioannis Kougkoulos; Simon J. Cook; Laura A. Edwards; Leon J. Clarke; Elias Symeonakis; Jason M. Dortch; Kathleen Nesbitt (Natural Hazards, 2018)

The Influence of Human Demography on Land Cover Change in the Great Lakes States, USA - Mark J. Ducey; Kenneth M. Johnson; Ethan P. Belair; Barbara D. Cook (Environmental Management, 2018)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Prospects for improved off-crop habitat management for pollen beetle control in oilseed rape - Matthew P. Skellern; Samantha M. Cook (Arthropod-Plant Interactions, 2018)

The potential of crop management practices to reduce pollen beetle damage in oilseed rape - Matthew P. Skellern; Samantha M. Cook (Arthropod-Plant Interactions, 2018)

Semiochemical-based alternatives to synthetic toxicant insecticides for pollen beetle management - Alice L. Mauchline; Maxime R. Hervé; Samantha M. Cook (Arthropod-Plant Interactions, 2018)

Restructuring of a mutualism following introduction of Australian fig trees and pollinating wasps to Europe and the USA - E. J. Morgan; T. L. Sutton; C. T. Darwell; J. M. Cook (Biological Invasions, 2018)

Delayed timing of successful spawning of an estuarine dependent fish, black bream Acanthopagrus butcheri - Gregory P. Jenkins; Julia A. Kent; Ryan J. Woodland; Fiona Warry; Stephen E. Swearer; Perran L. M. Cook (Journal of Fish Biology, 2018)
In this paper, we investigate the period of successful spawning for black bream Acanthopagrus butcheri , an obligate estuarine species in southern Australia that typically spawn in spring and early summer. However, back‐calculated spawning dates of juveniles sampled in Gippsland Lakes, Victoria from February to May 2016 indicated that spawning was concentrated over a short period in the Austral mid‐summer (January), with a second spawning in late summer and early autumn (late February–early March). Ichthyoplankton sampling in the tributary estuaries from October to early December collected substantial numbers of fish larvae, dominated by gobiids, eleotrids and retropinnids of freshwater origin, but no A. butcheri . The lack of A. butcheri larvae was consistent with the delayed successful spawning indicated by juvenile otolith data. Freshwater flows declined from late winter to summer, with consistent salinity stratification of the water column. Dissolved oxygen (DO) concentrations were generally very low below the halocline. These conditions may have delayed the upstream spawning migration of adults or may have been unsuitable for survival of eggs and newly‐hatched larvae. Longer‐term predictions for climate change in southern Victoria, including the Gippsland Lakes region, are for lower winter–spring freshwater flows, potentially benefiting the reproductive success of A. butcheri through high water‐column stratification, but only if DO concentrations are not compromised by a lack of high winter flows needed to flush low DO water from the system.

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

An ancient and a recent colonization of islands by an Australian sap‐feeding insect - Caroline Fromont; Paul D. Rymer; Markus Riegler; James M. Cook (Journal of Biogeography, 2018)
Aim To assess the genetic structure, biogeography, and the potential for speciation, of a highly host‐specific insect pest with mainland and island populations. Location East coast of Australia, Lord Howe Island ( LHI ), and New Zealand. Methods We focussed on Mycopsylla fici , a plant sap‐feeding insect host‐specific to the fig tree Ficus macrophylla . We genotyped 152 insects from across the natural and extended host plant range at 14 microsatellite loci and analysed the data using standard population genetics statistics, Discriminant Analysis of Principal Components, genetic autocorrelation, and two Bayesian clustering approaches. Results Genetic analyses revealed that the northeastern Australian mainland population (Brisbane) is the centre of genetic diversity. Northeastern and southeastern (Sydney) mainland populations are genetically differentiated and interconnected in a stepping‐stone pattern. The LHI population is the most distinct genetically and Bayesian estimates indicated that the most recent colonization occurred c . 2,000‐17,500 years ago from a northeastern mainland origin. In contrast, the New Zealand population is little differentiated from the Sydney population and probably diverged by colonization within the past 200 years. Main conclusions The strong differentiation in nuclear microsatellites mirrors previous evidence for divergence of the LHI population from both mt DNA and endosymbiont DNA . The LHI population may be undergoing speciation from the mainland populations, with an oceanic barrier to gene flow. In contrast, the geographically isolated population in Auckland represents a far more recent colonization reflecting the contemporary naturalization of the plant host in New Zealand.

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Persistence of Hepatitis A Virus in Fresh Produce and Production Environments, and the Effect of Disinfection Procedures: A Review - N. Cook; I. Bertrand; C. Gantzer; R. M. Pinto; A. Bosch (Food and Environmental Virology, 2018)

Applying the principles of isotope analysis in plant and animal ecology to forensic science in the Americas - Lesley A. Chesson; Janet E. Barnette; Gabriel J. Bowen; J. Renée Brooks; John F. Casale; Thure E. Cerling; Craig S. Cook; Charles B. Douthitt; John D. Howa; Janet M. Hurley; Helen W. Kreuzer; Michael J. Lott; et al. (Oecologia, 2018)

Functional diversity positively affects prey suppression by invertebrate predators: a meta‐analysis - Arran Greenop; Ben A. Woodcock; Andy Wilby; Samantha M. Cook; Richard F. Pywell (Ecology, 2018)
The use of pesticides within agricultural ecosystems has led to wide concern regarding negative effects on the environment. One possible alternative is the use of predators of pest species that naturally occur within agricultural ecosystems. However, the mechanistic basis for how species can be manipulated in order to maximize pest control remains unclear. We carried out a meta‐analysis of 51 studies that manipulated predator species richness in reference to suppression of herbivore prey to determine which components of predator diversity affect pest control. Overall, functional diversity ( FD ) based on predator's habitat domain, diet breadth and hunting strategy was ranked as the most important variable. Our analysis showed that increases in FD in polycultures led to greater prey suppression compared to both the mean of the component predator species, and the most effective predator species, in monocultures. Further analysis of individual traits indicated these effects are likely to be driven by broad niche differentiation and greater resource exploitation in functionally diverse predator communities. A decoupled measure of phylogenetic diversity, whereby the overlap in variation with FD was removed, was not found to be an important driver of prey suppression. Our results suggest that increasing FD in predatory invertebrates will help maximize pest control ecosystem services in agricultural ecosystems, with the potential to increase suppression above that of the most effective predator species.

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

What shapes plant and animal diversity on urban golf courses? - Sabine S. Nooten; Patrick Schultheiss; Jules Wright; Catriona Macdonald; Brajesh K. Singh; James M. Cook; Sally A. Power (Urban Ecosystems, 2018)

Impacts of Invasive Phragmites australis on Diamondback Terrapin Nesting in Chesapeake Bay - Cassandra E. Cook; Allison M. McCluskey; Randolph M. Chambers (Estuaries and Coasts, 2018)

Using biological–physical modelling for informing sea lice dispersal in Loch Linnhe, Scotland - N K G Salama; A C Dale; V V Ivanov; P F Cook; C C Pert; C M Collins; B Rabe (Journal of Fish Diseases, 2018)
Sea lice are a constraint on the sustainable growth of Scottish marine salmonid aquaculture. As part of an integrated pest management approach, farms coordinate procedures within spatial units. We present observations of copepodids being at relatively greater density than nauplii in upper waters, which informs the development of surface layer sea lice transmission modelling of Loch Linnhe, Scotland, for informing farm parasite management. A hydrodynamic model is coupled with a biological particle‐tracking model, with characteristics of plankton sea lice. Simulations are undertaken for May and October 2011–2013, forced by local wind data collected for those periods. Particles are continually released from positions representing farm locations, weighted by relative farm counts, over a 2‐week period and tracked for a further 5 days. A comparison is made between modelled relative concentrations against physical and biological surveys to provide confidence in model outputs. Connectivity between farm locations is determined in order to propose potential coordination areas. Generally, connectivity depends on flow patterns in the loch and decreases with increased farm separation. The connectivity indices are used to estimate the origins of the sea lice population composition at each site, which may influence medicinal regimens to avoid loss of efficacy.

Association between anti-tuberculosis drug resistance-conferring mutations and treatment outcomes in Myanmar - Htin Lin Aung; Thanda Tun; Wint Wint Nyunt; Yang Fong; John A. Crump; Kyi Kyi Thinn; Si Thu Aung; Gregory M. Cook (Infectious Diseases, 2018)

Discrimination and Variance Structure of Trace Element Signatures in Fe-Oxides: A Case Study of BIF-Mineralisation from the Middleback Ranges, South Australia - Marija Dmitrijeva; Andrew V. Metcalfe; Cristiana L. Ciobanu; Nigel J. Cook; Max Frenzel; William M. Keyser; Geoff Johnson; Kathy Ehrig (Mathematical Geosciences, 2018)

Trends of two HPV-associated cancers in Massachusetts: cervical and oropharyngeal cancer - Erin E. Cook; Susan T. Gershman; Jane J. Kim; Rulla M. Tamimi; R. Monina Klevens; Michelle D. Holmes (Cancer Causes & Control, 2018)

Population trends of bycatch species reflect improving status of target species - Robin M Cook; Michael R Heath (Fish and Fisheries, 2018)
Synthesis studies of fish stocks worldwide suggest improving status of mainly target species that are fully assessed. Other analyses, primarily based on catch data alone, but which include a wider range of species as well as bycatch, present a different view. Catch‐only analyses could be more robust if fishery‐independent data were used and discards accounted for. We develop a model that uses only survey biomass at length and landings data to estimate fishing mortality, spawning stock biomass ( SSB ) and discards. An analysis of species from the North Sea shows the model results compare well with most fully assessed stocks. When applied to bycatch species with limited data, trends in fishing mortality and SSB typically reflect those of the target species. In the last decade, mean fishing mortality rates have tended to decline, while mean SSB has increased. Despite increasing SSB , recent mean recruitment appears to have been lower than previously which may limit future biomass recovery. Species usually associated with more northerly distributions appear to show the greatest effect of weaker recruitment, which may be linked to climate. Estimated discards have tended to decline in magnitude as a result of reduced fishing mortality and associated lower total catches. The model offers a simple way to use both landings and survey data to obtain more detailed population trends for data limited species.

Negative allosteric modulation of alpha 5-containing GABAA receptors engenders antidepressant-like effects and selectively prevents age-associated hyperactivity in tau-depositing mice - Nina Z. Xu; Margot Ernst; Marco Treven; Rok Cerne; Mark Wakulchik; Xia Li; Timothy M. Jones; Scott D. Gleason; Denise Morrow; Jeffrey M. Schkeryantz; Md. Toufiqur Rahman; Guanguan Li; et al. (Psychopharmacology, 2018)

Treating risk as relational on shore platforms and implications for public safety on microtidal rocky coasts - Peter Kamstra; Brian Cook; David M. Kennedy; Barbara Brighton (Natural Hazards, 2018)

The role of catchment land use and tidal exchange in structuring estuarine fish assemblages - F. Y. Warry; P. Reich; P. L. M. Cook; R. Mac Nally; R. J. Woodland (Hydrobiologia, 2018)

Coagulase-negative staphylococci are associated to the mild inflammatory pattern of healthcare-associated meningitis: a retrospective study - S. Couffin; D. Lobo; F. Cook; P. H. Jost; V. Bitot; R. Birnbaum; B. Nebbad; B. Aït-Mamar; W. Lahiani; M. Martin; G. Dhonneur; R. Mounier (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Metabolomics of tomato xylem sap during bacterial wilt reveals Ralstonia solanacearum produces abundant putrescine, a metabolite that accelerates wilt disease - Tiffany M. Lowe‐Power; Connor G. Hendrich; Edda von Roepenack‐Lahaye; Bin Li; Dousheng Wu; Raka Mitra; Beth L. Dalsing; Patrizia Ricca; Jacinth Naidoo; David Cook; Amy Jancewicz; Patrick Masson; et al. (Environmental Microbiology, 2018)
Summary Ralstonia solanacearum thrives in plant xylem vessels and causes bacterial wilt disease despite the low nutrient content of xylem sap. We found that R. solanacearum manipulates its host to increase nutrients in tomato xylem sap, enabling it to grow better in sap from infected plants than in sap from healthy plants. Untargeted GC/MS metabolomics identified 22 metabolites enriched in R. solanacearum ‐infected sap. Eight of these could serve as sole carbon or nitrogen sources for R. solanacearum . Putrescine, a polyamine that is not a sole carbon or nitrogen source for R. solanacearum , was enriched 76‐fold to 37 µM in R. solanacearum ‐infected sap. R. solanacearum synthesized putrescine via a SpeC ornithine decarboxylase. A Δ speC mutant required ≥ 15 µM exogenous putrescine to grow and could not grow alone in xylem even when plants were treated with putrescine. However, co‐inoculation with wildtype rescued ΔspeC growth, indicating R. solanacearum produced and exported putrescine to xylem sap. Intriguingly, treating plants with putrescine before inoculation accelerated wilt symptom development and R. solanacearum growth and systemic spread. Xylem putrescine concentration was unchanged in putrescine‐treated plants, so the exogenous putrescine likely accelerated disease indirectly by affecting host physiology. These results indicate that putrescine is a pathogen‐produced virulence metabolite.

First identification and characterization of Borrobol‐type tephra in the Greenland ice cores: new deposits and improved age estimates - Eliza Cook; Siwan M. Davies; Esther R. Guðmundsdóttir; Peter M. Abbott; Nicholas J. G. Pearce (Journal of Quaternary Science, 2018)
Contiguous sampling of ice spanning key intervals of the deglaciation from the Greenland ice cores of NGRIP, GRIP and NEEM has revealed three new silicic cryptotephra deposits that are geochemically similar to the well‐known Borrobol Tephra (BT). The BT is complex and confounded by the younger closely timed and compositionally similar Penifiler Tephra (PT). Two of the deposits found in the ice are in Greenland Interstadial 1e (GI‐1e) and an older deposit is found in Greenland Stadial 2.1 (GS‐2.1). Until now, the BT was confined to GI‐1‐equivalent lacustrine sequences in the British Isles, Sweden and Germany, and our discovery in Greenland ice extends its distribution and geochemical composition. However, the two cryptotephras that fall within GI‐1e ice cannot be separated on the basis of geochemistry and are dated to 14358 ± 177 a b2k and 14252 ± 173 a b2k, just 106 ± 3 years apart. The older deposit is consistent with BT age estimates derived from Scottish sites, while the younger deposit overlaps with both BT and PT age estimates. We suggest that either the BT in Northern European terrestrial sequences represents an amalgamation of tephra from both of the GI‐1e events identified in the ice‐cores or that it relates to just one of the ice‐core events. A firm correlation cannot be established at present due to their strong geochemical similarities. The older tephra horizon, found within all three ice‐cores and dated to 17326 ± 319 a b2k, can be correlated to a known layer within marine sediment cores from the North Iceland Shelf (ca. 17179‐16754 cal a BP). Despite showing similarities to the BT, this deposit can be distinguished on the basis of lower CaO and TiO 2 and is a valuable new tie‐point that could eventually be used in high‐resolution marine records to compare the climate signals from the ocean and atmosphere.

Evaluation of the genotype MTBDR sl test for detection of second-line drug resistance in drug-resistant Mycobacterium tuberculosis strains in Myanmar - Wint Wint Nyunt; Si Thu Aung; Gregory M. Cook; Htin Lin Aung (Infectious Diseases, 2017)

Defining ecologically relevant scales for spatial protection with long‐term data on an endangered seabird and local prey availability - Richard B. Sherley; Philna Botha; Les G. Underhill; Peter G. Ryan; Danie van Zyl; Andrew C. Cockcroft; Robert J.M. Crawford; Bruce M. Dyer; Timothée R. Cook (Conservation Biology, 2017)
Human activities are important drivers of marine ecosystem functioning. However, separating the synergistic effects of fishing and environmental variability on the prey base of nontarget predators is difficult, often because prey availability estimates on appropriate scales are lacking. Understanding how prey abundance at different spatial scales links to population change can help integrate the needs of nontarget predators into fisheries management by defining ecologically relevant areas for spatial protection. We investigated the local population response (number of breeders) of the Bank Cormorant ( Phalacrocorax neglectus ), a range‐restricted endangered seabird, to the availability of its prey, the heavily fished west coast rock lobster ( Jasus lalandii ). Using Bayesian state‐space modeled cormorant counts at 3 colonies, 22 years of fisheries‐independent data on local lobster abundance, and generalized additive modeling, we determined the spatial scale pertinent to these relationships in areas with different lobster availability. Cormorant numbers responded positively to lobster availability in the regions with intermediate and high abundance but not where regime shifts and fishing pressure had depleted lobster stocks. The relationships were strongest when lobsters 20–30 km offshore of the colony were considered, a distance greater than the Bank Cormorant's foraging range when breeding, and may have been influenced by prey availability for nonbreeding birds, prey switching, or prey ecology. Our results highlight the importance of considering the scale of ecological relationships in marine spatial planning and suggest that designing spatial protection around focal species can benefit marine predators across their full life cycle. We propose the precautionary implementation of small‐scale marine protected areas, followed by robust assessment and adaptive‐management, to confirm population‐level benefits for the cormorants, their prey, and the wider ecosystem, without negative impacts on local fisheries.

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

Erratum - C. T. Darwell; J. M. Cook (Molecular Ecology, 2017)

Diversity of midwater cephalopods in the northern Gulf of Mexico: comparison of two collecting methods - H. Judkins; M. Vecchione; A. Cook; T. Sutton (Marine Biodiversity, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Pseudocyst formation in the marine parasitic amoeba Neoparamoeba perurans : a short‐term survival strategy to abrupt salinity variation - P C Lima; R S Taylor; M Cook (Journal of Fish Diseases, 2017)

Abuse-related effects of subtype-selective GABAA receptor positive allosteric modulators in an assay of intracranial self-stimulation in rats - Kathryn L. Schwienteck; Guanguan Li; Michael M. Poe; James M. Cook; Matthew L. Banks; S. Stevens Negus (Psychopharmacology, 2017)

“The river is us; the river is in our veins”: re-defining river restoration in three Indigenous communities - Coleen A. Fox; Nicholas James Reo; Dale A. Turner; JoAnne Cook; Frank Dituri; Brett Fessell; James Jenkins; Aimee Johnson; Terina M. Rakena; Chris Riley; Ashleigh Turner; Julian Williams; et al. (Sustainability Science, 2017)

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Aligning science and policy to achieve evolutionarily enlightened conservation - Carly N. Cook; Carla M. Sgrò (Conservation Biology, 2017)
There is increasing recognition among conservation scientists that long‐term conservation outcomes could be improved through better integration of evolutionary theory into management practices. Despite concerns that the importance of key concepts emerging from evolutionary theory (i.e., evolutionary principles and processes) are not being recognized by managers, there has been little effort to determine the level of integration of evolutionary theory into conservation policy and practice. We assessed conservation policy at 3 scales (international, national, and provincial) on 3 continents to quantify the degree to which key evolutionary concepts, such as genetic diversity and gene flow, are being incorporated into conservation practice. We also evaluated the availability of clear guidance within the applied evolutionary biology literature as to how managers can change their management practices to achieve better conservation outcomes. Despite widespread recognition of the importance of maintaining genetic diversity, conservation policies provide little guidance about how this can be achieved in practice and other relevant evolutionary concepts, such as inbreeding depression, are mentioned rarely. In some cases the poor integration of evolutionary concepts into management reflects a lack of decision‐support tools in the literature. Where these tools are available, such as risk‐assessment frameworks, they are not being adopted by conservation policy makers, suggesting that the availability of a strong evidence base is not the only barrier to evolutionarily enlightened management. We believe there is a clear need for more engagement by evolutionary biologists with policy makers to develop practical guidelines that will help managers make changes to conservation practice. There is also an urgent need for more research to better understand the barriers to and opportunities for incorporating evolutionary theory into conservation practice.

Genotypic diversity of Mycobacterium tuberculosis strains in Myanmar - Thanda Tun; Khin Saw Aye; Wint Wint Nyunt; John A. Crump; Chie Nakajima; Yasuhiko Suzuki; Kyi Kyi Thinn; Gregory M. Cook; Htin Lin Aung (Infectious Diseases, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Environmental predictors of bovine Eimeria infection in western Kenya - D. N. Makau; G. K. Gitau; G. K. Muchemi; L. F. Thomas; E. A. J. Cook; N. A. Wardrop; E. M. Fèvre; W. A. de Glanville (Tropical Animal Health and Production, 2017)

The structural history and mineralization controls of the world-class Geita Hill gold deposit, Geita Greenstone Belt, Tanzania - I. V. Sanislav; M. Brayshaw; S. L. Kolling; P. H. G. M. Dirks; Y. A. Cook; T. G. Blenkinsop (Mineralium Deposita, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Cryptic diversity in a fig wasp community—morphologically differentiated species are sympatric but cryptic species are parapatric - C. T. Darwell; J. M. Cook (Molecular Ecology, 2017)
A key debate in ecology centres on the relative importance of niche and neutral processes in determining patterns of community assembly with particular focus on whether ecologically similar species with similar functional traits are able to coexist. Meanwhile, molecular studies are increasingly revealing morphologically indistinguishable cryptic species with presumably similar ecological roles. Determining the geographic distribution of such cryptic species provides opportunities to contrast predictions of niche vs. neutral models. Discovery of sympatric cryptic species increases alpha diversity and supports neutral models, while documentation of allopatric/parapatric cryptic species increases beta diversity and supports niche models. We tested these predictions using morphological and molecular data, coupled with environmental niche modelling analyses, of a fig wasp community along its 2700‐km latitudinal range. Molecular methods increased previous species diversity estimates from eight to eleven species, revealing morphologically cryptic species in each of the four wasp genera studied. Congeneric species pairs that were differentiated by a key morphological functional trait (ovipositor length) coexisted sympatrically over large areas. In contrast, morphologically similar species, with similar ovipositor lengths, typically showed parapatric ranges with very little overlap. Despite parapatric ranges, environmental niche models of cryptic congeneric pairs indicate large regions of potential sympatry, suggesting that competitive processes are important in determining the distributions of ecologically similar species. Niche processes appear to structure this insect community, and cryptic diversity may typically contribute mostly to beta rather than alpha diversity.

Qualifying and quantifying minimal hepatic encephalopathy - Marsha Y. Morgan; Piero Amodio; Nicola A. Cook; Clive D. Jackson; Gerald Kircheis; Mette M. Lauridsen; Sara Montagnese; Sami Schiff; Karin Weissenborn (Metabolic Brain Disease, 2016)

Metabolome‐mediated biocryomorphic evolution promotes carbon fixation in G reenlandic cryoconite holes - Joseph M. Cook; Arwyn Edwards; Mark Bulling; Luis A. J. Mur; Sophie Cook; Jarishma K. Gokul; Karen A. Cameron; Michael Sweet; Tristram D. L. Irvine‐Fynn (Environmental Microbiology, 2016)
Summary Microbial photoautotrophs on glaciers engineer the formation of granular microbial‐mineral aggregates termed cryoconite which accelerate ice melt, creating quasi‐cylindrical pits called ‘cryoconite holes’. These act as biogeochemical reactors on the ice surface and provide habitats for remarkably active and diverse microbiota. Evolution of cryoconite holes towards an equilibrium depth is well known, yet interactions between microbial activity and hole morphology are currently weakly addressed. Here, we experimentally perturbed the depths and diameters of cryoconite holes on the Greenland Ice Sheet. Cryoconite holes responded by sensitively adjusting their shapes in three dimensions (‘biocryomorphic evolution’) thus maintaining favourable conditions for net autotrophy at the hole floors. Non‐targeted metabolomics reveals concomitant shifts in cyclic AMP and fucose metabolism consistent with phototaxis and extracellular polymer synthesis indicating metabolomic‐level granular changes in response to perturbation. We present a conceptual model explaining this process and suggest that it results in remarkably robust net autotrophy on the Greenland Ice Sheet. We also describe observations of cryoconite migrating away from shade, implying a degree of self‐regulation of carbon budgets over mesoscales. Since cryoconite is a microbe‐mineral aggregate, it appears that microbial processes themselves form and maintain stable autotrophic habitats on the surface of the Greenland ice sheet.

The balance between nitrogen fixation and denitrification on vegetated and non‐vegetated intertidal sediments - Douglas G. Russell; F. Y. Warry; Perran L. M. Cook (Limnology and Oceanography, 2016)

Size matters: experimental partitioning of the strength of fish herbivory on a fringing coral reef in M oorea, F rench P olynesia - Peggy Fong; Nicholas M. Frazier; Cameron Tompkins‐Cook; Ranjan Muthukrishnan; Caitlin R. Fong (Marine Ecology, 2016)
While the importance of top‐down control by grazers in maintaining tropical reef community structure is well known, the effect of ‘fishing down the food web’, which simultaneously changes the abundance and size of herbivorous fishes, has received less attention. As many fishing practices target the biggest fish and regulations often set minimum size limits, understanding size‐dependency of this controlling force is important. We evaluated the hypothesis that reduction in the abundance and size of fish, regardless of species identity, reduces the role of herbivory in controlling algal abundance on reefs and assessed variation in efficacy of this top‐down control on different types of common macroalgae. We quantified herbivory rates within cages of differing opening sizes on assemblages of four common algal species ( Padina boryana , Dictyota bartayresiana , Halimeda opuntia and Galaxaura fasciculata ) on two fringing reefs in Moorea, French Polynesia. Small acanthurids ( 50% in the largest opening cages (6 × 6 cm) where the maximum size fish entering was 12 cm in length (mean = 7.6, SE = 0.4). Fish entering medium (4.5 × 4.5 cm openings, maximum fish length = 8 cm, mean = 6.3, SE = 0.4) and small (3 × 3 cm openings, no fish observed entering) cages had herbivory rates approximately equal to the control treatment (1 × 1 cm openings). Consumption varied among algal species, with minimal consumption of physically and chemically defended algae and no pattern across treatments. Our results demonstrate a need for management plans to not only maintain the overall abundance of herbivorous fish but to protect the largest sizes for effective top‐down control of algal communities.

Codivergence of the primary bacterial endosymbiont of psyllids versus host switches and replacement of their secondary bacterial endosymbionts - Aidan A. G. Hall; Jennifer L. Morrow; Caroline Fromont; Martin J. Steinbauer; Gary S. Taylor; Scott N. Johnson; James M. Cook; Markus Riegler (Environmental Microbiology, 2016)
Summary Coevolution between insects and bacterial endosymbionts contributes to the success of many insect lineages. For the first time, we tested for phylogenetic codivergence across multiple taxonomic scales, from within genera to superfamily between 36 psyllid species of seven recognised families (Hemiptera: Psylloidea), their exclusive primary endosymbiont Carsonella and more diverse secondary endosymbionts (S‐endosymbionts). Within Aphalaridae, we found that Carsonella and S‐endosymbionts were fixed in one Glycaspis and 12 Cardiaspina populations. The dominant S‐endosymbiont was Arsenophonus , while Sodalis was detected in one Cardiaspina species. We demonstrated vertical transmission for Carsonella and Arsenophonus in three Cardiaspina species. We found strong support for strict cospeciation and validated the informative content of Carsonella as extended host genome for inference of psyllid relationships. However, S‐endosymbiont and host phylogenies were incongruent, and displayed signs of host switching and endosymbiont replacement. The high incidence of Arsenophonus in psyllids and other plant sap‐feeding Hemiptera may be due to repeated host switching within this group. In two psyllid lineages, Arsenophonus and Sodalis genes exhibited accelerated evolutionary rates and AT‐biases characteristic of long‐term host associations. Together with strict vertical transmission and 100% prevalence within host populations, our results suggest an obligate, and not facultative, symbiosis between psyllids and some S‐endosymbionts.

Geochemistry and petrology of the indium-bearing polymetallic skarn ores at Pitkäranta, Ladoga Karelia, Russia - M. Valkama; K. Sundblad; N. J. Cook; V. I. Ivashchenko (Mineralium Deposita, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Much more give than take: South Africa as a major donor but infrequent recipient of invasive non‐native grasses - Vernon Visser; John R. U. Wilson; Lyn Fish; Carly Brown; Garry D. Cook; David M. Richardson (Global Ecology and Biogeography, 2016)
Aim Some regions donate more invaders from particular taxonomic and functional groups than they receive. We demonstrate a particularly striking donor–recipient asymmetry in invasion ecology in grasses. Specifically, we explore whether low numbers of invasive grasses in South Africa can be explained by sampling biases, introduction dynamics, species traits or invasibility of ecosystems. Location South Africa, Australia, Chile, Europe and the USA. Methods We tested for a donor–recipient asymmetry using lists of native and non‐native grasses in five regions across the globe. Then, using distribution, trait and environmental data, we tested whether regions differed in: (1) herbarium sampling effort; (2) introduction dynamics of non‐native grasses (primary uses, area of origin and minimum residence time of non‐native grasses); (3) traits of native and non‐native grasses (leaf size, height, life history, growth form, C 3 :C 4 ratio and taxonomic placement); and (4) fire frequency. Results South Africa has fewer invasive grasses, and fewer widespread invasive grasses, than other regions; while grasses native to South Africa are much more likely to be invasive elsewhere than other grasses. This asymmetry cannot be explained by sampling biases, historical trade links or minimum residence time. Rather it is likely to be due to a combination of: (1) the massive scale of the introduction of South African grasses around the world; (2) specific traits that make South African grasses successful competitors; and (3) the high fire frequency of many South African ecosystems to which many native grasses are adapted, but introduced grasses are not. Main conclusion South Africa has a high diversity of grasses that possess specific traits to cope with fire, grazing and disturbance. This makes them more competitive. Moreover, the high diversity of certain grass lineages in South Africa acts as a reservoir of potential invaders and possibly helps limit invasions in South Africa by promoting fire.

Larvae influence thermoregulatory fanning behavior in honeybees (Apis mellifera L.) - C. N. Cook; S. Durzi; K. J. Scheckel; M. D. Breed (Insectes Sociaux, 2016)

Involvement of contractile vacuoles in the osmoregulation process of the marine parasitic amoeba N eoparamoeba perurans - P C Lima; R S Taylor; M Cook (Journal of Fish Diseases, 2016)

Pyrodiversity begets plant–pollinator community diversity - Lauren C. Ponisio; Kate Wilkin; Leithen K. M'Gonigle; Kelly Kulhanek; Lindsay Cook; Robbin Thorp; Terry Griswold; Claire Kremen (Global Change Biology, 2016)
Fire has a major impact on the structure and function of many ecosystems globally. Pyrodiversity, the diversity of fires within a region (where diversity is based on fire characteristics such as extent, severity, and frequency), has been hypothesized to promote biodiversity, but changing climate and land management practices have eroded pyrodiversity. To assess whether changes in pyrodiversity will have impacts on ecological communities, we must first understand the mechanisms that might enable pyrodiversity to sustain biodiversity, and how such changes might interact with other disturbances such as drought. Focusing on plant–pollinator communities in mixed‐conifer forest with frequent fire in Yosemite National Park, California, we examine how pyrodiversity, combined with drought intensity, influences those communities. We find that pyrodiversity is positively related to the richness of the pollinators, flowering plants, and plant–pollinator interactions. On average, a 5% increase in pyrodiversity led to the gain of approximately one pollinator and one flowering plant species and nearly two interactions. We also find that a diversity of fire characteristics contributes to the spatial heterogeneity ( β ‐diversity) of plant and pollinator communities. Lastly, we find evidence that fire diversity buffers pollinator communities against the effects of drought‐induced floral resource scarcity. Fire diversity is thus important for the maintenance of flowering plant and pollinator diversity and predicted shifts in fire regimes to include less pyrodiversity compounded with increasing drought occurrence will negatively influence the richness of these communities in this and other forested ecosystems. In addition, lower heterogeneity of fire severity may act to reduce spatial turnover of plant–pollinator communities. The heterogeneity of community composition is a primary determinant of the total species diversity present in a landscape, and thus, lower pyrodiversity may negatively affect the richness of plant–pollinator communities across large spatial scales.

Erratum to: Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

Post-traumatic stress is associated with verbal learning, memory, and psychomotor speed in HIV-infected and HIV-uninfected women - Leah H. Rubin; Maria Pyra; Judith A. Cook; Kathleen M. Weber; Mardge H. Cohen; Eileen Martin; Victor Valcour; Joel Milam; Kathryn Anastos; Mary A. Young; Christine Alden; Deborah R. Gustafson; et al. (Journal of NeuroVirology, 2016)

Use of an allostatic neurotechnology by adolescents with postural orthostatic tachycardia syndrome (POTS) is associated with improvements in heart rate variability and changes in temporal lobe electrical activity - John E. Fortunato; Catherine L. Tegeler; Lee Gerdes; Sung W. Lee; Nicholas M. Pajewski; Meghan E. Franco; Jared F. Cook; Hossam A. Shaltout; Charles H. Tegeler (Experimental Brain Research, 2016)

Systems genetics of intravenous cocaine self-administration in the BXD recombinant inbred mouse panel - Price E. Dickson; Mellessa M. Miller; Michele A. Calton; Jason A. Bubier; Melloni N. Cook; Daniel Goldowitz; Elissa J. Chesler; Guy Mittleman (Psychopharmacology, 2016)

Effects of Paclitaxel and Eribulin in Mouse Sciatic Nerve: A Microtubule-Based Rationale for the Differential Induction of Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Brett M. Cook; Jack Reifert; Krystyna M. Wozniak; Barbara S. Slusher; Bruce A. Littlefield; Leslie Wilson; Mary Ann Jordan; Stuart C. Feinstein (Neurotoxicity Research, 2016)

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

One step ahead: a parasitoid disperses farther and forms a wider geographic population than its fig wasp host - Timothy L. Sutton; Markus Riegler; James M. Cook (Molecular Ecology, 2016)
The structure of populations across landscapes influences the dynamics of their interactions with other species. Understanding the geographic structure of populations can thus shed light on the potential for interacting species to co‐evolve. Host–parasitoid interactions are widespread in nature and also represent a significant force in the evolution of plant–insect interactions. However, there have been few comparisons of population structure between an insect host and its parasitoid. We used microsatellite markers to analyse the population genetic structure of Pleistodontes imperialis sp. 1, a fig‐pollinating wasp of Port Jackson fig ( Ficus rubiginosa ), and its main parasitoid, Sycoscapter sp. A, in eastern Australia. Besides exploring this host–parasitoid system, our study also constitutes, to our knowledge, the first study of population structure in a nonpollinating fig wasp species. We collected matched samples of pollinators and parasitoids at several sites in two regions separated by up to 2000 km. We found that pollinators occupying the two regions represent distinct populations, but, in contrast, parasitoids formed a single population across the wide geographic range sampled. We observed genetic isolation by distance for each species, but found consistently lower F ST and R ST values between sites for parasitoids compared with pollinators. Previous studies have indicated that pollinators of monoecious figs can disperse over very long distances, and we provide the first genetic evidence that their parasitoids may disperse as far, if not farther. The contrasting geographic population structures of host and parasitoid highlight the potential for geographic mosaics in this important symbiotic system.

Deep dynamic pools of phosphorus in the sediment of a temperate lagoon with recurring blooms of diazotrophic cyanobacteria - Todd R. Scicluna; Ryan J. Woodland; Yafei Zhu; Michael R. Grace; Perran L. M. Cook (Limnology and Oceanography, 2015)
The storage and release of phosphorus by sediments can act as an important control on the formation of noxious blooms of cyanobacteria in lakes and estuaries. Here we studied the uptake and release of phosphorus associated with iron oxides within sediments of a lagoon system affected by recurring summer blooms of the cyanobacterium Nodularia spumigena . Using an ascorbate extraction, we observed deep pools of iron oxide associated phosphorus (P) at concentrations of ∼5 μ mol g −1 dry sed to a depth of ∼20 cm. This pool rapidly decreased with the onset of water column anoxia, leading to an integrated release of ∼300 mmol of phosphorus m −2 of sediment over 3.5 months. Scaling this flux over the periodically anoxic area of the lake and over the period of an N. spumigena bloom (November–December 2011) gave a broad mass balance agreement with the increase in total phosphorus within the water column and exported from the lagoon. Over this period we estimated that P release from the sediment would have allowed ∼130–187 tonnes of nitrogen to be fixed which agrees with previous estimates of nitrogen fixation. Upon reoxygenation of the water column, a regeneration of the deep iron oxide associated phosphorus pool was observed. This deep dynamic pool of phosphorus was most likely mediated by the burrowing activity of the polychaete Capitella capitata which was observed at the study site. This study underscores the potential importance of sediments colonized by deeply irrigating fauna to become a significant source of phosphorus during water column anoxia.

Antidepressant treatment history and drug-placebo separation in a placebo-controlled trial in major depressive disorder - Aimee M. Hunter; Ian A. Cook; Molly Tartter; Simi K. Sharma; Gregory D. Disse; Andrew F. Leuchter (Psychopharmacology, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Survival and Elimination of Hepatitis E Virus: A Review - Nigel Cook; Wim H. M. van der Poel (Food and Environmental Virology, 2015)

Nitrogen loads explain primary productivity in estuaries at the ecosystem scale - Ryan J. Woodland; James R. Thomson; Ralph Mac Nally; Paul Reich; Victor Evrard; Fiona Y. Wary; Jeffrey P. Walker; Perran L. M. Cook (Limnology and Oceanography, 2015)
Increased nutrient loads stimulate estuary primary productivity and can alter the structure and function of biological communities within estuaries, particularly when producer groups respond differently to changes in nutrient availability. Here, the relative influence of riverine inputs of nitrogen and phosphorus were compared to determine their contribution to estuarine primary producers at large spatial scales. Indices of demersal (extent of macroalgae relative to other vegetation, total shallow water area vegetated) and planktonic (seasonally averaged chlorophyll concentration) primary producer communities were derived at whole‐of‐ecosystem scales in 14 estuaries dispersed across a longitudinal gradient using aerial imaging, underwater videography and in situ monitoring. A model selection framework was used to relate annual nutrient loads (total nitrogen [TN], dissolved inorganic nitrogen [DIN], total phosphorus [TP]), sediment loads (TSS), molar stoichiometric load ratios (TN M : TP M ), and estuary water residence times to the demersal and planktonic indices. Dissolved inorganic nitrogen was the best predictor of the extent of macroalgae, total vegetation coverage, and the concentration of planktonic chlorophyll. Rapid increases in all three indices occurred at inorganic nitrogen loads of ∼ 5–10 Mg km −2 yr −1 . There was some evidence that TN M : TP M , TP and TSS loads were informative model covariates. Relative to DIN loads, TP loads were a poor predictor of the macroalgal and planktonic indices. These findings underscore the critical role of catchment‐derived nitrogen in contributing to producer communities at the whole‐of‐ecosystem scale and support the growing consensus that nitrogen loads (in addition to phosphorus) must be managed to effectively alleviate eutrophication in estuaries.

The association of perceived stress and verbal memory is greater in HIV-infected versus HIV-uninfected women - Leah H. Rubin; Judith A. Cook; Kathleen M. Weber; Mardge H. Cohen; Eileen Martin; Victor Valcour; Joel Milam; Kathryn Anastos; Mary A. Young; Christine Alden; Deborah R. Gustafson; Pauline M. Maki (Journal of NeuroVirology, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Evidence of climate‐driven ecosystem reorganization in the Gulf of Mexico - Mandy Karnauskas; Michael J. Schirripa; J. K. Craig; Geoffrey S. Cook; Christopher R. Kelble; Juan J. Agar; Bryan A. Black; David B. Enfield; David Lindo‐Atichati; Barbara A. Muhling; Kevin M. Purcell; Paul M. Richards; et al. (Global Change Biology, 2015)
The Gulf of Mexico is one of the most ecologically and economically valuable marine ecosystems in the world and is affected by a variety of natural and anthropogenic phenomena including climate, hurricanes, coastal development, agricultural runoff, oil spills, and fishing. These complex and interacting stressors, together with the highly dynamic nature of this ecosystem, present challenges for the effective management of its resources. We analyze a compilation of over 100 indicators representing physical, biological, and economic aspects of the Gulf of Mexico and find that an ecosystem‐wide reorganization occurred in the mid‐1990s. Further analysis of fishery landings composition data indicates a major shift in the late 1970s coincident with the advent of US national fisheries management policy, as well as significant shifts in the mid‐1960s and the mid‐1990s. These latter shifts are aligned temporally with changes in a major climate mode in the Atlantic Ocean: the Atlantic Multidecadal Oscillation ( AMO ). We provide an explanation for how the AMO may drive physical changes in the Gulf of Mexico, thus altering higher‐level ecosystem dynamics. The hypotheses presented here should provide focus for further targeted studies, particularly in regard to whether and how management should adjust to different climate regimes or states of nature. Our study highlights the challenges in understanding the effects of climatic drivers against a background of multiple anthropogenic pressures, particularly in a system where these forces interact in complex and nonlinear ways.

Natural abundance (δ15N) indicates shifts in nitrogen relations of woody taxa along a savanna–woodland continental rainfall gradient - Fiona M. Soper; Anna E. Richards; Ilyas Siddique; Marcos P. M. Aidar; Garry D. Cook; Lindsay B. Hutley; Nicole Robinson; Susanne Schmidt (Oecologia, 2015)

‘Double trouble’: the expansion of the Suez Canal and marine bioinvasions in the Mediterranean Sea - Bella S. Galil; Ferdinando Boero; Marnie L. Campbell; James T. Carlton; Elizabeth Cook; Simonetta Fraschetti; Stephan Gollasch; Chad L. Hewitt; Anders Jelmert; Enrique Macpherson; Agnese Marchini; Cynthia McKenzie; et al. (Biological Invasions, 2015)

Quantifying the effects of light intensity on bioproduction and maintenance energy during photosynthetic growth of Rhodobacter sphaeroides - Saheed Imam; Colin M. Fitzgerald; Emily M. Cook; Timothy J. Donohue; Daniel R. Noguera (Photosynthesis Research, 2015)

Dual functions of NME1 in suppression of cell motility and enhancement of genomic stability in melanoma - David M. Kaetzel; Mary K. Leonard; Gemma S. Cook; Marian Novak; Stuart G. Jarrett; Xiuwei Yang; Alexey M. Belkin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Improving treatment strategies for patients with metastatic castrate resistant prostate cancer through personalized computational modeling - Jill Gallaher; Leah M. Cook; Shilpa Gupta; Arturo Araujo; Jasreman Dhillon; Jong Y. Park; Jacob G. Scott; Julio Pow-Sang; David Basanta; Conor C. Lynch (Clinical & Experimental Metastasis, 2014)

Erratum to: Integrating new discoveries into the “vicious cycle” paradigm of prostate to bone metastases - Leah M. Cook; Gemma Shay; Arturo Araujo; Conor C. Lynch (Cancer and Metastasis Reviews, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Temporal ecology in the Anthropocene - E. M. Wolkovich; B. I. Cook; K. K. McLauchlan; T. J. Davies (Ecology Letters, 2014)
Two fundamental axes – space and time – shape ecological systems. Over the last 30 years spatial ecology has developed as an integrative, multidisciplinary science that has improved our understanding of the ecological consequences of habitat fragmentation and loss. We argue that accelerating climate change – the effective manipulation of time by humans – has generated a current need to build an equivalent framework for temporal ecology. Climate change has at once pressed ecologists to understand and predict ecological dynamics in non‐stationary environments, while also challenged fundamental assumptions of many concepts, models and approaches. However, similarities between space and time, especially related issues of scaling, provide an outline for improving ecological models and forecasting of temporal dynamics, while the unique attributes of time, particularly its emphasis on events and its singular direction, highlight where new approaches are needed. We emphasise how a renewed, interdisciplinary focus on time would coalesce related concepts, help develop new theories and methods and guide further data collection. The next challenge will be to unite predictive frameworks from spatial and temporal ecology to build robust forecasts of when and where environmental change will pose the largest threats to species and ecosystems, as well as identifying the best opportunities for conservation.

Reduction of circulating and selective limbic brain levels of (3α,5α)-3-hydroxy-pregnan-20-one (3α,5α-THP) following forced swim stress in C57BL/6J mice - Antoniette M. Maldonado-Devincci; Matthew C. Beattie; Danielle H. Morrow; Raechel E. McKinley; Jason B. Cook; Todd K. O’Buckley; A. Leslie Morrow (Psychopharmacology, 2014)

Integrating new discoveries into the “vicious cycle” paradigm of prostate to bone metastases - Leah M. Cook; Gemma Shay; Arturo Aruajo; Conor C. Lynch (Cancer and Metastasis Reviews, 2014)

Sources and fate of nitrate in a groundwater‐fed estuary elucidated using stable isotope ratios of nitrogen and oxygen - Wei Wen Wong; Michael R. Grace; Ian Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
We used δ 15 N‐nitrate (NO − 3 ) and δ 18 O‐NO − 3 to unravel the provenance and fate of NO − 3 in a groundwater‐fed estuary. A total of 13 monthly and two time series surveys were undertaken in the Werribee River estuary near Melbourne, Australia. The different survey timescales provided a comprehensive evaluation of the hydrological effects on the biogeochemistry of NO − 3 , which accounted for tidal variability and episodic runoff events. The distribution of δ 15 N and δ 18 O of the estuarine NO − 3 along a mixing line between shallow and deep groundwater provided strong evidence for the predominance of groundwater‐derived NO − 3 in the estuary. During dry periods when water residence time in the estuary was extended, shallow groundwater contributed 60% to 76% of the NO − 3 (calculated from δ 15 N‐NO − 3 and δ 18 O‐NO − 3 ) to the estuary, and assimilation removed ∼ 70% of this groundwater‐derived NO − 3 . During wet periods, deep groundwater provided more (62%) NO − 3 than shallow groundwater, and there was no indication of NO − 3 consumption. Occasional sources of NO − 3 , which were also reflected by their δ 15 N‐NO − 3 and δ 18 O‐NO − 3 values, included NO − 3 from nitrification and sewage‐derived NO − 3 particularly at the bay entrance to the estuary. Greater emphasis should be placed upon the role of groundwater as a substantial NO − 3 end member when assessing NO − 3 biogeochemistry using methods relying on the dual isotopic composition of NO − 3 .

Pore‐water exchange driven by tidal pumping causes alkalinity export in two intertidal inlets - Peter A. Faber; Victor Evrard; Ryan J. Woodland; Ian C. Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
Carbon (C) and alkalinity export from two adjacent intertidal inlets with different terrestrial inputs was investigated. One inlet receives a small creek from an agriculturally dominated catchment, leading to the input of terrestrially sourced material, whereas the other is relatively isolated from terrestrial inputs. Using time‐series measurements, we calculated the total advective exchange of dissolved organic C (DOC; 0–25 mmol m ‒2 d ‒1 ), dissolved inorganic C (DIC; 130–450 mmol m ‒2 d ‒1 ), total alkalinity (TA; 46–310 mmol m ‒ d ‒1 ), and the nutrients nitrate (1.0–1.1 mmol m ‒2 d ‒1 ), ammonia (0.0043–0.10 mmol m ‒2 d ‒1 ), and phosphorus (0.016–0.25 mmol m ‒2 d ‒1 ). Radon‐222 ( 222 Rn) data indicated that pore‐water exchange played an important part in controlling C export from the sediment as an advective flux. The residence time of pore water within both inlets was ~ 6.6–7.4 h, indicating that pore‐water exchange is driven by tidal pumping. The inlet with the greater amount of terrestrial inputs exported much more TA (310 vs. 46 mmol m ‒2 d ‒1 ), suggesting that the extent of land‐to‐sea connectivity influences how C is exported. We hypothesize that this is due to the increased input of iron (Fe) from terrestrial sources, which fosters net TA production through the burial of reduced sulfur species as Fe sulfides. A simple mass balance showed that the TA fluxes observed over 24 h were higher than could be sustained continuously with Fe input from the catchment (0.49 mmol Fe m ‒2 d ‒1 ), meaning that the observed TA fluxes could not be sustained on long timescales. It is most likely that there are periods of net reduction and net oxidation in response to wave action and calm conditions, highlighting the importance of long‐term monitoring over different seasons and weather patterns to obtain representative budgets.

Hydroacoustic tracking of the endangered Atlantic whitefish (Coregonus huntsmani); comparative analysis from wild and hatchery reared populations - A. M. Cook; R. G. Bradford; P. Bentzen (Environmental Biology of Fishes, 2014)

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Processes and Drivers of Nitrogen Removal in Stormwater Biofiltration - Emily G. I. Payne; Tim D. Fletcher; Perran L. M. Cook; Ana Deletic; Belinda E. Hatt (Critical Reviews in Environmental Science and Technology, 2014)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Turning passive detection systems into field experiments: an application using wetland fishes and enclosures to track fine-scale movement and habitat choice - J. S. Rehage; R. E. Boucek; E. A. Cline; M. I. Cook; R. M. Kobza; A. K. Saha (acta ethologica, 2014)

Characterising the distribution of near-shore submarine groundwater discharge along a coastline using 222 Rn and electrical conductivity - M. A. Short; S. Lamontagne; P. G. Cook; R. Cranswick (Australian Journal of Earth Sciences, 2014)

The number of days on which increment occurs is the primary determinant of annual ring width in Callitris intratropica - David M. Drew; Anna E. Richards; Garry D. Cook; Geoffrey M. Downes; Warwick Gill; Patrick J. Baker (Trees, 2014)

The relationship between glycine transporter 1 occupancy and the effects of the glycine transporter 1 inhibitor RG1678 or ORG25935 on object retrieval performance in scopolamine impaired rhesus monkey - Donnie Eddins; Terence G. Hamill; Vanita Puri; Christopher E. Cannon; Jeffrey A. Vivian; Sandra M. Sanabria-Bohórquez; Jacquelynn J. Cook; John A. Morrow; Fiona Thomson; Jason M. Uslaner (Psychopharmacology, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Facilitative plant interactions and climate simultaneously drive alpine plant diversity - Lohengrin A. Cavieres; Rob W. Brooker; Bradley J. Butterfield; Bradley J. Cook; Zaal Kikvidze; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Christian Schöb; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology Letters, 2014)
Interactions among species determine local‐scale diversity, but local interactions are thought to have minor effects at larger scales. However, quantitative comparisons of the importance of biotic interactions relative to other drivers are rarely made at larger scales. Using a data set spanning 78 sites and five continents, we assessed the relative importance of biotic interactions and climate in determining plant diversity in alpine ecosystems dominated by nurse‐plant cushion species. Climate variables related with water balance showed the highest correlation with richness at the global scale. Strikingly, although the effect of cushion species on diversity was lower than that of climate, its contribution was still substantial. In particular, cushion species enhanced species richness more in systems with inherently impoverished local diversity. Nurse species appear to act as a ‘safety net’ sustaining diversity under harsh conditions, demonstrating that climate and species interactions should be integrated when predicting future biodiversity effects of climate change.

Three different [ NiFe ] hydrogenases confer metabolic flexibility in the obligate aerobe M ycobacterium smegmatis - Michael Berney; Chris Greening; Kiel Hards; Desmond Collins; Gregory M. Cook (Environmental Microbiology, 2014)
Summary M ycobacterium smegmatis is an obligate aerobe that harbours three predicted [ NiFe ] hydrogenases, Hyd 1 ( MSMEG _2262–2263), Hyd 2 ( MSMEG _2720‐2719) and Hyd 3 ( MSMEG _3931‐3928). We show here that these three enzymes differ in their phylogeny, regulation and catalytic activity. Phylogenetic analysis revealed that Hyd 1 groups with hydrogenases that oxidize H 2 produced by metabolic processes, and Hyd 2 is homologous to a novel group of putative high‐affinity hydrogenases. Hyd 1 and Hyd 2 respond to carbon and oxygen limitation, and, in the case of Hyd 1, hydrogen supplementation. Hydrogen consumption measurements confirmed that both enzymes can oxidize hydrogen. In contrast, the phylogenetic analysis and activity measurements of Hyd 3 are consistent with the enzyme evolving hydrogen. Hyd 3 is controlled by DosR , a regulator that responds to hypoxic conditions. The strict dependence of hydrogen oxidation of Hyd 1 and Hyd 2 on oxygen suggests that the enzymes are oxygen tolerant and linked to the respiratory chain. This unique combination of hydrogenases allows M . smegmatis to oxidize hydrogen at high ( Hyd 1) and potentially tropospheric ( Hyd 2) concentrations, as well as recycle reduced equivalents by evolving hydrogen ( Hyd 3). The distribution of these hydrogenases throughout numerous soil and marine species of actinomycetes suggests that oxic hydrogen metabolism provides metabolic flexibility in environments with changing nutrient fluxes.

Tree-ring reconstructed summer temperature anomalies for temperate East Asia since 800 C.E. - Edward R. Cook; Paul J. Krusic; Kevin J. Anchukaitis; Brendan M. Buckley; Takeshi Nakatsuka; Masaki Sano (Climate Dynamics, 2013)

Convergent structure of multitrophic communities over three continents - Simon T. Segar; Rodrigo A. S. Pereira; Steve G. Compton; James M. Cook (Ecology Letters, 2013)
Astract Ecological theory predicts that communities using the same resources should have similar structure, but evolutionary constraints on colonisation and niche shifts may hamper such convergence. Multitrophic communities of wasps exploiting fig fruits, which first evolved about 75 MYA , do not show long‐term ‘inheritance’ of taxonomic (lineage) composition or species diversity. However, communities on three continents have converged ecologically in the presence and relative abundance of five insect guilds that we define. Some taxa fill the same niches in each community (phylogenetic niche conservatism). However, we show that overall convergence in ecological community structure depends also on a combination of niche shifts by resident lineages and local colonisations of figs by other insect lineages. Our study explores new ground, and develops new heuristic tools, in combining ecology and phylogeny to address patterns in the complex multitrophic communities of insect on plants, which comprise a large part of terrestrial biodiversity.

Insights into functional pharmacology of α1 GABAA receptors: how much does partial activation at the benzodiazepine site matter? - Srđan Joksimović; Zdravko Varagic; Jovana Kovačević; Michael Van Linn; Marija Milić; Sundari Rallapalli; Tamara Timić; Werner Sieghart; James M. Cook; Miroslav M. Savić (Psychopharmacology, 2013)

Upper thermal tolerances of key taxonomic groups of stream invertebrates - Barbara A. Stewart; Paul G. Close; Peter A. Cook; Peter M. Davies (Hydrobiologia, 2013)

Case–control study of lifetime alcohol consumption and endometrial cancer risk - Christine M. Friedenreich; Thomas P. Speidel; Heather K. Neilson; Annie R. Langley; Kerry S. Courneya; Anthony M. Magliocco; Linda S. Cook (Cancer Causes & Control, 2013)

GidA Expression in Salmonella is Modulated Under Certain Environmental Conditions - Jaclyn M. Rehl; Daniel C. Shippy; Nicholas M. Eakley; Megan D. Brevik; Jordan M. Sand; Mark E. Cook; Amin A. Fadl (Current Microbiology, 2013)

Dynamics of groundwater‐derived nitrate and nitrous oxide in a tidal estuary from radon mass balance modeling - Wei Wen Wong; Michael R. Grace; Ian Cartwright; M. Bayani Cardenas; Peter B. Zamora; Perran L. M. Cook (Limnology and Oceanography, 2013)
We monitored submarine groundwater discharge (SGD) into the Werribee Estuary, Australia, using both chemical and physical methods. SGD occurred at hotspots where 222 Rn persisted through a 12 month survey period. A significant correlation between 222 Rn and ( r 2 = 0.8, p 222 Rn and N 2 O ( r 2 = 0.6, p 222 Rn hotspot, and much higher and N 2 O concentrations in groundwater relative to surface water suggest that elevated and N 2 O concentrations in the estuary were derived from SGD. Two sampling campaigns over 24 h revealed that variations of 222 Rn,, and N 2 O were controlled by tide‐induced hydraulic‐head gradient fluctuations and, possibly to a much lesser extent, by tidal pumping and density‐driven convection. A two‐box 222 Rn mass‐balance model was used to calculate the rate of SGD into two different layers across the pycnocline of the estuary. A higher total groundwater discharge rate of 0.12 ± 0.09 m d −1 was observed in the surface layer during ebb tide compared with 0.10 ± 0.08 m d −1 during flood tide. Fluxes of groundwater‐derived and N 2 O were higher than the riverine flux at baseflow by more than 30 fold and 20 fold, respectively. SGD derived fluxes exceeded the mean annual riverine and TN fluxes by a factor of ∼ 5 and ∼ 3 respectively. SGD‐derived N 2 O fluxes were 170 µmol m −2 d −1 , which are among the highest N 2 O fluxes observed in estuaries.

On the influence of tree size on the climate–growth relationship of New Zealand kauri (Agathis australis): insights from annual, monthly and daily growth patterns - Jan Wunder; Anthony M. Fowler; Edward R. Cook; Maryann Pirie; Shane P. J. McCloskey (Trees, 2013)

Arboreal thorn-dwelling ants coexisting on the savannah ant-plant, Vachellia erioloba, use domatia morphology to select nest sites - H. Campbell; M. D. E. Fellowes; J. M. Cook (Insectes Sociaux, 2013)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

A comment on “What catch data can tell us about the status of global fisheries” (Froese et al. 2012) - R. M. Cook (Marine Biology, 2013)

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

Five in situ observations of live oarfish Regalecus glesne (Regalecidae) by remotely operated vehicles in the oceanic waters of the northern Gulf of Mexico - M. C. Benfield; S. Cook; S. Sharuga; M. M. Valentine (Journal of Fish Biology, 2013)
As part of the SERPENT Project, five observations of apparently healthy oarfish Regalecus glesne by remotely operated vehicles are reported from the northern Gulf of Mexico. Regalecus glesne were observed between 2008 and 2011 at depths from within the epipelagic and mesopelagic zones. These observations include the deepest verified record of R. glesne (463–492 m) and the first record of an arthropod ectoparasite (isopod).

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Development and characterization of 21 polymorphic microsatellite markers for the barren-ground shrew, Sorex ugyunak (Mammalia: Sorcidae), through next-generation sequencing, and cross-species amplification in the masked shrew, S. cinereus - S. A. Sonsthagen; G. K. Sage; M. Fowler; A. G. Hope; J. A. Cook; S. L. Talbot (Conservation Genetics Resources, 2013)

Red oilseed rape? The potential for manipulation of petal colour in control strategies for the pollen beetle (Meligethes aeneus) - Samantha M. Cook; Matthew P. Skellern; Thomas F. Döring; John A. Pickett (Arthropod-Plant Interactions, 2013)

A Transactional and Collaborative Approach to Reducing Effects of Bottom Trawling - MARY GLEASON; ERIKA M. FELLER; MATT MERRIFIELD; STEPHEN COPPS; ROD FUJITA; MICHAEL BELL; STEVE RIENECKE; CHUCK COOK (Conservation Biology, 2013)
Private‐sector financial and legal transactions have long been used to protect terrestrial habitats and working landscapes, but less commonly to address critical threats in marine environments. Transferrable and marketable fishing privileges, including permits and quotas, make it possible to use private‐sector transactions as conservation strategies to address some fishery management issues. Abating the effects of bottom trawling on the seafloor and bycatch and discard associated with the practice has proven challenging. On the Central Coast of California, The Nature Conservancy (TNC), Environmental Defense Fund, local fishers and local, state, and federal authorities worked collaboratively to protect large areas of the seafloor from bottom trawling for groundfish while addressing economic impacts of trawl closures. Contingent on the adoption of trawl‐closure areas by a federal regulatory agency, TNC used private funds to purchase federal groundfish trawl permits and vessels from willing sellers. Trawl‐closure areas were designed collaboratively by combining regional biological diversity and fisheries data with local fishers’ knowledge. The private transactional strategy was designed to remedy some deficiencies in previous federal buyouts, to mitigate economic impacts from trawl closures, and to carefully align with a public regulatory process to protect “essential fish habitat” under the Magnuson‐Stevens Fishery Conservation and Management Act. This collaborative effort protected 1.5 million ha (3.8 million acres) of seafloor, reduced trawl effort in the area by 50%, and set a precedent for collaborative partnerships between conservation and fishing interests. This is the first time a large conservation organization has taken an ownership position in a fishery and demonstrates how nongovernmental organizations can invest in fisheries to improve environmental and economic performance. Un Método Transaccional y Colaborativo para Reducir los Efectos de la Pesca de Arrastre de Fondo

Role of gamma-aminobutyric acid type A (GABAA) receptor subtypes in acute benzodiazepine physical dependence-like effects: evidence from squirrel monkeys responding under a schedule of food presentation - Bradford D. Fischer; Laura P. Teixeira; Michael L. van Linn; Ojas A. Namjoshi; James M. Cook; James K. Rowlett (Psychopharmacology, 2013)

Effects of the benzodiazepine GABAA α1-preferring ligand, 3-propoxy-β-carboline hydrochloride (3-PBC), on alcohol seeking and self-administration in baboons - Barbara J. Kaminski; Michael L. Van Linn; James M. Cook; Wenyuan Yin; Elise M. Weerts (Psychopharmacology, 2013)

Personal air sampling and risks of inhalation exposure during atrazine application in Honduras - Matthew J. Lozier; Jose Francisco Lopez Montoya; Alexis del Rosario; Esperanza Pintor Martínez; Laurence Fuortes; Thomas M. Cook; Wayne T. Sanderson (International Archives of Occupational and Environmental Health, 2013)

Gradient‐based habitat affinities predict species vulnerability to drought - Diane M. Debinski; Jennet C. Caruthers; Dianne Cook; Jason Crowley; Hadley Wickham (Ecology, 2013)
Ecological fingerprints of climate change are becoming increasingly evident at broad geographical scales as measured by species range shifts and changes in phenology. However, finer‐scale species‐level responses to environmental fluctuations may also provide an important bellwether of impending future community responses. Here we examined changes in abundance of butterfly species along a hydrological gradient of six montane meadow habitat types in response to drought. Our data collection began prior to the drought, and we were able to track changes for 11 years, of which eight were considered mild to extreme drought conditions. We separated the species into those that had an affinity for hydric vs. xeric habitats. We suspected that drought would favor species with xeric habitat affinities, but that there could be variations in species‐level responses along the hydrological gradient. We also suspected that mesic meadows would be most sensitive to drought conditions. Temporal trajectories were modeled for both species groups (hydric vs. xeric affinity) and individual species. Abundances of species with affinity for xeric habitats increased in virtually all meadow types. Conversely, abundances of species with affinity for hydric habitats decreased, particularly in mesic and xeric meadows. Mesic meadows showed the most striking temporal abundance trajectory: Increasing abundances of species with xeric habitat affinity were offset by decreasing or stable abundances of species with hydric habitat affinity. The one counterintuitive finding was that, in some hydric meadows, species with affinity for hydric habitats increased. In these cases, we suspect that decreasing moisture conditions in hydric meadows actually increased habitat suitability because sites near the limit of moisture extremes for some species became more acceptable. Thus, species responses were relatively predictable based upon habitat affinity and habitat location along the hydrological gradient, and mesic meadows showed the highest potential for changes in community composition. The implications of these results are that longer‐term changes due to drought could simplify community composition, resulting in prevalence of species tolerant to drying conditions and a loss of species associated with wetter conditions. We contend that this application of gradient analysis could be valuable in assessing species vulnerability of other taxa and ecosystems.

A new flow cytometry method enabling rapid purification of fossil pollen from terrestrial sediments for AMS radiocarbon dating - RICHARD K. TENNANT; RICHARD T. JONES; FIONA BROCK; CHARLOTTE COOK; CHRIS S. M. TURNEY; JOHN LOVE; ROB LEE (Journal of Quaternary Science, 2013)
Radiocarbon ( 14 C) accelerator mass spectrometry (AMS) dating has played a significant role towards improving our understanding of the timing of events and rates of change in archaeological and environmental records over the last 50 000 years. Although it is not always possible to find suitable macrofossils for 14 C dating, microfossils, notably plant pollen, are a viable alternative. Obtaining preserved pollen samples of known provenance and of sufficient quantity for dating by 14 C AMS is, however, challenging because of time‐consuming methods of extraction and purification and possible contamination from other organic material. Here we report a new, rapid and straightforward method using flow cytometry (FCM) to distinguish, sort and collect sufficient quantities of fossil pollen with minimal contamination from lake sediments for radiocarbon dating. Using this approach, we demonstrate 14 C AMS ages that date back to at least 40 ka BP. While future work may be required to refine purification methodologies for different sample types and to precisely quantify the dating limit of this approach, FCM dating of microfossils shows considerable promise in generating robust geochronological frameworks for sequences that have previously proved problematic. Copyright © 2013 John Wiley & Sons, Ltd.

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

Links between Indo-Pacific climate variability and drought in the Monsoon Asia Drought Atlas - Caroline C. Ummenhofer; Rosanne D. D’Arrigo; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climate Dynamics, 2013)

Amycolatopsis umgeniensis sp. nov., isolated from soil from the banks of the Umgeni River in South Africa - Gareth J. Everest; Marilize le Roes-Hill; Clifford Omorogie; Shuk-Kwan Cheung; Andrew E. Cook; Candice M. Goodwin; Paul R. Meyers (Antonie van Leeuwenhoek, 2013)

Mid-twenty-first century warm season climate change in the Central United States. Part I: regional and global model predictions - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2013)

Mid-twenty-first century climate change in the Central United States. Part II: Climate change processes - C. M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2013)
Ensemble regional model simulations over the central US with 30-km resolution are analyzed to investigate the physical processes of projected precipitation changes in the mid-twenty-first century under greenhouse gas forcing. An atmospheric moisture balance is constructed, and changes in the diurnal cycle are evaluated. Wetter conditions over the central US in April and May occur most strongly in the afternoon and evening, supported primarily by moisture convergence by transient eddy activity, indicating enhanced daytime convection. In June, increased rainfall over the northern Great Plains is strongest from 0000 to 0600 LT. It is supported by positive changes in stationary meridional moisture convergence related to a strengthening of the GPLLJ accompanied by an intensification of the western extension of the North Atlantic subtropical high. In the Midwest, decreased rainfall is strongest at 1500 LT and 0000 LT. Both a suppression of daytime convection as well as changes in the zonal flow in the GPLLJ exit region are important. Future drying over the northern Great Plains in summer is triggered by weakened daytime convection, and persists throughout August and September when a deficit in soil moisture develops and land–atmosphere feedbacks become increasingly important.

A comparative gradient approach as a tool for understanding and managing urban ecosystems - Christopher G. Boone; Elizabeth Cook; Sharon J. Hall; Marcia L. Nation; Nancy B. Grimm; Carol B. Raish; Deborah M. Finch; Abigail M. York (Urban Ecosystems, 2012)

Prediction of piezometric surfaces and drain spacing for horizontal drain design - Diana I. Cook; Paul M. Santi; Jerry D. Higgins (Landslides, 2012)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Harmonised Investigation of the Occurrence of Human Enteric Viruses in the Leafy Green Vegetable Supply Chain in Three European Countries - P. Kokkinos; I. Kozyra; S. Lazic; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; M. D’Agostino; N. Cook; et al. (Food and Environmental Virology, 2012)

(R)-Cysteate-nitrogen assimilation by Cupriavidus necator H16 with excretion of 3-sulfolactate: a patchwork pathway - Jutta Mayer; Karin Denger; Klaus Hollemeyer; David Schleheck; Alasdair M. Cook (Archives of Microbiology, 2012)

An intra-specific consensus genetic map of pigeonpea [Cajanus cajan (L.) Millspaugh] derived from six mapping populations - Abhishek Bohra; Rachit K. Saxena; B. N. Gnanesh; Kulbhushan Saxena; M. Byregowda; Abhishek Rathore; P. B. KaviKishor; Douglas R. Cook; Rajeev K. Varshney (Theoretical and Applied Genetics, 2012)

A five-gene cluster involved in utilization of taurine-nitrogen and excretion of sulfoacetaldehyde by Acinetobacter radioresistens SH164 - Zdenĕk Krejčík; David Schleheck; Klaus Hollemeyer; Alasdair M. Cook (Archives of Microbiology, 2012)

Summary Workshop Report: Facilitating Oral Product Development and Reducing Regulatory Burden Through Novel Approaches to Assess Bioavailability/Bioequivalence - James E. Polli; Jack A. Cook; Barbara M. Davit; Paul A. Dickinson; Domenick Argenti; Nancy Barbour; Alfredo García-Arieta; Jean-Marie Geoffroy; Kerry Hartauer; Shoufeng Li; Amitava Mitra; Francis X. Muller; et al. (The AAPS Journal, 2012)

Hypoxic events stimulate nitrogen recycling in a shallow salt‐wedge estuary: The Yarra River estuary, Australia - Keryn L. Roberts; Vera M. Eate; Bradley D. Eyre; Daryl P. Holland; Perran L. M. Cook (Limnology and Oceanography, 2012)
The Yarra River estuary is a salt‐wedge estuary prone to periods of stratification‐induced anoxia and hypoxia (O 2 −1 ) during low‐flow events. Nitrate reduction pathways were examined using the 15 N isotope pairing technique in intact sediment cores, emulating in situ conditions, to evaluate the fate of NO during changing oxygen conditions. Water‐column concentrations of dissolved inorganic carbon (DIC), O 2 , NH, and NO x (NO + NO) were also measured to examine any deviation from conservative behavior (denoted Δ) in response to oxygen variability within the estuary. The estuary was a source of NH in the anoxic bottom waters. Whole‐system estimates using deviations from conservative behavior and core incubations were in good agreement and showed that NH was regenerated more efficiently relative to DIC under hypoxic conditions. For the whole system, mean ΔDIC : ΔNH ratios under oxic (85 ± 33) and hypoxic (20 ± 3) conditions were significantly different. The more‐efficient NH regeneration during hypoxia was attributed to rapid mineralization rates and cessation of nitrification; dissimilatory nitrate reduction to ammonium (DNRA) was not a significant contributor. Unexpectedly, the denitrification : DNRA ratio was significantly higher under hypoxic conditions, with denitrification contributing 99.1% ± 0.3% of total nitrate reduction. DNRA rates were significantly higher during oxic conditions (123.5 ± 30.7 µmol m −2 h −1 ) when compared with rates during hypoxia (0.6 ± 0.1 µmol m −2 h −1 ). The increase in DNRA in the presence of oxygen was attributed to the alleviation of NO limitation during these conditions.

The “salt wedge pump”: Convection‐driven pore‐water exchange as a source of dissolved organic and inorganic carbon and nitrogen to an estuary - Isaac R. Santos; Perran L. M. Cook; Louissa Rogers; Jason de Weys; Bradley D. Eyre (Limnology and Oceanography, 2012)
Hypoxia and anoxia in coastal waters have typically been explained by the respiration of sinking organic matter associated with nutrient over‐enrichment and phytoplankton blooms. Here, we assess whether submarine groundwater discharge and seawater recirculation in sediments can explain widespread chemical anomalies, including low dissolved oxygen, in salt wedge estuaries. We rely on high‐resolution radon (a natural groundwater and pore‐water tracer), and dissolved carbon concentrations and stable isotope observations in the Yarra River estuary in Melbourne, Australia. Radon was highly enriched within the salt wedge, demonstrating enhanced pore‐water exchange at this area. We use the term “salt wedge pump” to describe convection‐driven advective pore‐water exchange at the sediment–water interface during the upstream propagation of the salt wedge. Radon‐derived convection‐driven pore‐water exchange rates within the salt wedge were estimated at 2.8 cm d −1 , a value equivalent to 2.4% of the total river freshwater runoff to the estuary. Pore‐water exchange led to pulsed dissolved inorganic carbon (DIC) and ammonium fluxes ∼ 10‐fold higher than measured diffusive fluxes. In contrast, diffusive sediment oxygen uptake was 5‐fold higher than oxygen uptake related to advective pore‐water exchange. Estimated fluxes, associated with the nonconservative DIC, δ 13 C‐DIC, and ammonium behavior within the estuary support convective pore‐water exchange as a major source of DIC and ammonium to the estuary, but not of dissolved organic carbon, nitrate, dissolved organic nitrogen, and anoxia. Accounting for seawater recirculation in sediments may help reconcile unbalanced carbon and nitrogen budgets in several coastal systems.

Variation in transport explains polymorphism of histidine and urocanate utilization in a natural Pseudomonas population - Xue‐Xian Zhang; Hao Chang; Sieu L. Tran; Jonathan C. Gauntlett; Gregory M. Cook; Paul B. Rainey (Environmental Microbiology, 2012)
Summary Phenotypic variation is a fundamental requirement for evolution by natural selection. While evidence of phenotypic variation in natural populations abounds, its genetic basis is rarely understood. Here we report variation in the ability of plant‐colonizing Pseudomonas to utilize histidine, and its derivative, urocanate, as sole sources of carbon and nitrogen. From a population of 164 phyllosphere‐colonizing Pseudomonas strains, 77% were able to utilize both histidine and urocanate (His + , Uro + ) as growth substrates, whereas the remainder could utilize histidine, but not urocanate (His + , Uro ‐ ), or vice versa (His ‐ , Uro + ). An in silico analysis of the hut locus, which determines capacity to utilize both histidine and urocanate, from genome‐sequenced Pseudomonas strains, showed significant variation in the number of putative transporters. To identify transporter genes specific for histidine and urocanate, we focused on a single genotype of Pseudomonas fluorescens , strain SBW25, which is capable of utilizing both substrates. Site‐directed mutagenesis, combined with [ 3 H]histidine transport assays, shows that hutT u encodes a urocanate‐specific transporter; hutT h encodes the major high‐affinity histidine transporter; and hutXWV encodes an ABC‐type transporter that plays a minor role in histidine uptake. Introduction of cloned copies of hutT h and hutT u from SBW25 into strains incapable of utilizing either histidine, or urocanate, complemented the defect, demonstrating a lack of functional transporters in these strains. Taken together our data show that variation in transport systems, and not in metabolic genes, explains a naturally occurring phenotypic polymorphism.

Quantifying denitrification in rippled permeable sands through combined flume experiments and modeling - Adam J. Kessler; Ronnie N. Glud; M. Bayani Cardenas; Morten Larsen; Michael F. Bourke; Perran L. M. Cook (Limnology and Oceanography, 2012)
We measured denitrification in permeable sediments in a sealed flume tank with environmentally representative fluid flow and solute transport behavior using novel measurements. Numerical flow and reactive transport models representing the flume experiments were implemented to provide mechanistic insight into the coupled hydrodynamic and biogeochemical processes. There was broad agreement between the model results and experimental data. The model showed that the coupling between nitrification and denitrification was relatively weak in comparison to that in cohesive sediments. This was due to the direct advective transport between anoxic pore water and the overlying water column, and little interaction between the mostly oxic advective region and the underlying anoxic region. Denitrification was therefore mainly fueled by nitrate supplied from the water column. This suggests that the capacity of permeable sediments with nonmigratory ripples to remove bioavailable nitrogen from coastal ecosystems is lower than that of cohesive sediments. We conclude that while experimental measurements provide a good starting point for constraining key parameters, reactive transport models with realistic kinetic and transport parameters provide critical insight into biogeochemical processes in permeable sediment that are difficult to experimentally evaluate.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis - Leah M. Cook; Xuemei Cao; Alexander E. Dowell; Michael T. Debies; Mick D. Edmonds; Benjamin H. Beck; Robert A. Kesterson; Renee A. Desmond; Andra R. Frost; Douglas R. Hurst; Danny R. Welch (Clinical & Experimental Metastasis, 2012)

Residential landscapes as social-ecological systems: a synthesis of multi-scalar interactions between people and their home environment - Elizabeth M. Cook; Sharon J. Hall; Kelli L. Larson (Urban Ecosystems, 2012)

Thoracic Artificial Lung Impedance Studies Using Computational Fluid Dynamics and In Vitro Models - Rebecca E. Schewe; Khalil M. Khanafer; Ryan A. Orizondo; Keith E. Cook (Annals of Biomedical Engineering, 2012)

Lifelong CRF overproduction is associated with altered gene expression and sensitivity of discrete GABAA and mGlu receptor subtypes - Christiaan H. Vinkers; Hendrikus Hendriksen; Ruud van Oorschot; James M. Cook; Sundari Rallipalli; Shengming Huang; Mark J. Millan; Berend Olivier; Lucianne Groenink (Psychopharmacology, 2012)

Phylogeography of related diadromous species in continental and island settings, and a comparison of their potential and realized dispersal patterns - Benjamin D. Cook; Timothy J. Page; Jane M. Hughes (Journal of Biogeography, 2012)
Aim To compare patterns of potential and realized dispersal in ecologically similar and phylogenetically related amphidromous shrimps (Atyidae) in continental and island‐dominated landscapes. Location Eastern Australia and the Caribbean region. Methods Population genetic and phylogeographic analyses of mitochondrial DNA data for Australatya striolata from eastern Australia (a continental landscape) and Atya scabra from the Caribbean (an island‐dominated landscape). Results Australatya striolata contained two highly divergent genetic lineages in eastern Australia, corresponding to the disjunct northern and southern populations, respectively. These lineages probably represent allopatric cryptic species, both of which were found to have genetically homogeneous population structures within their regions of occurrence. Atya scabra was genetically homogeneous throughout the Caribbean. Recent population expansions were detected for Atya scabra in the Caribbean, but not for northern or southern Australatya striolata . Main conclusions The findings of this study are consistent with previously reported patterns of genetic population structure in amphidromous species in both continental and island‐dominated landscapes, suggesting that potential for widespread dispersal is typically matched by realized patterns of panmixia. We therefore raise the hypothesis that landscape setting (i.e. continent or island‐dominated) does not influence dispersal patterns in amphidromous species. Further studies, especially of population genetic patterns of amphidromous species on continents, are needed to test this idea. Interestingly, results of the genetic neutrality tests led us to hypothesize that demographic and drift‐mutation equilibrium is attainable although not always evident for amphidromous species on continents, but is not attainable for those species distributed across island settings.

The glucocorticoid stress response is repeatable between years in a wild teleost fish - K. V. Cook; C. M. O’Connor; K. M. Gilmour; S. J. Cooke (Journal of Comparative Physiology A, 2011)

Predicting phenology by integrating ecology, evolution and climate science - Stephanie Pau; Elizabeth M. Wolkovich; Benjamin I. Cook; T. Jonathan Davies; Nathan J. B. Kraft; Kjell Bolmgren; Julio L. Betancourt; Elsa E. Cleland (Global Change Biology, 2011)
Forecasting how species and ecosystems will respond to climate change has been a major aim of ecology in recent years. Much of this research has focused on phenology – the timing of life‐history events. Phenology has well‐demonstrated links to climate, from genetic to landscape scales; yet our ability to explain and predict variation in phenology across species, habitats and time remains poor. Here, we outline how merging approaches from ecology, climate science and evolutionary biology can advance research on phenological responses to climate variability. Using insight into seasonal and interannual climate variability combined with niche theory and community phylogenetics, we develop a predictive approach for species’ reponses to changing climate. Our approach predicts that species occupying higher latitudes or the early growing season should be most sensitive to climate and have the most phylogenetically conserved phenologies. We further predict that temperate species will respond to climate change by shifting in time, while tropical species will respond by shifting space, or by evolving. Although we focus here on plant phenology, our approach is broadly applicable to ecological research of plant responses to climate variability.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The potential to reconstruct broadscale climate indices associated with southeast Australian droughts from Athrotaxis species, Tasmania - K. J. Allen; J. Ogden; B. M. Buckley; E. R. Cook; P. J. Baker (Climate Dynamics, 2011)

Evaluation of the use of recN sequence analysis in the phylogeny of the genus Amycolatopsis - Gareth J. Everest; Andrew E. Cook; Bronwyn M. Kirby; Paul R. Meyers (Antonie van Leeuwenhoek, 2011)

Sub-Saharan Northern African climate at the end of the twenty-first century: forcing factors and climate change processes - Christina M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Repurposing climate reconstructions for drought prediction in Southeast Asia - Andrew R. Bell; Benjamin I. Cook; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climatic Change, 2011)

Development and use of genic molecular markers (GMMs) for construction of a transcript map of chickpea (Cicer arietinum L.) - Neha Gujaria; Ashish Kumar; Preeti Dauthal; Anuja Dubey; Pavana Hiremath; A. Bhanu Prakash; Andrew Farmer; Mangla Bhide; Trushar Shah; Pooran M. Gaur; Hari D. Upadhyaya; Sabhyata Bhatia; et al. (Theoretical and Applied Genetics, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Population structure and linkage disequilibrium in oat (Avena sativa L.): implications for genome-wide association studies - M. A. Newell; D. Cook; N. A. Tinker; J.-L. Jannink (Theoretical and Applied Genetics, 2011)

You are what you eat, whenever or wherever you eat it: an integrative analysis of fish food habits in Canadian and U.S.A. waters - A. Bundy; J. S. Link; B. E. Smith; A. M. Cook (Journal of Fish Biology, 2011)
The degree to which fish diet differs by season and area, particularly over broad scales, was examined for the first time in temperate, contiguous north‐west Atlantic Ocean waters by comparing food habit data for 10 species of fishes collected concurrently during the spring and autumn surveys in the U.S.A. (Gulf of Maine proper and Georges Bank) and in the summer survey in Canada (western Scotian Shelf and Bay of Fundy). For most species, there was a general concurrence among the three seasons and four areas: summer diets had the same dominant prey items as spring and autumn diets. Although a suite of multivariate analyses did elucidate some differences in specific proportions of the diet for these species across seasons and areas, the main prey did not substantially change for most of these species. These results suggest that there are (1) minimal differences in diet across season for these species at these taxonomic resolutions, (2) there are minimal differences in diet geographically for these species and (3) differences across species, as expected, are important. Many fisheries ecosystem and multispecies models are dependent on food habit data, where resolving seasonal and spatial differences in diet remains an important consideration; however, the present work implies that amalgamated estimates of diet from seasonal surveys may be a reasonable approach when no finer seasonal resolution exists, as long as due diligence is exercised.

Tolerance of nonindigenous cichlid fishes (Cichlasoma urophthalmus, Hemichromis letourneuxi) to low temperature: laboratory and field experiments in south Florida - Pamela J. Schofield; William F. Loftus; Robert M. Kobza; Mark I. Cook; Daniel H. Slone (Biological Invasions, 2010)

Succession and physiological health of freshwater microalgal fouling in a Tasmanian hydropower canal - Kathryn J. Perkins; Jessica M. Andrewartha; Andrew McMinn; Suellen S. Cook; Gustaaf M. Hallegraeff (Biofouling, 2010)

The WAMME regional model intercomparison study - Leonard M. Druyan; Jinming Feng; Kerry H. Cook; Yongkang Xue; Matthew Fulakeza; Samson M. Hagos; Abdourahamane Konaré; Wilfran Moufouma-Okia; David P. Rowell; Edward K. Vizy; Seidou Sanda Ibrah (Climate Dynamics, 2010)

Northern African climate at the end of the twenty-first century: an integrated application of regional and global climate models - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2010)

Case–control study of lifetime total physical activity and endometrial cancer risk - Christine M. Friedenreich; Linda S. Cook; Anthony M. Magliocco; Máire A. Duggan; Kerry S. Courneya (Cancer Causes & Control, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Effect of a flood event on the dynamics of phytoplankton and biogeochemistry in a large temperate Australian lagoon - Perran L. M. Cook; Daryl P. Holland; Andrew R. Longmore (Limnology and Oceanography, 2010)
In episodically driven estuaries, nutrient delivery is typically confined to sporadic flow events, followed by intense biogeochemical recycling of nutrients. We document the response of a temperate lagoon system with episodic winter‐ or spring‐dominated catchment inflows (Gippsland Lakes, southeast Australia) to a flood event. High winter inflows resulted in high surface‐water concentrations of inorganic nitrogen (IN; NO 2 − + NO 3 − + NH 4 + ) relative to reactive phosphorus (RP) with an IN :RP ratio > 100. This resulted in a rapid diatom and dinoflagellate bloom, which collapsed as water column nutrients were exhausted. Increased carbon delivery to the sediment stimulated benthic respiration and depleted bottom‐water oxygen, which led to a large release of RP from the sediments, decreasing the IN :RP ratio in the bottom water to ~6. Strong stratification of the water column allowed the accumulation of RP in the bottom water over spring and into summer. Mixing of RP from the bottom water over summer triggered the development of a Nodularia spumigena Mertens bloom. As such, the nutrient supply for the Nodularia bloom was through a biogeochemical filter that strongly favored N 2 ‐fixing cyanobacterial blooms by reducing IN :RP ratios through a combination of sediment denitrification and release of stored phosphorus from within the sediment. These observations lead us to the paradoxical conclusion that high nitrogen loading over winter contributed to severe nitrogen limitation over summer, and highlight the importance of controlling both nitrogen and phosphorus loading to estuaries.

Microcyclic conidiogenesis in powdery mildews and its association with intracellular parasitism by Ampelomyces - Levente Kiss; Alexandra Pintye; Györgyi Zséli; Tünde Jankovics; Orsolya Szentiványi; Yaser M. Hafez; Roger T. A. Cook (European Journal of Plant Pathology, 2010)

Slowing of dexterous manipulation in old age: force and kinematic findings from the ‘nut-and-rod’ task - Kelly J. Cole; Kelly M. Cook; Stephanie M. Hynes; Warren G. Darling (Experimental Brain Research, 2010)

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

Immigration history of amphidromous species on a Greater Antillean island - Benjamin D. Cook; Catherine M. Pringle; Jane M. Hughes (Journal of Biogeography, 2010)
Aim To use molecular data to test for dispersal structuring in the immigration history of an amphidromous community on an island. Location The Caribbean island of Puerto Rico. Methods Mitochondrial DNA sequences were obtained from 11 amphidromous species, including shrimps, fish and a gastropod, sampled from throughout the island. The timing of population expansion ( T E ) in each species was calculated using nucleotide variation and molecular clock dating methods. The order of species accumulation was then reconstructed (oldest to most recent estimate for T E ), and groups of species with non‐overlapping estimates for T E were identified. The temporal span and average immigration rate for each group were calculated and compared with expectations of two previously published models of island immigration [the ‘dispersal‐structured model of island recolonization’ ( Whittaker & Jones, Oikos , 1994 , 69 , 524–529), which predicts short phases of rapid immigration followed by extended phases with relatively slow immigration rates; and the ‘colonization window hypothesis’ ( Carine, Taxon , 2005 , 54 , 895–903), which suggests that opportunities for island colonization are temporally constrained to discrete waves of colonization]. Results The molecular data indicated the immigration history of Puerto Rican amphidromous fauna from the late Pleistocene through the Holocene and identified two groups of species with non‐overlapping estimates for T E and one group that overlapped with the other two groups. The temporal span, average immigration rate and lack of discreteness between all three groups indicated a continuum of immigration rather than distinct phases of species arrivals. Main conclusions This study did not support the expectations of the immigration models and suggested that amphidromous species from Puerto Rico comprise a single class of marine‐based dispersers. The immigration sequence we report probably reflects a recolonization chronology in this community, in keeping with the notion of species turnover through time. Four areas of future research into the immigration history of amphidromous species on islands are identified, and indicated the possibility that equilibrium processes govern long‐term community change in amphidromous biota on islands.

Amoebic gill disease resistance is not related to the systemic antibody response of Atlantic salmon, Salmo salar L. - R S Taylor; P B Crosbie; M T Cook (Journal of Fish Diseases, 2010)
Amoebic gill disease (AGD) is a proliferative gill tissue response caused by Neoparamoeba perurans and is the main disease affecting Australian marine farmed Atlantic salmon. We have previously proposed that macroscopic gill health (‘gill score’) trajectories and challenge survival provide evidence of a change in the nature of resistance to AGD. In order to examine whether the apparent development of resistance was because of an adaptive response, serum was sequentially sampled from the same individuals over the first three rounds of natural AGD infection and from survivors of a subsequent non‐intervention AGD survival challenge. The systemic immune reaction to ‘wildtype’ Neoparamoeba sp. was characterized by Western blot analysis and differentiated to putative carbohydrate or peptide epitopes by periodate oxidation reactions. The proportion of seropositive fish increased from 46% to 77% with each AGD round. Antibody response to carbohydrate epitope(s) was immunodominant, occurring in 43–64% of samples. Antibodies that bound peptide epitope were identified in 16% of the challenge survivors. A 1:50 (single‐dilution) enzyme‐linked immunosorbent assay confirmed a measurable immune titre in 13% of the survivors. There was no evidence that antibodies recognizing wildtype Neoparamoeba provided significant protection against AGD.

The petrogenesis of sodic island arc magmas at Savo volcano, Solomon Islands - D. J. Smith; M. G. Petterson; A. D. Saunders; I. L. Millar; G. R. T. Jenkin; T. Toba; J. Naden; J. M. Cook (Contributions to Mineralogy and Petrology, 2009)

Increased belowground biomass and soil CO 2 fluxes after a decade of carbon dioxide enrichment in a warm‐temperate forest - Robert B. Jackson; Charles W. Cook; Jeffrey S. Pippen; Sheila M. Palmer (Ecology, 2009)
Atmospheric CO 2 concentrations have risen 40% since the start of the industrial revolution. Beginning in 1996, the Duke Free‐Air CO 2 Enrichment experiment has exposed plots in a loblolly pine forest to an additional 200 μL/L CO 2 compared to trees growing in ambient CO 2 . This paper presents new belowground data and a synthesis of results through 2008, including root biomass and nutrient concentrations, soil respiration rates, soil pore‐space CO 2 concentrations, and soil‐solution chemistry to 2 m depth. On average in elevated CO 2 , fine‐root biomass in the top 15 cm of soil increased by 24%, or 59 g/m 2 (26 g/m 2 C). Coarse‐root biomass sampled in 2008 was twice as great in elevated CO 2 and suggests a storage of ~20 g C·m −2 ·yr −1 . Root C and N concentrations were unchanged, suggesting greater belowground plant demand for N in high CO 2 . Soil respiration was significantly higher by 23% on average as assessed by instantaneous infrared gas analysis and 24‐h integrated estimates. N fertilization decreased soil respiration and fine‐root biomass by ~10–20% in both ambient and elevated CO 2 . In recent years, increases in root biomass and soil respiration grew stronger, averaging ~30% at high CO 2 . Peak changes for root biomass, soil respiration, and other variables typically occurred in midsummer and diminished in winter. Soil CO 2 concentrations between 15 and 100 cm depths increased 36–60% in elevated CO 2 . Differences from 30 cm depth and below were still increasing after 10 years' exposure to elevated CO 2 , with soil CO 2 concentrations >10 000 μL/L higher at 70‐ and 100‐cm depths, potentially influencing soil acidity and rates of weathering. Soil solution Ca 2+ and total base cation concentrations were 140% and 176% greater, respectively, in elevated CO 2 at 200 cm depth. Similar increases were observed for soil‐solution conductivity and alkalinity at 200 cm in elevated CO 2 . Overall, the effect of elevated CO 2 belowground shows no sign of diminishing after more than a decade of CO 2 enrichment.

Seizure Detection Using Seizure Probability Estimation: Comparison of Features Used to Detect Seizures - Levin Kuhlmann; Anthony N. Burkitt; Mark J. Cook; Karen Fuller; David B. Grayden; Linda Seiderer; Iven M. Y. Mareels (Annals of Biomedical Engineering, 2009)

Dissociating anxiolytic and sedative effects of GABAAergic drugs using temperature and locomotor responses to acute stress - Christiaan H. Vinkers; Marianne Klanker; Lucianne Groenink; S. Mechiel Korte; James M. Cook; Michael L. Van Linn; Seth C. Hopkins; Berend Olivier (Psychopharmacology, 2009)

Glutamatergic and GABAergic modulations of ultrasonic vocalizations during maternal separation distress in mouse pups - Aki Takahashi; Jasmine J. Yap; Dawnya Zitzman Bohager; Sara Faccidomo; Terry Clayton; James M. Cook; Klaus A. Miczek (Psychopharmacology, 2009)

Contribution of α1 subunit-containing γ-aminobutyric acidA (GABAA) receptors to motor-impairing effects of benzodiazepines in squirrel monkeys - Stephanie C. Licata; Donna M. Platt; James M. Cook; Michael L. Van Linn; James K. Rowlett (Psychopharmacology, 2009)

Respiratory Irritants in Australian Bushfire Smoke: Air Toxics Sampling in a Smoke Chamber and During Prescribed Burns - Annemarie J. B. M. De Vos; Fabienne Reisen; Angus Cook; Brian Devine; Philip Weinstein (Archives of Environmental Contamination and Toxicology, 2009)

Phylogenetic analysis of actinobacterial populations associated with Antarctic Dry Valley mineral soils - Olubukola O. Babalola; Bronwyn M. Kirby; Marilize Le Roes‐Hill; Andrew E. Cook; S. Craig Cary; Stephanie G. Burton; Don A. Cowan (Environmental Microbiology, 2009)
Summary Despite the apparent severity of the environmental conditions in the McMurdo Dry Valleys, Eastern Antarctica, recent phylogenetic studies conducted on mineral soil samples have revealed the presence of a wide diversity of microorganisms, with actinobacteria representing one of the largest phylotypic groups. Previous metagenomic studies have shown that the majority of Antarctic actinobacterial populations are classified as ‘uncultured’. In this study, we assessed the diversity of actinobacteria in Antarctic cold desert soils by complementing traditional culture‐based techniques with a metagenomic study. Phylogenetic analysis of clones generated with actinobacterium‐ and streptomycete‐specific PCR primers revealed that the majority of the phylotypes were most closely related to uncultured Pseudonocardia and Nocardioides species. Phylotypes most closely related to a number of rarer actinobacteria genera, including Geodermatophilus , Modestobacter and Sporichthya , were also identified. While complementary culture‐dependent studies isolated a number of Nocardia and Pseudonocardia species, the majority of the cultured isolates (> 80%) were S treptomyces species – although phylotypes affiliated to the genus Streptomyces were detected at a low frequency in the metagenomic study. This study confirms that Antarctic Dry Valley desert soil harbours highly diverse actinobacterial communities and suggests that many of the phylotypes identified may represent novel, uncultured species.

Is (−)-Catechin a Novel Weapon of Spotted Knapweed (Centaurea stoebe)? - Stephen O. Duke; Amy C. Blair; Franck E. Dayan; Robert D. Johnson; Kumudini M. Meepagala; Daniel Cook; Joanna Bajsa (Journal of Chemical Ecology, 2009)

Electronic tags reveal behaviour of captured and discarded fish - F. C. Neat; M. Breen; R. M. Cook; I. M. Gibb; P. J. Wright (Journal of Fish Biology, 2009)
Internally implanted data storage tags (DST) recording hydrostatic pressure (depth) and temperature in Atlantic cod Gadus morhua were used to track the behaviour of nine individuals during fishing operations. Gadus morhua showed identifiable and characteristic behavioural responses to different capture processes. In a unique observation, one fish survived being discarded and upon return to the seabed exhibited a cessation of activity comparable to observations on stressed fish under laboratory conditions.

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Frequency-Domain Fluorescence Lifetime Measurements via Frequency Segmentation and Recombination as Applied to Pyrene with Dissolved Humic Materials - Hadi M. Marwani; Mark Lowry; Baoshan Xing; Isiah M. Warner; Robert L. Cook (Journal of Fluorescence, 2009)

Brain Electrical Source Differences between Depressed Subjects and Healthy Controls - Alexander S. Korb; Ian A. Cook; Aimee M. Hunter; Andrew F. Leuchter (Brain Topography, 2008)

Therapeutic frontiers: preventing and treating infectious diseases by inhibiting bacterial quorum sensing - C. A. Martin; A. D. Hoven; A. M. Cook (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Sulfoacetate released during the assimilation of taurine-nitrogen by Neptuniibacter caesariensis: purification of sulfoacetaldehyde dehydrogenase - Zdenĕk Krejčík; Karin Denger; Sonja Weinitschke; Klaus Hollemeyer; Václav Pačes; Alasdair M. Cook; Theo H. M. Smits (Archives of Microbiology, 2008)

Different bacterial strategies to degrade taurocholate - Verena Rösch; Karin Denger; David Schleheck; Theo H. M. Smits; Alasdair M. Cook (Archives of Microbiology, 2008)

Summary Workshop Report: Bioequivalence, Biopharmaceutics Classification System, and Beyond - James E. Polli; Bertil S. I. Abrahamsson; Lawrence X. Yu; Gordon L. Amidon; John M. Baldoni; Jack A. Cook; Paul Fackler; Kerry Hartauer; Gordon Johnston; Steve L. Krill; Robert A. Lipper; Waseem A. Malick; et al. (The AAPS Journal, 2008)

Marine Metapopulations - Celeste Benham; Alison M. Cawood; Geoffrey S. Cook; Ange Darnell; Peter C. Davison; Miriam C. Goldstein; Ayana Elizabeth Johnson; Talina Konotchick; Elisa M. Maldonado; Alexis L. Pasulka; Jennifer C. Prairie; Serena M. Moseman; et al. (Marine Ecology, 2008)

Genetic variants in the 8q24 locus and risk of testicular germ cell tumors - Michael B. Cook; Barry I. Graubard; Sabah M. Quraishi; Meredith Yeager; Stephen J. Chanock; Andrew Crenshaw; Ralph L. Erickson; Mark V. Rubertone; Gilles Thomas; Katherine A. McGlynn (Human Genetics, 2008)

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

Species richness in Madeiran land snails, and its causes - Laurence M. Cook (Journal of Biogeography, 2008)
Aim To unravel the reasons why a group of islands of 800 km 2 area should support over 200 extant land snail species. Location The temperate Atlantic Madeiran archipelago. Methods Distributional surveys and model testing. Results Repeated volcanic events have changed the topography of the islands and created periodic further isolates. There has been climatic fluctuation and varying sea level. Individual locations are not species‐rich, but there is replacement from one subregion to another. Evidence of competitive interactions is lacking. Main conclusions High diversity results from the fortuitous coincidence of rates of geological and climatic change and isolation on the one hand, and migration and genetic divergence on the other. Hubbell’s neutral model of biodiversity explains species richness if a factor is added describing structural instability or periodicity, here called the geodetic rate. This geodetic, biological interaction can explain why some archipelagos are species‐rich.

Andropogon gayanus (Gamba Grass) Invasion Increases Fire-mediated Nitrogen Losses in the Tropical Savannas of Northern Australia - N. A. Rossiter-Rachor; S. A. Setterfield; M. M. Douglas; L. B. Hutley; G. D. Cook (Ecosystems, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

°Molecular evidence for sequential colonization and taxon cycling in freshwater decapod shrimps on a Caribbean island - BENJAMIN D. COOK; CATHERINE M. PRINGLE; JANE M. HUGHES (Molecular Ecology, 2008)
Taxon cycling, i.e. sequential phases of expansions and contractions in species’ distributions associated with ecological or morphological shifts, are postulated to characterize dynamic biogeographic histories in various island faunas. The Caribbean freshwater shrimp assemblage is mostly widespread and sympatric throughout the region, although one species (Atyidae: Atya lanipes ) is geographically restricted and ecologically and morphologically differentiated from other Atya species. Using patterns of nucleotide variation at the COI mtDNA gene in five species of freshwater shrimp ( A. lanipes , A. scabra , A. innocuous ; Xiphocarididae: Xiphocaris elongata ; Palaemonidae: Macrobrachium faustinum ) from Puerto Rico, we expected to detect a signature of sequential colonization in these shrimp, consistent with the concept of taxon cycling, and expected that A. lanipes would be at a different taxon stage (i.e. an early stage species) to all other species. We also examined patterns of genetic population structure in each species expected with poor, intermediate and well‐developed abilities for among‐river dispersal. Population expansions were detected in all species, although the relative timing of the expansions varied among them. Assuming that population expansions followed colonization of Puerto Rico by freshwater shrimp, results bear the hallmarks of sequential colonization and taxon cycling in this fauna. A. lanipes had a star phylogeny, low mean pairwise nucleotide differences and recent (Holocene) estimates for an in situ population expansion in Puerto Rico, and it was inferred as an early stage species in the taxon cycle undergoing a secondary phase of expansion. All other species were inferred as late stage species undergoing regional population expansions, as their mean pairwise nucleotide differences were relatively high and phylogenetic patterns were more complex than A. lanipes . High rates of gene flow without isolation by distance among rivers were detected in all species, although results should be treated cautiously as some populations are unlikely to be in mutation–drift equilibrium. Nested clade analysis produced inconsistent results among species that all have high rates of gene flow and expanding populations.

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Impact of canal development on intertidal microalgal productivity: Comparative assessment of Patterson Lakes and Ralphs Bay, South East Australia - S. S. Cook; J. L. Roberts; G. M. Hallegraeff; A. McMinn (Journal of Coastal Conservation, 2007)

Len Muscatine (1932–2007) and his contributions to the understanding of algal-invertebrate endosymbiosis - O. Hoegh-Guldberg; G. Muller-Parker; C. B. Cook; R. D. Gates; E. Gladfelter; R. K. Trench; V. M. Weis (Coral Reefs, 2007)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Tellurides from Sunrise Dam gold deposit, Yilgarn Craton, Western Australia: a new occurrence of nagyágite - Y.-H. Sung; C. L. Ciobanu; A. Pring; J. Brügger; W. Skinner; N. J. Cook; M. Nugus (Mineralogy and Petrology, 2007)

Segmented Frequency-domain Fluorescence Lifetime Measurements: Minimizing the Effects of Photobleaching Within a Multi-component System - Hadi M. Marwani; Mark Lowry; Patrick Keating; Isiah M. Warner; Robert L. Cook (Journal of Fluorescence, 2007)

Survivorship, growth and reproduction of the non-native Caprella mutica Schurin, 1935 (Crustacea: Amphipoda) - Elizabeth J. Cook; Kate J. Willis; M. Lozano-Fernandez (Hydrobiologia, 2007)

Benthic solute exchange and carbon mineralization in two shallow subtidal sandy sediments: Effect of advective pore‐water exchange - Perran L. M. Cook; Frank Wenzhöfer; Ronnie N. Glud; Felix Janssen; Markus Huettel (Limnology and Oceanography, 2007)
We conducted four field campaigns to evaluate benthic O 2 consumption and the effect of advective pore‐water flow in nearshore permeable sediments in the North Sea and Baltic Sea. Advective pore‐water transport had a marked effect on the benthic exchange of O 2 and TCO 2 in benthic chamber incubations, with the rates of exchange increasing by a factor of up to 2.5 when imposing flushing rates of 100‐300 L m −2 d −1 , compared to settings with diffusive exchange only. Estimates of in situ exchange rates using oxygen penetration and volumetric O 2 consumption and TCO 2 production rates were within the range measured in the chambers. The contribution of advection to solute exchange was highly variable and dependent on sediment topography. Advective processes also had a pronounced influence on the in situ distribution of O 2 within the sediment, with characteristic two‐dimensional patterns of O 2 distribution across ripples, and also deep subsurface O 2 pools, being observed. Mineralization pathways were predominantly aerobic when benthic mineralization rates were low and advective pore‐water flow high as a result of well‐developed sediment topography. By contrast, mineralization proceeded predominantly through sulfate reduction when benthic mineralization rates were high and advective pore‐water flow low as a result of poorly developed topography. Previous studies of benthic mineralization in shallow sandy sediments have generally ignored these dynamics and, hence, have overlooked crucial aspects of permeable sediment function in coastal ecosystems.

Responses of Phradis parasitoids to volatiles of lavender, Lavendula angustifolia—a possible repellent for their host, Meligethes aeneus - Samantha M. Cook; Martin Jönsson; Matthew P. Skellern; Darren A. Murray; Peter Anderson; Wilf Powell (BioControl, 2007)

Effects of a plant parasitic nematode (Heterodera trifolii) on clover roots and soil microbial communities - Amy M. Treonis; Roger Cook; Lorna Dawson; Susan J. Grayston; Tony Mizen (Biology and Fertility of Soils, 2007)

Isolation of viral haemorrhagic septicaemia virus from mummichog, stickleback, striped bass and brown trout in eastern Canada - N Gagné; A‐M MacKinnon; L Boston; B Souter; M Cook‐Versloot; S Griffiths; G Olivier (Journal of Fish Diseases, 2007)
Viral haemorrhagic septicaemia virus (VHSV) was isolated from mortalities occurring in populations of mummichog, Fundulus heteroclitus , stickleback, Gasterosteus aculeatus aculeatus , brown trout, Salmo trutta , and striped bass, Morone saxatilis , in New Brunswick and Nova Scotia, Canada. The isolated viral strains produced a cytopathic effect on the epithelioma papillosum cyprini cell line. Serum neutralization indicated the virus was VHSV and sequencing identified the rhabdovirus isolates as the North American strain of VHSV. Phylogenetic analysis indicated that the isolates are closely related and form a distinguishable subgroup of North American type VHSV. To our knowledge, this is the first report of VHSV in mummichog and striped bass.

Behavioural and chemical ecology underlying the success of turnip rape (Brassica rapa) trap crops in protecting oilseed rape (Brassica napus) from the pollen beetle (Meligethes aeneus) - S. M. Cook; H. B. Rasmussen; M. A. Birkett; D. A. Murray; B. J. Pye; N. P. Watts; I. H. Williams (Arthropod-Plant Interactions, 2007)

Allelic and haplotypic diversity at the major histocompatibility class II within domesticated Australian Atlantic salmon ( Salmo salar L.) - J. W. Wynne; M. T. Cook; B. H. Holmes; N. G. Elliott (Journal of Fish Biology, 2007)
Variation within the major histocompatibility (MH) class II alpha gene ( Sasa‐DAA ) was compared between domesticated Australian Atlantic salmon and their ancestral Canadian population. The level of Sasa‐DAA and MH class II beta gene ( Sasa‐DAB ) sequence variation was also examined within the Australian population and compared with that published for European Atlantic salmon populations. In contrast to variation previously reported for non‐coding microsatellite loci, a high level of MH class II allelic variation has been maintained within the domesticated Australian populations. Furthermore, a high level of Sasa‐DAA and Sasa‐DAB allele sequence diversity was also observed and exceeded that reported for other cultured Atlantic salmon populations. The number of Sasa‐DAB allele sequences (14) surpassed the number of Sasa‐DAA allele sequences (9) to produce 14 unique class II haplotypes. We conclude that the Australian Atlantic salmon populations show high MH class II allelic and haplotypic variation compared with both its ancestral Canadian population and other cultured Atlantic salmon populations.

Bacterial community shifts in organically perturbed sediments - Andrew Bissett; Chris Burke; Perran L. M. Cook; John P. Bowman (Environmental Microbiology, 2007)
Summary Bacterial abundance, diversity and sediment function were investigated in organically perturbed sediments under Tasmanian salmon ( Salmo salar ) farms and adjacent reference sites. Bacterial numbers increased as farming and organic loading progressed through the farm stocking cycle and declined during the fallow period, although not to prestocking levels. Bacterial numbers ranged between approximately 2 × 10 8 and 3 × 10 9 cells per gram of sediment and were higher at cage sites than reference sites. Microelectrode and respiration data also demonstrated a clear effect of organic loading on sediments. Denaturing gradient gel electrophoresis (DGGE) showed that bacterial communities shifted both in response to farm loading and its cessation. A seasonal effect on microbial communities was also evident. Although bacterial communities did shift again during the fallowing period, this shift was not necessarily a return to preloading communities. The complexity of community shifts may be affected by the vast functional redundancy of bacterial groups. All bacterial communities, including those at reference sites, were highly dynamic. Respiration studies of amended sediments indicated that fish farm sediments were at least as resilient and diverse as reference site communities. The results of this study indicate that the functional redundancy of highly complex bacterial communities contributes to their robustness. The relationship between diversity and stability in bacterial communities remains unclear and requires further investigation before an understanding of bacterial response to perturbation is possible.

Analysis of referrals to a multi-disciplinary breast cancer genetics clinic: practical and economic considerations - Marta M. Reis; Dorothy Young; Lorna McLeish; David Goudie; Alan Cook; Frank Sullivan; Helen Vysny; Alison Fordyce; Roger Black; Manouche Tavakoli; Michael Steel (Familial Cancer, 2006)

Thermal tolerance of a northern population of striped bass Morone saxatilis - A. M. Cook; J. Duston; R. G. Bradford (Journal of Fish Biology, 2006)
Thermal tolerance of age 0+ year Shubenacadie River (Nova Scotia, Canada) striped bass Morone saxatilis juveniles (mean ± s . e . fork length, L F , 19·2 ± 0·2 cm) acclimated in fresh water to six temperatures from 5 to 30° C was measured by both the incipient lethal technique (72 h assay), and the critical thermal method ( C m ). The lower incipient lethal temperature ranged from 2·4 to 11·3° C, and the upper incipient lethal temperature ( I U ) from 24·4 to 33·9° C. The area of thermal tolerance was 618° C 2 . In a separate experiment, the I U of large age 2+ year fish (34·4 ± 0·5 cm L F ) was 1·2 and 0·6° C lower ( P L F ) at acclimation temperatures of 16 and 23° C. Using the C m , loss of equilibrium occurred at 27·4–37·7° C, loss of righting response at 28·1–38·4° C and onset of spasms at 28·5–38·8° C, depending on acclimation temperature. The linear regression slopes for these three responses were statistically similar (0·41; P > 0·05), but the intercepts differed (25·3, 26·0 and 26·5° C; P

Populations of Myriophyllum alterniflorum L. as bioindicators of pollution in acidic to neutral rivers in the Limousin region - P. Chatenet; D. Froissard; J. Cook-Moreau; P. Hourdin; A. Ghestem; M Botineau; J. Haury (Hydrobiologia, 2006)

Millennia‐long tree‐ring records from Tasmania and New Zealand: a basis for modelling climate variability and forcing, past, present and future - Edward R. Cook; Brendan M. Buckley; Jonathan G. Palmer; Pavla Fenwick; Michael J. Peterson; Gretel Boswijk; Anthony Fowler (Journal of Quaternary Science, 2006)
Progress in the development of millennia‐long tree‐ring chronologies from Australia and New Zealand is reviewed from the perspective of modelling long‐term climate variability there. Three tree species have proved successful in this regard: Huon pine ( Lagarostrobos franklinii ) from Tasmania, silver pine ( L. colensoi ) from the South Island of New Zealand, and kauri ( Agathis australis ) from the North Island of New Zealand. Each of these species is very long‐lived and produces abundant quantities of well‐preserved wood for extending their tree‐ring chronologies back several millennia into the past. The growth patterns on these chronologies strongly correlate with both local and regional warm‐season temperature changes over significant areas of the Southern Hemisphere (especially Huon and silver pine) and to ENSO variability emanating from the equatorial Pacific region (especially kauri). In addition, there is evidence for significant, band‐limited, multi‐decadal and centennial timescale variability in the warm‐season temperature reconstruction based on Huon pine tree rings that may be related to slowly varying changes in ocean circulation dynamics in the southern Indian Ocean. This suggests the possibility of long‐term climate predictability there. Copyright © 2006 John Wiley & Sons, Ltd.

Measures of preferred direction for environmental and ecological circular data - B. Sango Otieno; Christine M. Anderson-Cook (Environmental and Ecological Statistics, 2006)

Enhanced sucrose pellet consumption induced by benzodiazepine-type drugs in squirrel monkeys: role of GABAA receptor subtypes - Angela N. Duke; Donna M. Platt; James M. Cook; Shengming Huang; Wenyuan Yin; Bruce A. Mattingly; James K. Rowlett (Psychopharmacology, 2006)

Evidence of an oscillating peripheral clock in an equine fibroblast cell line and adipose tissue but not in peripheral blood - Barbara A. Murphy; Mandi M. Vick; Dawn R. Sessions; R. Frank Cook; Barry P. Fitzgerald (Journal of Comparative Physiology A, 2006)

N-Acetyltaurine dissimilated via taurine by Delftia acidovorans NAT - Jutta Mayer; Karin Denger; Theo H. M. Smits; Klaus Hollemeyer; Ulrich Groth; Alasdair M. Cook (Archives of Microbiology, 2006)

Advective relief of CO 2 limitation in microphytobenthos in highly productive sandy sediments - Perran L. M. Cook; Hans Røy (Limnology and Oceanography, 2006)
Following field observations of increased photosynthesis at increased rates of sediment flushing in sandy sediments, we conducted a series of laboratory experiments to elucidate the mechanism behind these observations. Column experiments in which water was pumped though sand at rates ranging from 0 to 613 L m −2 d −1 showed that carbon (C) fixation, as measured using carbon‐14 ( 14 C) incorporation, increased from 6.4 to 8.6 mmol m −2 h −1 with increasing rates of flushing. Bottle incubations showed that the addition of inorganic nutrients [ammonium ion (NH 4 + ), inorganic phosphate (HPO 4 − ), silicic acid Si(OH) 4 ] did not stimulate C fixation over short‐term incubations. Microprofiles of pH showed that the pH within the photic zone increased to 8.9, reducing free carbon dioxide (CO 2 ) concentrations to ~0.5 µmol L −1 . Further bottle incubations, where pH and total inorganic carbon (TCO 2 ) were manipulated, showed that high pH (9.6) did not affect photosynthesis if free CO 2 was present at concentrations of 10 µmol L −1 , suggesting a direct effect of low free CO 2 concentrations. 14 C fixation profiles at a resolution of 100 µm recorded by b‐radiation imaging showed that while the depth specific maximum rates of C fixation were the same under both diffusive and advective (flushed) conditions, the integrated rates of photosynthesis were highest under flushed conditions because of a thickening of the photosynthetic zone. We conclude that advective pore‐water transport can enhance benthic photosynthesis in shallow permeable sand sediments by counteracting CO 2 limitation.

Fire Frequency and Mosaic Burning Effects on a Tallgrass Prairie Ground Beetle Assemblage - William M. Cook; Robert D. Holt (Biodiversity and Conservation, 2006)

Inducible transcription of genes involved in taurine uptake and dissimilation by Silicibacter pomeroyi DSS-3T - Andzelika K. Gorzynska; Karin Denger; Alasdair M. Cook; Theo H. M. Smits (Archives of Microbiology, 2006)

Rapid development of polyclonal antisera against infectious salmon anaemia virus and its optimization and application as a diagnostic tool - S J McBeath; L M Ellis; P F Cook; L Wilson; K L Urquhart; I R Bricknell (Journal of Fish Diseases, 2006)
Infectious salmon anaemia is an important disease of Atlantic salmon. One of the current methods of diagnosis is the indirect fluorescent antibody test (IFAT), using a monoclonal antibody specific to the haemagglutinin of the virus. The conformationally dependent nature of this antibody could be a drawback in its usefulness in other tests. This study describes the development and optimization of a polyclonal antiserum against infectious salmon anaemia virus, including a method of separating virus from cell culture components within culture supernatant. The antiserum was subsequently optimized for use in a variety of immunological diagnostic tests, including IFAT and an alkaline phosphatase‐based immunoassay, and Western blot.

Biogeographic history of an Australian freshwater shrimp, Paratya australiensis (Atyidae): the role life history transition in phylogeographic diversification - B. D. COOK; A. M. BAKER; T. J. PAGE; S. C. GRANT; J. H. FAWCETT; D. A. HURWOOD; J. M. HUGHES (Molecular Ecology, 2006)
The widespread distribution of the freshwater shrimp Paratya australiensis in eastern Australia suggests that populations of this species have been connected in the past. Amphidromy is ancestral in these shrimps, although many extant populations are known to be restricted to freshwater habitats. In this study, we used a fragment of the cytochrome c oxidase I mitochondrial DNA (mtDNA) gene to examine diversity within P. australiensis and to assess the relative importance of amphidromy in its evolutionary history. We hypothesized that if transitions from an amphidromous to a freshwater life history were important, then we would find a number of divergent lineages restricted to single or groups of nearby drainages. Alternatively, if amphidromy was maintained within the species historically, we expected to find lineages distributed over many drainages. We assumed that the only way for divergence to occur within amphidromous lineages was if dispersal was limited to between nearby estuaries, which, during arid periods in the earth's history, became isolated from one another. We found nine highly divergent mtDNA lineages, estimated to have diverged from one another in the late Miocene/early Pliocene, when the climate was more arid than at present. Despite this, the geographic distribution of lineages and haplotypes within lineages did not support the notion of a stepping‐stone model of dispersal between estuaries. We conclude that the extensive divergence has most likely arisen through a number of independent amphidromy–freshwater life history transitions, rather than via historical isolation of amphidromy populations. We also found evidence for extensive movement between coastal and inland drainages, supporting the notion that secondary contact between lineages may have occurred as a result of drainage rearrangements. Finally, our data indicate that P. australiensis is likely a complex of cryptic species, some of which are widely distributed, and others geographically restricted.

Effects of combining ethanol (EtOH) with gamma-hydroxybutyrate (GHB) on the discriminative stimulus, locomotor, and motor-impairing functions of GHB in mice - Charles D. Cook; Laura Biddlestone; Andrew Coop; Patrick M. Beardsley (Psychopharmacology, 2006)

Dissimilation of C3-sulfonates - Alasdair M. Cook; Karin Denger; Theo H. M. Smits (Archives of Microbiology, 2006)

Bactericidal effects of plasma-generated cluster ions - I. Digel; A. Temiz Artmann; K. Nishikawa; M. Cook; E. Kurulgan; G. M. Artmann (Medical & Biological Engineering & Computing, 2005)

Interaction between inflammation-related gene polymorphisms and cigarette smoking on the risk of myocardial infarction in the Physician’s Health Study - Sarah A. Rosner; Paul M. Ridker; Robert Y. L. Zee; Nancy R. Cook (Human Genetics, 2005)

Cyanobacterial blooms and water quality in Greek waterbodies - Elizabeth Vardaka; Maria Moustaka-Gouni; Catherine M. Cook; Tom Lanaras (Journal of Applied Phycology, 2005)

Temporal resolution of the Florida manatee (Trichechus manatus latirostris) auditory system - David A. Mann; Debborah E. Colbert; Joseph C. Gaspard; Brandon M. Casper; Mandy L. H. Cook; Roger L. Reep; Gordon B. Bauer (Journal of Comparative Physiology A, 2005)

ω-Oxygenation of the alkyl sidechain of linear alkylbenzenesulfonate (LAS) surfactant in Parvibaculum lavamentivorans T - David Schleheck; Alasdair M. Cook (Archives of Microbiology, 2005)

Isethionate as a product from taurine during nitrogen-limited growth of Klebsiella oxytoca TauN1 - Katharina Styp von Rekowski; Karin Denger; Alasdair M. Cook (Archives of Microbiology, 2005)

Bidirectional effects of benzodiazepine binding site ligands on active avoidance acquisition and retention: differential antagonism by flumazenil and β-CCt - Miroslav M. Savić; Dragan I. Obradović; Nenad D. Ugrešić; James M. Cook; P. V. V. S. Sarma; Dubravko R. Bokonjić (Psychopharmacology, 2005)

Variation in ITGB3 has sex-specific associations with plasma lipoprotein(a) and whole blood serotonin levels in a population-based sample - Lauren A. Weiss; Mark Abney; Rodney Parry; Angelo M. Scanu; Edwin H. Cook; Carole Ober (Human Genetics, 2005)

The North Atlantic Oscillation and regional phenology prediction over Europe - Benjamin I. Cook; Thomas M. Smith; Michael E. Mann (Global Change Biology, 2005)
We present an integrated modeling study designed to investigate changes in ecosystem level phenology over Europe associated with changes in climate pattern, by the North Atlantic Oscillation (NAO). We derived onset dates from processed NDVI data sets and used growing degree day (GDD) summations from the NCEP re‐analysis to calibrate and validate a phenology model to predict the onset of the growing season over Europe. In a cross‐validation hindcast, the model (PHENOM) is able to explain 63% of the variance in onset date for grid cells containing at least 50% mixed and boreal forest. Using a model developed from previous work we performed climate change scenarios, generating synthetic temperature and GDD distributions under a hypothetically increasing NAO. These new distributions were used to drive PHENOM and project changes in the timing of onset for forested cells over Europe. Results from the climate change scenarios indicate that, if the current trend in the NAO continues, there is the potential for a continued advance to the start of the growing season by as much as 13 days in some areas.

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)

Postglacial expansion of the southern red‐backed vole ( Clethrionomys gapperi ) in North America - AMY M. RUNCK; JOSEPH A. COOK (Molecular Ecology, 2005)
Dynamic climatic oscillations of the Pleistocene dramatically changed the distributions of high latitude species. Molecular investigations of a variety of organisms show that processes of postglacial colonization of boreal regions were more complex than initially thought. Phylogeographical and coalescent analyses were conducted on partial sequences of the cytochrome b gene (600 bp) from 64 individuals of Clethrionomys gapperi from North Carolina, Pennsylvania, Minnesota, Idaho, Washington, British Columbia, Northwest Territories, and Alaska to test hypotheses relating to Pleistocene refugia and postglacial colonization routes. Three divergent clades (east, west, central) were identified with highest net divergence ( d A = 5.2%) between the eastern and western clades. Populations from the recently deglaciated higher latitudes of Canada and Alaska are closely related to lower latitude populations of the central clade ( d A = 1.2%) suggesting recent expansion from this midwestern region. No representatives from the east or west clade were found at latitudes higher than 50°N, indicating that postglacial colonization occurred through a midcontinental route. The high latitude population from the Northwest Territories exhibited demographic patterns and genetic diversity consistent with a stable noncolonizing population. This population is found near the Mackenzie range, where the two continental ice sheets were believed to have coalesced. Molecular variation observed in this population may be the result of leading edge population diversifying in the continental corridor or may reflect the signal of a high latitude refugial population.

Historical transoceanic dispersal of a freshwater shrimp: the colonization of the South Pacific by the genus Paratya (Atyidae) - Timothy J. Page; Andrew M. Baker; Benjamin D. Cook; Jane M. Hughes (Journal of Biogeography, 2005)
Aim To infer the phylogenetic relationships within the freshwater shrimp genus Paratya Miers, 1882 (Atyidae) and to use these data to answer biogeographical questions about the location, timing and form of evolution of this genus in the South Pacific. Location Paratya are spread throughout various freshwater habitats in the western Pacific, with a disjunct northern range in the North Pacific (Japan, Korea, Ryukyu Islands, Siberia) and South Pacific (Australia, New Zealand, New Caledonia, Lord Howe, Norfolk Island). Methods Specimens were obtained from throughout its range. Mitochondrial sequences of cytochrome oxidase subunit I and 16S ribosomal DNA were analysed using phylogenetic techniques to identify whether landmasses are monophyletic and what the relationships are between landmasses. Molecular clock dating methods were used to date divergences between taxa. Results Each landmass was recovered as monophyletic. Japan/Ryukyu Islands is the most basal group, followed by New Zealand. Australian specimens form a sister group to a clade made up of two groups (New Caledonia and Lord Howe/Norfolk Island). The oldest divergence within the genus (between North and South Pacific) took place 12 –19 Ma. Main conclusions The geographical origin of the genus (either Gondwana or Laurasia) is unclear. Dispersal occurred between the North and South Pacific long after the split up of Gondwana. Dispersal likely explains the presence of Paratya on each landmass in the South Pacific, from continent to isolated oceanic island. This dispersal is conjectured to have taken place through oceanic currents because of the amphidromous life cycle of some taxa of Paratya , given that amphyidromy is plesiomorphic in atyid shrimp.

Effect of a turnip rape (Brassica rapa) trap crop on stem-mining pests and their parasitoids in winter oilseed rape (Brassica napus) - Hassan Barari; Samantha M. Cook; Suzanne J. Clark; Ingrid H. Williams (BioControl, 2005)

Protocatechuate 4,5-dioxygenase from Comamonas testosteroni T-2: biochemical and molecular properties of a new subgroup within class III of extradiol dioxygenases - Jrg Mampel; Miguel A. Providenti; Alasdair M. Cook (Archives of Microbiology, 2005)

Field-Scale Experiments for Site-Specific Crop Management. Part II: A Geostatistical Analysis - M. J. Pringle; A. B. McBratney; S. E. Cook (Precision Agriculture, 2004)

Field-Scale Experiments for Site-Specific Crop Management. Part I: Design Considerations - M. J. Pringle; S. E. Cook; A. B. McBratney (Precision Agriculture, 2004)

Body Mass Index and Risk of Colorectal Cancer in Women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2004)

Development of Selective Ligands for Benzodiazepine Receptor Subtypes by Manipulating the Substituents at Positions 3- and 7- of Optically Active BzR Ligands - Xiaoyan Li; Jianming Yu; John R. Atack; James M. Cook (Medicinal Chemistry Research, 2004)

Isolation and Characterization of Arsenate-Reducing Bacteria from Arsenic-Contaminated Sites in New Zealand - Craig R. Anderson; Gregory M. Cook (Current Microbiology, 2004)

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

GABAA/α1 receptor agonists and antagonists: effects on species-typical and heightened aggressive behavior after alcohol self-administration in mice - Rosa M. M. de Almeida; James K. Rowlett; James M. Cook; Wenyuan Yin; Klaus A. Miczek (Psychopharmacology, 2004)

Analysis of soil wetting and solute transport in subsurface trickle irrigation - Claire M. Cote; Keith L. Bristow; Philip B. Charlesworth; Freeman J. Cook; Peter J. Thorburn (Irrigation Science, 2003)

An additional regulator, TsaQ, is involved with TsaR in regulation of transport during the degradation of p -toluenesulfonate in Comamonas testosteroni T-2 - Tewes Tralau; Alasdair M. Cook; Jrgen Ruff (Archives of Microbiology, 2003)

Responses of the Aphids Phorodon humuli and Rhopalosiphum padi to Sex Pheromone Stereochemistry in the Field - Colin A. M. Campbell; Fraser J. Cook; John A. Pickett; Tom W. Pope; Lester J. Wadhams; Christine M. Woodcock (Journal of Chemical Ecology, 2003)

Amino acid transport by Sphingomonas sp. strain Ant 17 isolated from oil-contaminated Antarctic soil - Katherine Young; R. Brent Seale; Karen Olsson; Jackie Aislabie; Gregory M. Cook (Polar Biology, 2003)

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

Nitrous oxide emissions following application of residues and fertiliser under zero and conventional tillage - E.M. Baggs; M. Stevenson; M. Pihlatie; A. Regar; H. Cook; G. Cadisch (Plant and Soil, 2003)

Uptake of erythromycin by first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), fed live or freeze‐dried enriched adult Artemia or medicated pellets - M A Cook; M B Rust; K Massee; T Majack; M E Peterson (Journal of Fish Diseases, 2003)
The potential to use adult Artemia to deliver erythromycin to first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), was investigated in three trials. In the first trial, first‐feeding sockeye were fed live erythromycin enriched adult Artemia or pellets containing equal amounts of erythromycin for 35 days. At the end of the trial, tissue erythromycin concentration of the fish fed the live Artemia was significantly greater ( P μ g mL −1 ; mean ± SEM), than the tissue concentration of the fish fed the pellets (0.72 ± 0.01 μ g mL −1 ). In the second trial, first‐feeding sockeye were fed either live or freeze‐dried bioencapsulated erythromycin (adult Artemia ) or pellets containing erythromycin daily for 21 days. Mean daily erythromycin concentration in fish fed the freeze‐dried Artemia , live Artemia , or pellets did not differ significantly. In the third trial, apparent erythromycin digestibility was determined. Significantly more ( P Artemia (live or freeze‐dried) appears to be greater than uptake from pellets. Freeze‐dried and live Artemia were equally effective at delivery suggesting enriched freeze‐dried adult Artemia could be produced into a highly palatable, consistent, off‐the‐shelf product.

Holarctic phylogeography of the root vole ( Microtus oeconomus ): implications for late Quaternary biogeography of high latitudes - C. Brunhoff; K. E. Galbreath; V. B. Fedorov; J. A. Cook; M. Jaarola (Molecular Ecology, 2003)
A species‐wide phylogeographical study of the root vole ( Microtus oeconomus ) was performed using the whole 1140 base pair mitochondrial (mt) cytochrome b gene. We examined 83 specimens from 52 localities resulting in 65 unique haplotypes. Our results demonstrate that the root vole is divided into four main mtDNA phylogenetic lineages that seem to have largely allopatric distributions. Net divergence estimates (2.0–3.5%) between phylogroups, as well as relatively high nucleotide diversity estimates within phylogroups, indicate that the distinct phylogeographical structure was initiated by historical events that predated the latest glaciation. European root voles are divided into a Northern and a Central mtDNA phylogroup. The mtDNA data in concert with fossil records imply that root voles remained north of the classical refugial areas in southern Europe during the last glacial period. The currently fragmented populations in central Europe belong to a single mtDNA phylogroup. The Central Asian and the North European lineages are separated by the Ural Mountains, a phylogeographical split also found in collared lemmings ( Dicrostonyx ) and the common vole ( M. arvalis ). The Beringian lineage occurs from eastern Russia through Alaska to northwestern Canada. This distribution is congruent with the traditional boundaries of the Beringian refugium and with phylogeographical work on other organisms. In conclusion, similarities between the phylogeographical patterns in the root vole and other rodents, such as Arctic and subarctic lemmings, as well as more temperate vole species, indicate that late Quaternary geological and climatic events played a strong role in structuring northern biotic communities.

Deep Natural Gas Resources - T. S. Dyman; R. E. Wyman; V. A. Kuuskraa; M. D. Lewan; T. A. Cook (Natural Resources Research, 2003)

Saccharin as a sole source of carbon and energy for Sphingomonas xenophaga SKN - David Schleheck; Alasdair M. Cook (Archives of Microbiology, 2003)

Phylogeography of lemmings ( Lemmus ): no evidence for postglacial colonization of Arctic from the Beringian refugium - V. B. Fedorov; A. V. Goropashnaya; M. Jaarola; J. A. Cook (Molecular Ecology, 2003)
Beringia is considered as an important glacial refugium that served as the main source for colonization of formerly glaciated Arctic regions. To obtain high resolution views of Arctic refugial history, we examined mitochondrial cytochrome b phylogeography in the northern genus of rodents, Lemmus ( true lemmings), sampled across its circumpolar distribution. Strong phylogeographical structure suggests vicariant separation over several glacial–interglacial periods and does not provide evidence supporting the importance of Beringia for extensive colonization of formerly glaciated regions. Rather than a source of postglacial colonization, Beringia represents an area of intraspecific endemism previously undetected by biogeographical analysis. Existing phylogeographical structure suggests that vicariant separation by glacial barriers was an important factor generating genetic divergence and, thus, increasing genetic diversity in lemmings on continental and circumpolar scales. However, there is little evidence for the direct effect of the last glaciation on the level of genetic variation and allele genealogy in lemmings on a regional geographical scale. This finding implies that the population genetic models of postglacial colonization suggested for temperate taxa might have limited applicability for Arctic species.

A Modeling System for Studying Climate Controls on Mountain Glaciers with Application to the Patagonian Icefields - Kerry H. Cook; Xiaosong Yang; Corinne M. Carter; Brian N. Belcher (Climatic Change, 2003)

PATHOGENICITY OF CHORISTONEURA FUMIFERANA NUCLEOPOLYHEDROVIRUS PROPAGATED IN VITRO AT DIFFERENT INCUBATION TEMPERATURES - PETER M. EBLING; GUIDO F. CAPUTO; BARBARA J. COOK (In Vitro Cellular & Developmental Biology - Animal, 2003)

Estrogen–progestin replacement therapy and breast cancer risk: the Women's Health Study (United States) - Juliet V. Porch; I-Min Lee; Nancy R. Cook; Kathryn M. Rexrode; Julie E. Buring (Cancer Causes & Control, 2002)

Incidence of leukemia in Asian migrants to the United States and their descendants - Jenny W.Y. Pang; Linda S. Cook; Stephen M. Schwartz; Noel S. Weiss (Cancer Causes & Control, 2002)

An alkaline phosphatase‐based method for the detection of infectious salmon anaemia virus (ISAV) in tissue culture and tissue imprints - L Wilson; S J McBeath; K L Adamson; P F Cook; L M Ellis; I R Bricknell (Journal of Fish Diseases, 2002)
Currently, the presence of infectious salmon anaemia virus (ISAV) is often detected in Atlantic salmon by the use of an indirect fluorescent antibody test. This test is limited by the poor stability of fluorescein isothiocyanate which fades after about a week in storage, preventing the development of stained archive material as a reference source. One possible alternative would be the use of immunohistochemical staining methods to detect ISAV. An immunohistochemical method is presented that uses alkaline phosphatase‐conjugated antibodies and Vector ® Red as a substrate, to detect ISAV in kidney imprints. This paper also describes a procedure where Bouin's fluid is used to successfully inhibit endogenous alkaline phosphatase in tissue samples, prior to immunohistochemical processing. This method provides a stable stain that can be read for many weeks after staining or archived for future reference.

Island theory, matrix effects and species richness patterns in habitat fragments - William M. Cook; Kurt T Lane; Bryan L. Foster; Robert D. Holt (Ecology Letters, 2002)
Island biogeography theory, created initially to study diversity patterns on islands, is often applied to habitat fragments. A key but largely untested assumption of this application of theory is that landscape matrix species composition is non‐overlapping with that of the islands. We tested this assumption in successional old field patches in a closely mowed matrix, and because our patches are appropriately viewed as sets of contiguous habitat units we studied patterns of species richness per unit area. Previous studies at our site did not find that diversity patterns on patch ‘islands’ conformed to predictions of island biogeography theory. Our results indicate that when matrix species are removed from the patch samples, diversity patterns conform better to theory. We suggest that classical island theory remains an appropriate tool to study diversity patterns in fragmented habitats, but that allowances should be made for spill‐over colonization of ‘islands’ from the ‘sea’.

Physiological and performance effects of pyridostigmine bromide in healthy volunteers: a dose-response study - Mary R. Cook; Charles Graham; Antonio Sastre; Mary M. Gerkovich (Psychopharmacology, 2002)

Diversity, Distribution, and Ancient Taxonomic Relationships Within the TIR and Non-TIR NBS-LRR Resistance Gene Subfamilies - Steven B. Cannon; Hongyan Zhu; Andrew M. Baumgarten; Russell Spangler; Georgiana May *, , Douglas R. Cook (Journal of Molecular Evolution, 2002)

Environmental Impacts of Acid Leachate Derived from Coal-Storage Piles upon Groundwater - Angie M. Cook; Steven J. Fritz (Water, Air, & Soil Pollution, 2002)

Bioencapsulation of five forms of erythromycin by adult Artemia salina (L.) - M A Cook; M B Rust (Journal of Fish Diseases, 2002)
Uptake of five chemical forms of erythromycin by adult Artemia salina (L.) (erythromycin phosphate – EP, erythromycin stearate – ES, erythromycin estolate – EE, erythromycin hydrate – EH and crystalline erythromycin – CE) was investigated in two trials. In each trial, final erythromycin concentration in Artemia tissue and survival after a 12‐h bioencapsulation period were determined. In the first trial, Artemia tissue concentration after a 12‐h bioencapsulation period was significantly ( P −1 , mean ± SEM) ≈ EH (61.2 ± 3.4 μg mL −1 ) > CE (37.1 ± 10.7 μg mL −1 ) > EP (16.4 ± 7.7 μg mL −1 ) > control. In trial 2, Artemia tissue concentration was also significantly ( P −1 ) > CE (89.1 ± 1.7 μg mL −1 ) > ES (78.9 ± 1.6 μg mL −1 ) > EP (33.4 ± 5.2 μg mL −1 ) > control. Survival was significantly affected by erythromycin form in trial 1 with EP=control (100 ± 0.0%) > ES (74.4 ± 2.0%) > CE (32.2 ± 0.3%) > EH (8.8 ± 4.4%). In trial 2, survival was also significantly affected by erythromycin form with EP=control (100 ± 0.0%) > ES (67.1 ±3.7%) > CE (52.5 ± 7.7%) > EE (5.0 ± 2.5%). Based on both uptake and survival, EP and ES appear to be appropriate compounds for bioencapsulation of erythromycin using live adult Artemia .

Dissimilation of the C2 sulfonates - Alasdair M. Cook; Karin Denger (Archives of Microbiology, 2002)

Cocaine-like discriminative stimulus effects of novel cocaine and 3-phenyltropane analogs in the rat - Charles D. Cook; Ivy F. Carroll; Patrick M. Beardsley (Psychopharmacology, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

Colorectal cancer following tamoxifen therapy for breast cancer (United States) - Linda S. Cook; Noel S. Weiss; Nikolas Pharris-Ciurej; Stephen M. Schwartz; Emily White (Cancer Causes & Control, 2001)

Spatial variability in oviposition damage by periodical cicadas in a fragmented landscape - William M. Cook; Robert D. Holt; Jin Yao (Oecologia, 2001)

Physical activity and breast cancer risk: the Women's Health Study (United States) - I-Min Lee; Kathryn M. Rexrode; Nancy R. Cook; Charles H. Hennekens; Julie E. Buring (Cancer Causes & Control, 2001)

Molecular analysis of the genotype-phenotype relationship in factor VII deficiency - D. Millar; G. Kemball-Cook; J. McVey; E. Tuddenham; A. Mumford; G. Attock; J. Reverter; N. Lanir; L. Parapia; J. Reynaud; E. Meili; A. von Felton; et al. (Human Genetics, 2000)

Sucrose transport by the alkaliphilic, thermophilic Bacillus sp. strain TA2.A1 is dependent on a sodium gradient - C. J. Peddie; Gregory M. Cook; Hugh W. Morgan (Extremophiles, 2000)

The intracellular pH of the thermophilic bacterium Thermoanaerobacter wiegelii during growth and production of fermentation acids - Gregory M. Cook (Extremophiles, 2000)

Phytosociological analysis of restored and managed grassland habitat within an urban national park - Andrew M. Greller; Celestine Durando; Leslie F. Marcus; D. Siril A. Wijesundara; Michael D. Byer; Robert Cook; John T. Tanacredi (Urban Ecosystems, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Photochemical and Microbial Degradation of 2,4,6-Trinitrotoluene (TNT) in a Freshwater Environment - Huey-Min Hwang; L. F. Slaughter; S. M. Cook; Hua Cui (Bulletin of Environmental Contamination and Toxicology, 2000)

Purification, properties and primary structure of alanine dehydrogenase involved in taurine metabolism in the anaerobe Bilophila wadsworthia - Heike Laue; Alasdair M. Cook (Archives of Microbiology, 2000)

Photochemical and Microbial Degradation of 2,4,6-Trinitrotoluene (TNT) in a Freshwater Environment - Huey-Min Hwang; L. F. Slaughter; S. M. Cook; Hua Cui (Bulletin of Environmental Contamination and Toxicology, 2000)

Roles of respiratory oxidases in protecting Escherichia coli K12 from oxidative stress - Arne Lindqvist; Jorge Membrillo-Hernández; Robert K. Poole; Gregory M. Cook (Antonie van Leeuwenhoek, 2000)

Oxide-sulphide relationships in sodalite-bearing metasomatites of the Epembe-Swartbooisdrif Alkaline Province, north-west Namibia - V. von Seckendorff; K. Drüppel; M. Okrusch; N. J. Cook; S. Littmann (Mineralium Deposita, 2000)

Colorectal cancer incidence in Asian migrants to the United States and their descendants - Danna M. Flood; Noel S. Weiss; Linda S. Cook; Julia C. Emerson; Stephen M. Schwartz; John D. Potter (Cancer Causes & Control, 2000)

Seasonal soil‐surface carbon fluxes from the root systems of young Pinus radiata trees growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; Freeman J. Cook; David Whitehead; John A. Adams (Global Change Biology, 2000)
Summary Elevated atmospheric CO 2 concentration may result in increased below‐ground carbon allocation by trees, thereby altering soil carbon cycling. Seasonal estimates of soil surface carbon flux were made to determine whether carbon losses from Pinus radiata trees growing at elevated CO 2 concentration were higher than those at ambient CO 2 concentration, and whether this was related to increased fine root growth. Monthly soil surface carbon flux density ( f ) measurements were made on plots with trees growing at ambient (350) and elevated (650 μmol mol −1 ) CO 2 concentration in large open‐top chambers. Prior to planting the soil carbon concentration (0.1%) and f (0.28 μmol m −2 s −1 at 15 °C) were low. A function describing the radial pattern of f with distance from tree stems was used to estimate the annual carbon flux from tree plots. Seasonal estimates of fine root production were made from minirhizotrons and the radial distribution of roots compared with radial measurements of f . A one‐dimensional gas diffusion model was used to estimate f from soil CO 2 concentrations at four depths. For the second year of growth, the annual carbon flux from the plots was 1671 g y −1 and 1895 g y −1 at ambient and elevated CO 2 concentrations, respectively, although this was not a significant difference. Higher f at elevated CO 2 concentration was largely explained by increased fine root biomass. Fine root biomass and stem production were both positively related to f. Both root length density and f declined exponentially with distance from the stem, and had similar length scales. Diurnal changes in f were largely explained by changes in soil temperature at a depth of 0.05 m. Ignoring the change of f with increasing distance from tree stems when scaling to a unit ground area basis from measurements with individual trees could result in under‐ or overestimates of soil‐surface carbon fluxes, especially in young stands when fine roots are unevenly distributed.

Warm-season temperatures since 1600 BC reconstructed from Tasmanian tree rings and their relationship to large-scale sea surface temperature anomalies - E. R. Cook; B. M. Buckley; R. D. D'Arrigo; M. J. Peterson (Climate Dynamics, 2000)

The activity of the H + -monocarboxylate cotransporter during pre-implantation development in the mouse - E. A. Harding; M. L. Day; C. A. Gibb; M. H. Johnson; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1999)

Sex allocation and local mate competition in Old World non-pollinating fig wasps - Mark D. E. Fellowes; Steve G. Compton; James M. Cook (Behavioral Ecology and Sociobiology, 1999)

Use of replication-deficient adenoviruses to study signal transduction pathways. Muscarinic responses in HSG and HT29 epithelial cell lines are mediated by G protein βγ-subunits - P. Poronnik; L. M. O'Mullane; A. D. Conigrave; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1999)

Nitric oxide donors, sodium nitroprusside and S-nitroso-N-acetylpenicillamine, stimulate myoblast proliferation in vitro - J. A. Ulibarri; P. E. Mozdziak; E. Schultz; C. Cook; T. M. Best (In Vitro Cellular & Developmental Biology - Animal, 1999)

Three new species of Apheviderulix gen. nov. and proposal of Apheviderulicidae fam. nov. (Acari: Hydrachnidia: Eylaoidea) - Reinhard Gerecke; Ian M. Smith; David R. Cook (Hydrobiologia, 1999)

The incidence of gastric carcinoma in Asian migrants to the United States and their descendants - Aruna Kamineni; Michelle A. Williams; Stephen M. Schwartz; Linda S. Cook; Noel S. Weiss (Cancer Causes & Control, 1999)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Mineralogy and textural relationships among sulphosalts and related minerals in the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - N. J. Cook; P. G. Spry; F. M. Vokes (Mineralium Deposita, 1998)

Thermobarometry of the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - J. L. Rosenberg; P. G. Spry; C. E. Jacobson; N. J. Cook; F. M. Vokes (Mineralium Deposita, 1998)

Wolbachia in two insect host–parasitoid communities - S. A. WEST; J. M. COOK; J. H. WERREN; H. C. J. GODFRAY (Molecular Ecology, 1998)
Wolbachia form a group of intracellular bacteria that alter reproduction in their arthropod hosts. Two major phylogenetic subdivisions (A and B) of Wolbachia occur. Using a polymerase chain reaction assay we surveyed for the A and B group Wolbachia in 82 insect species from two temperate host–parasitoid communities (food webs) and a general collection of Lepidoptera caught at a light trap. One host–parasitoid community was based around leaf‐mining Lepidoptera, and the other around Aphids. We found that: (i) 22.0% of insects sampled were infected with Wolbachia ; and (ii) the prevalence and type (A or B) of Wolbachia infection differed significantly between communities and taxonomic groups. We obtained DNA sequences from the ftsZ gene for the group B Wolbachia found in six leaf‐mining species and one of their parasitoids, as well as four of the Lepidoptera caught by a light trap. Taken together, the results of our survey and phylogenetic analyses of the sequence data suggest that host–parasitoid transfer of Wolbachia is not the major route through which the species we have examined become infected. In addition, the Wolbachia strains observed in five leaf‐mining species from the same genus were not closely related, indicating that transfer between species has not occurred due to a shared feeding niche or cospeciation.

Cell cycle regulation of a T-type calcium current in early mouse embryos - M. L. Day; M. H. Johnson; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1998)

Multiple independent formations of Tragopogon tetraploids (Asteraceae): evidence from RAPD markers - L. M. COOK; P. S. SOLTIS; S. J. BRUNSFELD; D. E. SOLTIS (Molecular Ecology, 1998)
Polyploidy is widely recognized as a significant force leading to the formation of new plant species. Estimates of the number of angiosperm species with polyploid origins are as high as ≈ 50%; however, in spite of this prevalence, many aspects of polyploid evolution remain poorly understood. Recent studies have suggested that recurrent origins of polyploid species are the rule rather than the exception. The present study is one of only a few designed to quantify the number of independent origins of a polyploid species. The two tetraploid species Tragopogon mirus and T . miscellus (Asteraceae) arose within the past 50 years in the Palouse region of eastern Washington and adjacent northern Idaho. Previous work using morphology, cpDNA and rDNA restriction site analyses, allozymes, cytology, and flavonoid chemistry established that T . mirus had arisen at least five times, and T . miscellus at least twice, on the Palouse. To assess the frequency of multiple origins of these species more rigorously, seven populations of T . mirus and three populations of T . miscellus that were indistinguishable based on previous markers were surveyed using random amplified polymorphic DNA (RAPD) markers; populations of the diploid progenitor species from the same sites were also analysed. Each tetraploid population had a unique RAPD marker profile, suggesting that each population surveyed originated independently of the other populations in the region. Only two of the tetraploid populations combined the RAPD marker profiles of the diploid progenitors occurring at the same site. Both polyploid species, whose ranges and numbers have greatly increased since their formation in the early part of the twentieth century, have formed repeatedly on a local geographical scale and during a short time frame. Furthermore, each tetraploid species is spreading not primarily by dispersal of propagules from a single population of origin, but through repeated, independent polyploidization events that recreate the polyploid taxa.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Evidence of deep circulation in two perennially ice‐covered Antarctic lakes - Scott W. Tyler; Peter G. Cook; Anya Z. Butt; James M. Thomas; Peter T. Doran; W. Berry Lyons (Limnology and Oceanography, 1998)
The perennial ice covers found on many of the lakes in the McMurdo Dry Valley region of the Antarctic have been postulated to severely limit mixing and convective turnover of these unique lakes. In this work, we utilize chlorofluorocarbon (CFC) concentration profiles from Lakes Hoare and Fryxell in the McMurdo Dry Valley to determine the extent of deep vertical mixing occurring over the last 50 years. Near the ice‐water interface, CFC concentrations in both lakes were well above saturation, in accordance with atmospheric gas supersaturations resulting from freezing under the perennial ice covers. Evidence of mixing throughout the water column at Lake Hoare was confirmed by the presence of CFCs throughout the water column and suggests vertical mixing times of 20–30 years. In Lake Fryxell, CFC‐11, CFC‐12, and CFC‐113 were found in the upper water column; however, degradation of CFC‐ 11 and CFC‐ 12 in the anoxic bottom waters appears to be occurring with CFC‐ 113 only present in these bottom waters. The presence of CFC‐113 in the bottom waters, in conjunction with previous work detecting tritium in these waters, strongly argues for the presence of convective mixing in Lake Fryxell. The evidence for deep mixing in these lakes may be an important, yet overlooked, phenomenon in the limnology of perennially icecovered lakes.

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

Cytokinesis and nodal anatomy in the charophycean green alga Chara zeylanica - M. E. Cook; L. E. Graham; C. A. Lavin (Protoplasma, 1998)

The effects of high-intensity intermittent exercise on the plasma concentrations of glutamine and organic acids - N. P. Walsh; A. K. Blannin; A. M. Clark; L. Cook; P. J. Robson; M. Gleeson (European Journal of Applied Physiology, 1998)

Axon guidance and somites - David Tannahill; Geoff M. W. Cook; Roger J. Keynes (Cell and Tissue Research, 1998)

Homology modelling of the catalytic domain of early mammalian protein C: evolution of structural features - A. I. Wacey; M. Krawczak; G. Kemball-Cook; D. N. Cooper (Human Genetics, 1997)

Axon guidance and somites - David Tannahill; Geoff M. W. Cook; Roger J. Keynes (Cell and Tissue Research, 1997)

Thiosulfate as a metabolic product: the bacterial fermentation of taurine - Karin Denger; Heike Laue; A. M. Cook (Archives of Microbiology, 1997)

Fermentation of cysteate by a sulfate-reducing bacterium - Heike Laue; Karin Denger; A. M. Cook (Archives of Microbiology, 1997)

The mouse urate oxidase gene, Uox, maps to distal Chromosome 3 - S. Cook; K. Johnson; M. Davisson (Mammalian Genome, 1997)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

A CHANGING TEMPERATURE RESPONSE WITH ELEVATION FOR LAGAROSTROBOS FRANKLINII IN TASMANIA, AUSTRALIA - B. M. BUCKLEY; E. R. COOK; M. J. PETERSON; M. BARBETTI (Climatic Change, 1997)

Geographic and ecological patterns in Turkish land snails - L. M. Cook (Journal of Biogeography, 1997)
The distribution of Turkish land snails has been examined, using data from a monograph by H. Schütt (1993). Turkey has been divided into eight regions for purposes of describing localization of fauna. On average, species occupy 1.7 regions. About 36% of the fauna is known from Turkey alone. There are affinities with Europe, the Caucasus, the eastern Mediterranean and the Levant and Middle East. The influence of neighbouring faunas shows up when the similarities of the eight regions are clustered. As usual, the fauna contains a high spired and a discoidal mode of shell shape, with species covering a wide range of sizes. Clausiliacea occupy a higher mode than other high spired species, while Helicacea become progressively more equidimensional from small to large species. The pattern of shell size and shape varies between regions, smaller and high spired species being most common in cooler and damper parts, larger discoidal species in parts with Mediterranean or continental dry climates. A test for evidence that animals of the same shape and size are more likely to be allopatric than sympatric failed to show that they were. The fauna is dominated by a few families to a greater extent than that of Europe, and is more like that of the isolated Madeiran archipelago. It is suggested that the Turkish fauna still shows evidence of external penetration with some local radiation, in the manner of the oceanic islands, and has not evolved to become a balanced assemblage such as is seen in Europe.

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

Assimilation of sulfur from alkyl- and arylsulfonates by Clostridium spp. - Karin Denger; A. M. Cook (Archives of Microbiology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Concentrations of Cu, Growth, and Chlorophyll Content of Field-Cultivated Wheat Growing in Naturally Enriched Cu Soil - C. M. Cook; E. Vardaka; T. Lanaras (Bulletin of Environmental Contamination and Toxicology, 1997)

Effects of vibration frequency and postural changes on human responses to seated whole-body vibration exposure - C. L. Zimmermann; Thomas M. Cook (International Archives of Occupational and Environmental Health, 1997)

Regional differences in the regulation of intracellular sodium and in action potential configuration in rabbit left ventricle - S. J. Cook; J. P. Chamunorwa; M. K. Lancaster; S. C. O'Neill (Pflügers Archiv - European Journal of Physiology, 1997)

Purification of two isofunctional hydrolases (EC 3.7.1.8) in the degradative pathway for dibenzofuran inSphingomonas sp. strain RW1 - Patricia V. Bnz; Rocco Falchetto; Alasdair M. Cook (Biodegradation, 1993)

Purification of ribulose 1,5-bisphosphate carboxylase/oxygenase and of carboxysomes from Thiobacillus thyasiris the putative symbiont of Thyasira flexuosa (Montagu) - Tom Lanaras; Catherine M. Cook; Ann P. Wood; Don P. Kelly; Geoffrey A. Codd (Archives of Microbiology, 1991)

Effect of in ovo bursectomy on the course of an infectious bronchitis virus infection in line C White Leghorn chickens - J. K. A. Cook; T. F. Davison; M. B. Huggins; P. McLaughlan (Archives of Virology, 1991)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Dichloromethane utilized by an anaerobic mixed culture: acetogenesis and methanogenesis - Susanna A. Stromeyer; Wolfgang Winkelbauer; Herbert Kohler; Alasdair M. Cook; Thomas Leisinger (Biodegradation, 1991)

Initial steps in the degradation of benzene sulfonic acid, 4-toluene sulfonic acids, and orthanilic acid in Alcaligenes sp. strain O-1 - Thomas Thurnheer; Daniel Zrrer; Otmar Hglinger; Thomas Leisinger; Alasdair M. Cook (Biodegradation, 1990)

Monochloro- and dichloroacetic acids as carbon and energy sources for a stable, methanogenic mixed culture - Christine Egli; Markus Ther; Dieter Suter; Alasdair M. Cook; Thomas Leisinger (Archives of Microbiology, 1989)

Difference in metabolic profile of potassium canrenoate and spironolactone in the rat: Mutagenic metabolites unique to potassium canrenoate - Chyung S. Cook; Charles L. Hauswald; Grant L. Schoenhard; Charles E. Piper; Arun Patel; Frederick M. Radzialowski; Jeremy D. Hribar; William Aksamit; Pat Finnegan; Roy H. Bible; James A. Oppermann (Archives of Toxicology, 1988)

Detection and prevalence of serotypes of feline syncytial spumaviruses - R. L. P. Flower; G. E. Wilcox; R. D. Cook; T. M. Ellis (Archives of Virology, 1985)

The influence of the bone-implant interface stiffness on stress profiles surrounding Al2O3 and carbon dental implants - C. J. Lavernia; S. D. Cook; A. M. Weinstein; J. J. Klawitter (Annals of Biomedical Engineering, 1982)

Metabolite concentrations in Alcaligenes eutrophus H 16 and a mutant defective in poly-?-hydroxybutyrate synthesis - Alasdair M. Cook; Hans G. Schlegel (Archives of Microbiology, 1978)

Evidence for the in vivo regulation of glucose 6-phosphate dehydrogenase activity in Hydrogenomonas eutropha H 16 from measurements of the intracellular concentrations of metabolic intermediates - B. Bowien; A. M. Cook; H. G. Schlegel (Archives of Microbiology, 1974)

On the uniqueness of the flagellum ofThiobacillus thiooxidans - R. N. Doetsch; T. M. Cook; Z. Vaituzis (Antonie van Leeuwenhoek, 1967)

Une pidmie d'exanthme virus ECHO de type 16 en milieu hospitalier avec bilan d'une enqute longitudinale - J. Couvreur; C. M. Cook; Ch. Chany; J. Gerbeaux (Archives of Virology, 1963)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)

Sectional notes - Frank E. Garrett; Roy M. Barnes; W. Frank McGee; A. H. Eddins; W. B. Ward; Verne C. Beverly; H. A. Reiley; Allan W. Purdy; J. C. Campbell; H. J. Evans; Harold Mattson; O. D. Burke; et al. (American Journal of Potato Research, 1947)

The effect of different amounts of spindle tuber and leaf roll on yields of Irish potato - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)

Effect of different amounts of spindle tuber and leaf roll on yields of Irish potatoes - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)